Evaluating ex vivo toll-like receptor agonist response as a potential biomarker in equine gastric ulcer syndrome - Gustavo Ferlini Agne; Daniel Thomas Barratt; Bridget Eileen May; Mark R. Hutchinson; Joshua Holmes; Catherine Steel; Olivier Simon; Samuel Greig Evans; Andrew A. Somogyi; Benjamin W. Sykes; Samantha Franklin (The Veterinary Journal, 2026)

Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

A recombinase polymerase amplification-based rapid diagnostic assay for Dysmicoccus neobrevipes, a serious pest of banana in India, with notes on the damage symptoms, natural enemies, and management - J. Poorani; C. Anuradha; A. Mohanasundaram; R. Thanigairaj; P. Samuel; N. Baskar (Molecular Biology Reports, 2026)

California's plan to decarbonize electricity omits key greenhouse gas emissions - Marie-Odile P. Fortier; Amir Sharafi; Alyssa R. Pfadt-Trilling; Samuel A. Markolf (Energy Policy, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Spatial and demographic disparities between rural and urban electric vehicle adopters in Tennessee - Samuel Barbour; Christopher R. Cherry; Aaron Fellhoelter; Amin Mohamadi Hezaveh (Journal of Transport Geography, 2026)

Additional morphological data and first genetic characterization on females of Micropleura vazi Travassos, 1933, parasitic in Caiman yacare from Brazil, with comments on the phylogeny of Dracunculoidea (Nematoda) - Glória M. C. Lacerda; Fernando Paiva; Luiz E. R. Tavares; João A. de Araujo Filho; Samuel C. Ribeiro; Felipe B. Pereira (Systematic Parasitology, 2026)
Species of Micropleura Linstow, 1906 (Dracunculoidea: Nematoda) are common parasites of crocodilians worldwide. Studies related to this genus remain scarce, particularly regarding genetic characterizations, due to the difficulty in obtaining the parasite specimens. Although the morphology of M . vazi Travassos, 1933, a parasite of Caiman spp. in the Neotropics, has been previously evaluated, some morphological inconsistencies persist, and certain features are insufficiently described. Moreover, there is no genetic data for the species. In this regard, we provide the first genetic characterization of M . vazi along with detailed morphological analysis using light and scanning electron microscopy (SEM). We report for the first time in M . vazi the presence of phasmids and of oesophageal gland nuclei, in addition to provide a clearer view of the cephalic region and the accurate position of the vulva. Genetic characterization of the species was conducted using partial sequences of the 18S and 28S rDNA, and the phylogenetic reconstructions using these first indicated the monophyly of Micropleura and of most families within Dracunculoidea. Moreover, Micropleuridae appears to be the sister group to Dracunculidae, and Philonematidae should be considered valid as it is not close to Philometridae. Furthermore, Anguillicolidae should be allocated in another superfamily, Anguillicoloidea, which is basal relative to Dracunculoidea and far from it. The absence of males in the current sampling may suggest a seasonal occurrence of these parasites, as has been reported for other dracunculoid nematodes.

The influence of predator lethality on prey behavior and growth - Haleigh Nogueira; Samuel Sonnega; Eleanor R. DiNuzzo; Sarah C. Donelan; Michael J. Sheriff (Ecology, 2026)
Predators are known to impact prey populations through both consumptive and nonconsumptive effects, and the magnitude of prey responses has long been assumed to depend on the lethality of the predator. Yet, there are few, if any studies, that have empirically tested this assumption. While there are studies that have approximated lethality and provide support for this assumption, difficulties arise given there is a need to estimate encounter rates and subsequent predation events while simultaneously separating prey risk responses from such events to truly determine predator lethality. Without the separation of risk responses from predation events, predator lethality may be erroneously assigned; for example, a highly lethal predator may elicit strong and early antipredator responses from prey, reducing actual capture and consumption, making the predators ‘seem’ less lethal than they actually are. We used a marine crab‐snail system consisting of Carcinus maenas or Hemigrapsus sanguineus (crab predators) with Nucella lapillus (snail prey), pairing large and small crabs with large and small snails in a two‐phase mesocosm experiment. We first eliminated prey's behavioral risk responses to determine predator lethality and second estimated prey's risk responses after rendering the predators nonlethal. We found that the specific lethality of a predator for a given prey did not drive prey risk responses. Our most lethal treatments (large crabs paired with small snails) had similar risk responses to our least lethal treatments (small crabs paired with large snails). The greatest risk responses came from treatments with large crabs paired with large snails (only medium lethality). Thus, while our results do not support the assumption that lethality itself drives prey risk responses, we did find that overall snails responded the most to the largest predators. This is likely due to the ability of these predators to consume prey over a wide size range and prey's inability to recognize their own relative size. Furthermore, prey state (body size) is clearly an equal if not greater contributor to prey risk responses than a predator's ability to kill.

A tiered secondary poisoning risk assessment approach to prevent unnecessary fish bioaccumulation testing of pharmaceuticals - Gemma Janer; Joanne Elmoznino; Andreas Häner; Samuel K. Maynard; Dermot Reddy; Alison N. Perkins; Michael R. Lee; Todd Davidson; Shibin Li; Erick Nfon; Jan Woelz; Kelli Fagan Malott; et al. (Regulatory Toxicology and Pharmacology, 2026)

The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Barriers and facilitators to implementing the European code of cancer practice in a rural and coastal setting: a qualitative study - Shanice Thomas; Hannah Cumberland Keeble; Erica Brown; Sarah R. Baker; Samuel Cooke; Mark Lawler; Kathie McPeake; Kathy Oliver; Peter Selby; David Nelson (Cancer Causes & Control, 2026)
Purpose The European Code of Cancer Practice (ECCP) is a patient-centred framework for good clinical cancer practice, to improve outcomes for all of Europe’s patients [1]. Given challenges with applications to rural regions, the study aimed to explore the barriers and facilitators to implementing the ECCP in a rural, coastal, and urban context. Methods We conducted semi-structured individual and group interviews with nine acute cancer professionals; nine non-clinical professionals; and four people with lived experience of cancer. Interviews were analysed using reflexive thematic analysis, underpinned by a constructivist approach. Results Three themes were developed across all groups. 1) ‘Fragmented communication pathways limits access’ to information-sharing between services, and about support and research, linked to workforce challenges. 2) ‘Geographic and infrastructural disparities between urban, rural, and coastal areas’ highlight barriers to accessing and delivering care, including transport issues, alongside place-specific facilitators to wellbeing. 3) ‘Unmet needs for living well during and after treatment’ denotes financial, work-related, and psychological challenges through treatment and survivorship. These barriers transcended across all ECCP domains. Conclusion Workforce challenges that limit information-sharing about support and research, and gaps in post-treatment support, must be addressed to meet the ECCP aim to ensure equitable cancer care across geographical locations.

PFAS quantitation with diffusive gradients in thin-film passive samplers: Capturing time-weighted average concentrations around maximum contaminant levels to facilitate compliance - Brianna J. Harris; Samuel D. Hodges; David G. Wahman; Levi M. Haupert; Justin R. Chimka; Julian L. Fairey (Water Research, 2026)

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

The action of marimastat, a metalloprotease inhibitor, on the coagulant, hemorrhagic, and neuromuscular activities of Lachesis muta (South American bushmaster) venom - Vitória S. Proença-Hirata; Isabele N. Oliveira; Gabrielly C. Souza-Gomes; Samuel R. Dias; Hugo A. Ghirotti; Sofia N.S. Azevedo; Poliana J. Demico; Francis L. Pacagnelli; Rogério Giuffrida; Gisele A. Nai; Nelson J. Silva; Kristian A. Torres-Bonilla; et al. (Toxicon, 2026)

Functional morphotypes as proxies for large-scale assessment of marine nematode assemblages along the Indian coastline - Sanofar Khokher; Joydeep Dutta; Elisa Baldrighi; Amita Choudhury; Abhilash K. R.; Deepak Samuel (Regional Studies in Marine Science, 2026)

Non-tuberculous mycobacteria in cattle: Distribution, antimicrobial resistance and zoonotic implications in Tamil Nadu, India - Sundar Annadurai; Sureshkannan Sundaram; Porteen Kannan; Samuel Masilamoni Ronald; Rajagunalan S; Kannan Palaniyandi; Sivachandiran R; Elango Ayyasamy (Veterinary Research Communications, 2026)

More diverse diets and duller colours: seasonal insights into great tits urban life - Lisa Sandmeyer; Laurine A. Mathieu; Samuel P. Caro; Christophe de Franceschi; Johan R. Michaux; Adrien André; Anne Charmantier; Arnaud Grégoire; Claire Doutrelant (Urban Ecosystems, 2026)

Electrifying Sagar Island, West Bengal, India: advancing multiple SDGs through integrated coastal policy and sustainable development - Satyendra Kumar; Selvin Pitchaikani J; Deepak Samuel V; Ramesh R (Journal of Coastal Conservation, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Mitragynine reduces methamphetamine self-administration in rats without disrupting food-maintained responding - Lida Khodavirdilou; Julio D Zuarth Gonzalez; Sushobhan Mukhopadhyay; Nicholas Guadagnoli; Samuel Obeng; Christopher R. McCurdy; Lance R. McMahon; Jenny L. Wilkerson (Psychopharmacology, 2026)
Rationale Kratom ( Mitragyna speciosa ), a plant native to Southeast Asia, has become popular in the United States for its reported ability to treat substance use disorders (SUD). Mitragynine (MG) is the most abundant alkaloid found in kratom. Objectives The present studies evaluated whether MG decreases methamphetamine self-administration under both fixed-ratio (FR) and progressive-ratio (PR) schedules. In a separate cohort we examined whether MG would alter food-maintained responding. Methods Three separate experiments were conducted in male and female adult Sprague–Dawley rats. In Experiment 1, rats self-administered methamphetamine (0.032 mg/kg/infusion, intravenous) under a fixed-ratio (FR) schedule. In Experiment 2, a separate group received food pellets under a FR schedule. In Experiment 3, a different group received methamphetamine (0.032 mg/kg/infusion) under a progressive-ratio (PR) schedule. In all experiments rats received pretreatment with MG (10–56 mg/kg, intraperitoneal) or vehicle 30 min before testing. Behavioral measures included active and inactive lever presses, response rates, and in the case of PR, breakpoints. Results MG dose-dependently reduced methamphetamine delivery under both the FR and PR schedules, with significant decreases in active lever presses, and breakpoints at 32 and 56 mg/kg. Effects were generally comparable in males and females, without significant sex × treatment interaction detected. Conclusions MG decreased methamphetamine-maintained responding at doses that did not affect food-maintained responding, indicating a selective effect on methamphetamine reinforcement relative to natural reward. These findings identify MG as a compound with robust effects on methamphetamine-maintained behavior and support its continued evaluation in preclinical models of methamphetamine use disorder.

Ontogenetic co-option of myotoxin expression variation in island Eastern Diamondback Rattlesnake (Crotalus adamanteus) venoms - Ella G. Guedouar; Samuel R. Hirst; Shantal S. Solis; Dale Chaput; Mark J. Margres (Toxicon, 2026)

Translation-dependent retrograde signaling coordinates high-light acclimation in plants - Marten Moore; Aaron B. Smith; Melanie Wegener; Pravin B. Khambalkar; Rebeccah V. Tyrrell; Brea C. Watts; Samuel J. Nix; Hong Ting Tsang; Muhammad Ansar Farooq; Diep R. Ganguly; Robert T. Furbank; Maria Ermakova; et al. (Molecular Plant, 2026)

Hydrodynamic behavior and design implications in continuous-flow hydrothermal liquefaction systems - Dylan J. Cronin; Juliano Souza dos Passos; Alan H. Zacher; Uriah Kilgore; Andrew J. Schmidt; Samuel P. Fox; Michael R. Thorson (Fuel, 2026)

Scaling the Spatial and Temporal Effects of Wrack Disturbance Across a Saltmarsh Landscape - Matt J. Pierce; Tyler Lynn; Julie Grissett; Shelby Ziegler; Sydney Williams; Satyatejas Reddy; Samuel Dong; Cailyn Bowser; Merryl Alber; Steven C. Pennings; Deepak R. Mishra; Amanda C. Spivak; et al. (Estuaries and Coasts, 2026)
Disturbance effects are rarely distributed uniformly over space or time. Thus, scaling up the effects of disturbances requires detailed measurements across multiple spatial scales. To characterize disturbance from wrack we used monthly images from an unmanned aerial vehicle (UAV) in a 144,500 m 2 Spartina alterniflora saltmarsh on Sapelo Island, Georgia (USA), from March 2020 to December 2022. Prior work as well as the results of our study demonstrated that wrack persisting for ≥ 2 months (“persistent wrack”) affects underlying vegetation. During our study, persistent wrack comprised ~ 30% of the average monthly wrack area (161 m 2 or ~ 0.10% of the total S. alterniflora marsh) and showed an annual peak between July and September. We quantified the effects of persistent wrack on live S. alterniflora , two invertebrate taxa (snails and burrowing marsh crabs), and porewater via field surveys of paired wrack-affected and wrack-free controls. At each monthly sampling point relative to controls, S. alterniflora stem density in wrack-affected plots was 41% lower on average and snail density lower by 25%, while crab burrow abundance and porewater parameters remained similar between controls and disturbed plots. Using wrack area from monthly UAV imaging, we scaled-up plot-level effects to marsh-level and found a < 1% change per species in abundance. Thus, our data suggest that even if wrack has strong local effects, the effects can be minor in S. alterniflora marshes at a landscape scale. This study demonstrates that field monitoring to quantify the effects of disturbances, coupled with repeat UAV imagery, allows for scaling that better contextualizes the overall impact than either method alone.

Comparing phosphatised galleried stereom of Ordovician Cincinnaticrinus to modern Endoxocrinus illustrates preservation by micromolding - Benjamin F. Dattilo; Rebecca L. Freeman; David F. Wright; David L. Meyer; James R. Thomka; Samuel Sheray; Michael Harrison; Christopher D. Aucoin (Facies, 2026)
Fossil echinoderm ossicles are often occluded by syntaxial overgrowths which obscure stereom. Phosphatized ossicles from insoluble residues show fine microstructure. We investigated phosphatized stereom in Cincinnaticrinus columnals in insoluble residues from the Ordovician around Cincinnati, Ohio USA. Microstructures appeared to be stereom micromolds. We tested this hypothesis by examining residue and thin sections of undissolved sample using light microscopy, SEM and EDS, resulting in these observations: (1) calcite within phosphatized ossicles is optically aligned and parallel to stem; (2) phosphate deposited centripetally from calcite surfaces, often incompletely filling cavities, leaving a central vug; (3) while calcite is inclusion-free, phosphate contains siliciclastic inclusions from surrounding sediments. These observations suggest that calcite is original, and phosphate was deposited as micromolds. To confirm the phosphatic micromold hypothesis, we compared internodal columnals from the extant isocrinid Endoxocrinus from the Florida Straits using fracture surfaces and epoxy-impregnated thin sections. We then dissolved the thin section calcite, leaving epoxy micromolds for comparison. Schematic 3-D models summarize our reconstructions of structure of the crinoids in both original calcite and micromolds. Through-going solid cylinders are present in Cincinnaticrinus phosphate and Endoxocrinus epoxy molds. In Endoxocrinus , these are molds of stereomic galleries complete with ligaments, confirming Cincinnaticrinus phosphate is also moldic. Galleried stereom of the two crinoids differs in structural details, a divergence that is consistent with phylogenetic evidence of through-going ligaments in an early common ancestor. Preservation by phosphatic micro-molding, interpreted as preserved negative space, facilitates study of stereomic features supporting crinoid soft tissues.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Cyclooxygenase-dependent contribution to increased flow mediated dilatation following a week of repeated ischemic preconditioning - Samuel Thomas; Sophia R. Murphy; Sultan E. AlSalahi; Rehan T. Junejo (European Journal of Applied Physiology, 2026)
Purpose Ischemic preconditioning (IPC) and remote ischemic preconditioning (RIPC) independently enhance endothelial function and flow mediated dilation (FMD); yet the underlying mechanisms remain incompletely defined. This study investigated the contribution of cyclooxygenase (COX) dependent vasodilators to FMD before and after repeated IPC and RIPC. Methods 21 healthy participants underwent Radial artery FMD assessments before and after oral aspirin (600 mg) ingestion for COX inhibition. Participants then completed a one-weeklong alternate day unilateral IPC protocol (four repeated cycles of 5-minute ischemia and 5-minute reperfusion). 24 h after the final IPC session, FMD responses were reassessed before and after aspirin ingestion. Results Prior to IPC treatment, aspirin failed to significantly reduce FMD in both Radial arteries. Following IPC treatment, the now significantly increased FMD of the ipsilateral arm (9.50 ± 4.58% (mean ± standard deviation); p = 0.006) attenuated with aspirin (4.55 ± 2.68%; p = 0.002). Absolute difference in FMD % before and after aspirin ingestion increased from 1.48 ± 5.05% pre-IPC to 4.95 ± 4.96% ( p = 0.016) post-IPC. In the contralateral (RIPC) arm, increased FMD % also attenuated with aspirin ( p = 0.006) but this statistical significance was not seen following correction for shear rate. Nonetheless, absolute difference in FMD % before and after aspirin increased from 0.04 ± 4.05 pre-RIPC to 2.27 ± 3.60% ( p = 0.043) post-RIPC. Conclusion One week of alternate day IPC improves contribution of COX-derived vasoactive mediators to FMD. Contributions to RIPC driven improvements in FMD require further investigation.

Development of multivariate health index for tropical seagrass meadows: a case study from Pulicat Lagoon, India - C. Viswanathan; J. Joyson Joe Jeevamani; K. Balachandar; K. Arumugam; K. Paramasivam; Dipnarayan Ganguly; R. Muruganandam; V. Deepak Samuel; R. Purvaja (Environmental Monitoring and Assessment, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

AIS-driven vessel activity and emissions modelling for offshore decommissioning activities in the North Sea - Kate Gormley; Samuel R. Cauvin; Shahin Jalili; Malcolm Stone; Richard Neilson (Frontiers in Marine Science, 2026)
Introduction Maritime transport is a major source of air pollutants yet remains one of the least regulated sectors globally. In the North Sea, vessel activity associated with offshore energy infrastructure decommissioning is expected to increase over the next decade. However, vessel-specific emissions during these activities remain poorly quantified, with existing approaches relying largely on coarse-scale estimates. This study aimed to develop a data-driven, bottom-up methodology for estimating vessel emissions using Automatic Identification System (AIS) data to enable high-resolution spatial and temporal analysis of offshore energy-related shipping emissions. Methods A custom vessel-tracking tool was developed to process large AIS datasets collected between 2015 and 2021 for the northern North Sea. Vessel movements and operational patterns were reconstructed from AIS records, and emissions of carbon dioxide (CO 2 ), nitrogen oxides (NO x ), and sulphur dioxide (SO 2 ) were estimated based on vessel speed, operational activity, and engine characteristics. Emissions were spatially allocated to a 1 km 2 grid. The methodology was applied to three offshore decommissioning case study areas: Scott, Gannet, and Subsea, representing different infrastructure densities and operational stages within the marine energy sector. Sensitivity analyses were conducted to evaluate uncertainties associated with fuel consumption and auxiliary engine assumptions. Results Emissions were found to be highly localised around offshore installations and displayed strong temporal variability associated with episodic operational activity. Among the case study areas, Gannet exhibited the highest emissions intensity, contributing up to 5% of regional CO 2 emissions during peak operational periods. Correlations between vessel transits and emissions varied between sites, indicating that vessel counts alone do not adequately capture emissions behaviour. Operational modes such as idling and dynamic positioning were identified as important contributors to overall emissions. Sensitivity analysis demonstrated that assumptions relating to fuel consumption rates and auxiliary engine usage were key sources of uncertainty in the emissions estimates. Discussion The findings demonstrate that AIS-based bottom-up approaches can provide more accurate, transparent, and spatially resolved emissions estimates for offshore energy operations compared with conventional regional-scale methods. Incorporating operational vessel behaviour substantially improves emissions characterisation and highlights the importance of accounting for non-transit activities in offshore environments. This methodology has potential applications in emissions reporting, regulatory compliance, and decarbonisation planning for offshore energy systems undergoing transition and decommissioning.

Building climate resilient urban forests: Impacts of irrigation and heat on tree establishment in a legacy city - Erika R. Wright; Christopher B. Riley; Ellen Danford; Samuel F. Ward; Mary M. Gardiner (Urban Forestry & Urban Greening, 2026)

Network-Scale Patterns and Drivers of Microcystins in a Heavily Impacted Watershed - Jessica Lerminiaux; Kerri Finlay; Peter R. Leavitt; Samuel G. Woodman; Matthew J. Bogard (Ecosystems, 2026)

The resistance of lemon myrtle (Backhousia citriodora) to myrtle rust (Austropuccinia psidii) - Emily Kathryn Lancaster; Geoffrey Samuel Pegg; R. Andrew Hayes; André Drenth; David John Lee (Australasian Plant Pathology, 2026)
Lemon myrtle ( Backhousia citriodora , F. Muell.) is a native Australian myrtaceous species, highly valued for its unique, citral-rich essential oil. The development and success of this Australian industry has been in jeopardy since the detection of myrtle rust ( Austropuccinia psidii ) in Australia (April 2010). Since the initial invasion, it has spread across the major lemon myrtle growing regions in New South Wales and Queensland. The main commercial clones are highly susceptible to infection, with plantations experiencing up to 70% production losses. To identify resistance to A. psidii for industry use, disease assessments were conducted on germplasm originating from 13 Queensland provenances, established in two clonal field trials. Newly collected germplasm from the Ubobo provenance was also screened under controlled conditions. Infection caused symptoms ranging from small, restricted sori on a low percentage of leaves, to infection on up to 100% of leaves, with distorted shoots and severe dieback on infected stems. No fully resistant germplasm was identified, but significant differences in observed disease offer opportunities to select more resistant clones than those currently relied on by the industry. Germplasm from Eumundi, Noosa and Woondum (southern Queensland), and Silver Valley (northern Queensland), showed superior resistance to A. psidii across assessments and trial sites. Substantial variation in plant growth traits of importance to commercial production (e.g. canopy structure and foliage density) was observed among the provenances, families, and clones evaluated across the trials, suggesting the need to consider plant growth, biomass yield and essential oil properties when selecting industry-suitable germplasm. Implementing a breeding or hybridisation program should be a priority for the industry.

Time-resolved network metabolomics reveals metabolic reprogramming and network stability in cowpea leaves during virus infection - Raissa S. C. Bret; Silvio A. Cândido-Sobrinho; Samuel G. Abreu; Nicole P. Porto; David B. Medeiros; Leonardo Perez Souza; Murilo S. Alves; Alisdair R. Fernie; Danilo M. Daloso (Theoretical and Experimental Plant Physiology, 2026)
Cowpea severe mosaic virus (CPSMV) represents a major constraint for cowpea ( Vigna unguiculata (L.) Walp.) cultivation. However, the metabolic basis underlying CPSMV resistance remains poorly understood. Given the importance of metabolism for plant defence against pathogens, we hypothesized that cowpea resistance to CPSMV is associated to the activation of defence-related pathways from both primary and secondary metabolisms. We investigated the metabolic dynamics associated with CPSMV infection in the resistant cowpea genotype Macaibo using a time-resolved, network-based metabolomics approach. Conventional RT-PCR suggests that the intensity of the CPSMV coat protein band increased in the first eight H ours A fter CPSMV I noculation (HAI) but appeared reduced in the following 72 HAI. Metabolomic analyses revealed that CPSMV infection had little impact on secondary metabolism, whereas several primary metabolites were significantly altered over time. Transient increases in fumarate, pyruvate, and several amino acids, including alanine, asparagine, glutamine, glutamate, isoleucine, leucine, proline, serine, threonine, and valine, were observed at 48 HAI compared with mock-treated leaves. Network analysis indicated that overall metabolic network density and heterogeneity remained relatively stable during infection. However, a highly connected metabolic module composed of the branched-chain amino acids (BCAAs) isoleucine, leucine, and valine emerged in infected leaves. Our results indicate that CPSMV infection reshapes primary metabolic dynamics without extensive alterations in secondary metabolism during early infection in cowpea leaves. Despite these metabolic adjustments, the overall metabolic network structure remained stable, suggesting that a robust metabolic reprograming, including the activation of BCAA-associated pathways, may help buffer viral perturbation in cowpea leaves.

Functional redundancy shapes spatial patterns of vulnerability to climate-driven shifts in plant communities across Australia - Irene Martín-Forés; Rhys V. Morgan; Samuel C. Andrew; Rachael V. Gallagher; Greg R. Guerin (Science of The Total Environment, 2026)

Role of autonomic receptors in ethyl ferulate-induced cardiovascular effects in normotensive and hypertensive female rats - Francisca Valdirene de S. Nunes; Samuel S. P. Araujo; Juliana A. da Silva; José Guilherme V. de Assunção; Ariell A. de Oliveira; Carlos E. R. Dourado; Vandercley de O. Damasceno; Aldeídia P. de Oliveira; Maria do Carmo C. Martins; Mayara C. de Morais; Damião P. de Sousa; Thyago M. de Queiroz; et al. (Pflügers Archiv - European Journal of Physiology, 2026)
Aims Ethyl ferulate (EF) may offer novel benefits in hypertension. We investigated the contribution of autonomic receptors to EF-induced effects in female Wistar and SHR. Methods Anesthetized females received EF intravenously at 7.5, 15, or 30 mg/kg. Autonomic involvement was evaluated using pretreatment with atropine, atenolol, or hexamethonium. MAP and HR were continuously monitored. Results EF induced rapid and pronounced reductions in MAP and HR in both strains. In Wistar rats, muscarinic and nicotinic blockade significantly attenuated these responses. In SHR, atropine abolished bradycardia and partially mitigated hypotension, whereas β1-adrenergic and nitric oxide synthase inhibition had minimal impact. Conclusion EF acutely lowers MAP and HR, with muscarinic and nicotinic receptors driving the effects in normotensive females, and muscarinic pathways partially mediating responses in hypertensive females. These results position EF as a compelling candidate for antihypertensive therapy and underscore the critical need to study cardiovascular interventions in female hypertension models.

Transient tracer observations in the Gulf of St. Lawrence reveal shift from younger to older inflow waters - Lennart Gerke; Toste Tanhua; William A. Nesbitt; Samuel W. Stevens; Douglas W. R. Wallace (Ocean Science, 2026)
The deep waters of the Gulf of St. Lawrence (GSL) have experienced a significant reduction in dissolved oxygen content during the past decades. One widely documented driver of this deoxygenation is a change in the composition of the deep inflowing water that ventilates the Gulf, which consists of a mixture of warmer, less-oxygenated North Atlantic Central Waters (NACW) and cooler, more-oxygenated Labrador Current Waters (LCW). While previous studies have inferred changes in this inflow from hydrographic and biogeochemical observations, direct constraints on deep-water ventilation timescales have been lacking. Here, we present the first spatially-comprehensive measurements of transient tracers (SF6 and CFC-12) in the GSL, allowing direct estimates of tracer-derived mean ages and ventilation timescales throughout the deep layer. Mean ages increase systematically with density and exhibit a pronounced along-channel gradient, with younger waters (30–40 years) in the Lower St. Lawrence Estuary and older waters (50–60 years) toward Cabot Strait. This west-east increase in ventilation age is more gradual than corresponding changes in temperature and salinity, indicating that tracer-derived ages respond differently to variations in source water composition than hydrographic properties. The observed gradual age structure is consistent with a greater influence of older, earlier ventilated NACW in the eastern Gulf, while younger ages inland reflect a continued contribution of LCW. These results demonstrate that, as of 2022, the shift toward longer deep-water ventilation timescales, and associated changes in inflow properties toward higher NACW composition, is ongoing rather than having reached a steady end state, contrary to earlier predictions.

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

The larva-Symbiodiniaceae association at risk: putative impacts of climate change on reproduction, dispersal, and recruitment in coral reefs - Arthur Loures; Nils Rädecker; Christian R. Voolstra; Amana G. Garrido; Carla Zilberberg; Samuel C. Faria; Paulo Y. G. Sumida; Miguel Mies (Coral Reefs, 2026)

Further Description and First Genetic Characterization of Oswaldofilaria bacillaris (Nematoda: Onchocercidae) Infecting the Pantanal Caiman (Caiman yacare), with Insights into the Phylogeny of Oswaldofilaria - Glória M. C. Lacerda; Gustavo M. do Carmo; Lorena G. Ailán-Choke; Fernando Paiva; Luiz E. R. Tavares; João A. de Araújo-Filho; Samuel C. Ribeiro; Felipe B. Pereira (Acta Parasitologica, 2026)
Purpose Oswaldofilaria bacillaris is the type species of the genus, but its morphology remains little known and partially contradictory. Moreover, there are no genetic data and scanning electron microscopical observations on the species, like in most Oswaldofilaria spp. The phylogenetic relationships among Oswaldofilaria spp. are practically unknown. This study aimed to evaluate the detailed morphology of O . bacillaris , provide its first genetic characterization, and discuss the phylogenetic relationships within Oswaldofilaria . Methods Parasites infecting the body cavity of Caiman yacare in Pantanal wetlands, Mato Grosso do Sul, Brazil, were collected and processed for morphological studies using light and scanning electron microscopy. Genetic characterization was based on partial sequences of 18S and 28S rDNA. A phylogeny was reconstructed based on 28S sequences including all Oswaldofilaria available. Results Nematodes were assigned to O . bacillaris mainly based on the oral opening markedly displaced ventrally. Males had seven pairs of caudal papillae encircling the cloaca, and their two most posterior pairs were hardly visible, which is also characteristic in other congeners. Moreover, a delicate area rugosa previously unreported in the species was observed. Oswaldofilaria bacillaris formed a monophyletic assemblage with the congeners, being sister to O . chabaudi , and O . petersi was basal, these last two parasites of lizards. Conclusion The present findings strengthened the specific diagnosis of O . bacillaris and elucidated the morphological contradictions. The phylogeny reinforced the hypotheses that Oswaldofilaria emerged in lizards and colonized crocodilians by host switch, and reduction in number of caudal papillae in males is a derived feature.

Dynamic cycling and redox transformations of dissolved organic sulfur in the surface ocean - Molly A. Crotteau; Erin L. McParland; Alexandra A. Phillips; Elizabeth B. Kujawinski; Krista Longnecker; Aaron M. Martinez; Samuel M. Webb; Morgan R. Raven (Limnology and Oceanography, 2026)
The marine dissolved organic sulfur (DOS) pool contains both labile metabolites that are rapidly cycled in the surface ocean and compounds that may persist for thousands of years in the marine environment. Here, we describe the sulfur speciation of marine solid‐phase extracted DOS (DOS SPE ) from the North Atlantic surface ocean, revealing a diversity of oxidation states that include alkyl sulfides, disulfides, aromatics, sulfonates, and sulfate esters. As dissolved organic carbon concentrations decrease with depth in the water column, relative abundances of reduced sulfur species decrease while those of oxidized sulfur species increase, indicating preferential remineralization of reduced organic sulfur (OS) compounds. Although microorganisms are considered to be the origin of a vast majority of marine DOS SPE , the DOS SPE produced by cultures of phototrophs and heterotrophic bacteria is compositionally distinct and 34 S‐enriched relative to environmental DOS SPE . Ultimately, mechanisms spanning different timescales, including microbial reworking, uptake, and photochemical oxidation transform labile DOS in the surface ocean, and may generate recalcitrant compounds that contribute to the long‐lived dissolved organic matter pool. The oxidation states of OS function as powerful tools for tracking the sources, sinks, and transformations of organic matter in complex biogeochemical systems.

Environmental Variability Shapes Life‐History Trade‐Offs Within and Between Populations of a Long‐Lived Seabird - Bertille Mohring; Jonathan R. Potts; Alastair J. Wilson; Denis Réale; Richard A. Phillips; Henri Weimerskirch; Christophe Barbraud; Ashley Bennison; Karine Delord; Andrew G. Wood; Samuel Peroteau; Etienne Rouby; et al. (Ecology Letters, 2026)
Individuals face a trade‐off between allocating resources to reproduction or self‐maintenance, yet the drivers of the existence and strength of such trade‐off have been hard to determine. Environmental conditions are thought to play a crucial role, as long‐lived species are predicted to favour more precautionary life‐history strategies in variable environments. However, empirical evidence remains limited. Using long‐term monitoring of two black‐browed albatross Thalassarche melanophris populations, we investigated variation in life‐history strategies under contrasting environmental conditions, through reproductive senescence. In more variable environments, individuals displayed generally slower life histories (i.e., slow, late‐onset senescence) and greater among‐individual variation in life‐history strategies. Interestingly, earlier and faster reproductive senescence correlated with higher lifetime reproductive success regardless of environmental variability, suggesting that either faster life histories incur higher fitness or successful reproduction accelerates reproductive senescence. These findings reveal how environmental variability shapes life‐history strategies, highlighting potential responses to increasing environmental variability in a changing world.

Survey on new technologies and precision medicine to advance healthcare - R. Díaz Jiménez; Y. Trakadis; Collins Mokua; Denis Margalik; Hussam Alkaissi; Jadira Scott; Jake A. Ayisi; Jhena Hammond; Kamal Kant Sahu; Khadija Brouillette; Nneka Ede; Oluwaseun Akinkuolie; et al. (Journal of Community Genetics, 2026)

Chronostratigraphic grounds for the decision against formalizing an Anthropocene Epoch - Samuel R. Ribeiro (Anthropocene, 2026)

Photobiomodulation of tissue regeneration: low-power light therapy accelerates wound healing in earthworms - Saravanakumar Venkatachalam; Johnson Retnaraj Samuel Selvan Christyraj; R. Kamaraj Kennedy; Jackson Durairaj Selvan Christyraj; Beryl Vedha Yesudhason (Biologia Futura, 2026)

Genetic Surveillance Reveals Differential Evolutionary Dynamic of Anopheles gambiae Under Contrasting Insecticidal Tools Used in Malaria Control - Harun N. Njoroge; Lilian Namuli; Sanjay C. Nagi; Anastasia Hernandez‐Koutoucheva; Daniel P. McDermott; Erin Knight; Samuel Gonahasa; Amy Lynd; Ambrose Oruni; Catherine Maiteki‐Sebuguzi; Jimmy Opigo; Adoke Yeka; et al. (Molecular Ecology, 2026)
Malaria, a febrile disease caused by the Plasmodium parasites and transmitted by mosquitoes, is a leading cause of mortality in children under 5 in endemic countries. The widespread deployment of insecticide‐treated bed nets (ITNs) has significantly reduced malaria transmission, but rising levels of insecticide resistance threaten to halt the progress. Monitoring insecticide resistance is vital for effective vector control, particularly when deploying new tools. Understanding mosquito population responses to these interventions is crucial for guiding control programmes in making informed decisions about the selection, timing and geographic deployment of tools. This genomic study investigates the demographic and evolutionary consequences on the malaria vector Anopheles gambiae of deploying standard ITNs (containing only pyrethroids) and pyrethroid‐PBO nets (containing pyrethroids plus the synergist piperonyl butoxide) during a clinical trial in Uganda. Despite substantial reductions in indoor mosquito densities in the clinical trial, estimates of nucleotide diversity (π) and linkage disequilibrium revealed no significant decline in effective population size, reflecting continued large population size even after effective control. Marked allele frequency shifts at resistance‐associated loci indicated strong selection pressures driven by the interventions, with distinct selective dynamics between the two net types, highlighting alternative pyrethroid detoxification pathways in the presence of PBO. A duplication in the Cyp9k1 gene significantly increased in frequency in populations exposed to pyrethroid‐only nets but decreased in populations exposed to PBO‐treated nets, suggesting that selection for over‐expression of this gene is removed when this resistance mechanism is impacted by PBO. An alternative potential detoxification mechanism was selected within a region of the 2La chromosomal inversion on chromosome 2 L, which encompasses the UDP‐glucose 6‐dehydrogenase gene. This variant consistently increased in frequency when exposed to PBO‐treated nets. Additionally, pyrethroid‐only nets selected for a novel locus on the X chromosome containing the diacylglycerol kinase gene, which is potentially linked to behavioural adaptations through its role in neurotransmission modulation. Our findings underscore the importance of genomic surveillance in vector control, revealing distinct evolutionary dynamics of insecticide resistance mechanisms in the presence of PBO. While ITNs remain effective, the persistence and evolution of resistance‐associated alleles highlight the need for adaptive and dynamic resistance management strategies. By integrating high‐resolution genomic data with epidemiological and entomological monitoring, this study offers actionable insights to sustain malaria control efforts amid the ongoing challenge of insecticide resistance.

Resting-state motor network connectivity as a biomarker of Levodopa response in Parkinson’s disease - Emma E. Russo; Leif E. R. Simmatis; Kevin Kadak; Zoyeb Ehsan; Selma Sieber; Hannah Seo; Christina Xie; Aditya Pancholi; Emma Abray; Irene E. Harmsen; Nardin Samuel (Brain Imaging and Behavior, 2026)

Crop rotation phase has a greater impact on soil biology than crop rotation diversity - Marijke Struijk; Erika Degani; Samuel G. Leigh; Emma Bowen; Sion Thomas; Simon R. Mortimer; Andrew P. Whitmore; Frank Ashwood; Suzanne J. Clark; Tom Sizmur (Agriculture, Ecosystems & Environment, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Ecological Processes Shaping Marine Microbial Assemblages Diverge Between Equatorial and Temperate Time‐Series - Pedro C. Junger; Vinicius S. Kavagutti; Ina M. Deutschmann; Carlota R. Gazulla; Paula Huber; Maiara Menezes; Rodolfo Paranhos; André M. Amado; Isabel Ferrera; Janaina Rigonato; Samuel Chaffron; Josep M. Gasol; et al. (Molecular Ecology, 2026)
Marine microbial communities are structured by a complex interplay of deterministic and stochastic processes, yet how these vary across latitudes remains poorly understood. Most long‐term microbial observatories are restricted to temperate regions, limiting our ability to assess latitudinal contrasts in microbial dynamics. Here, we compare coastal microbial communities from two contrasting marine time‐series stations using standardised molecular protocols: a new tropical site in the Equatorial Atlantic (EAMO, 6° S) and a well‐studied temperate site in the Mediterranean Sea (BBMO, 41° N). Monthly 16S and 18S rRNA gene sequencing of two size‐fractions (0.22–3 μm and > 3 μm) over 41 months (from April 2013 to August 2016) revealed marked differences in taxonomic composition, temporal variability and ecological assembly processes. Temperate communities exhibited strong seasonal turnover, higher beta‐diversity and tighter coupling with environmental variables such as temperature and daylength. In contrast, tropical communities were compositionally more stable and more governed by biotic factors and stochastic processes such as historical contingency and ecological drift. These patterns were consistent across taxonomic domains and size‐fractions, though selection was generally stronger in prokaryotes and the smallest size‐fraction. Co‐occurrence networks at the temperate site were more densely connected and environmentally responsive compared to tropical networks, where stochastic processes and putative biological interactions gain prominence. This study highlights the importance of integrating observatories from underrepresented latitudes into global microbial monitoring efforts, particularly as climate change alters the amplitude and frequency of environmental drivers across the ocean.

Hidden Vulnerability: Extreme Drought Threatens Dryland Plant Communities Under Climate Change - Samuel W. Wilson; Rachel R. Renne; Ingrid C. Burke; William K. Lauenroth (Global Change Biology, 2026)
Extreme heat and drought are becoming more frequent, altering the distribution and disturbance cycles of plant communities. These weather events have caused widespread mortality of woody plant species globally. We investigated the environmental conditions preceding multiple shrub mortality events in a widespread North American dryland (big sagebrush ecosystems) using field and remote sensing data, a process‐based ecosystem water balance model, and historic weather data. We identified temperature and soil water conditions that were similar across sites preceding a mortality event. We used historic and future climate data with an ecosystem water balance model to investigate how the probabilities of these events have and will change relative to historic (1915–1980) frequencies under current conditions and future emissions scenarios. Our analysis showed that the frequency of these events is likely to increase and, in many areas, has already surpassed historical conditions. Last, we used 898 sites spread across big sagebrush ecosystems to understand the spatial variability of this increase in frequency of mortality‐related conditions. While the frequency of extreme hot and dry conditions is projected to increase, there is substantial variability across the region. Our findings highlight substantial risks of weather‐related mortality in regions previously projected to be relatively stable under climate change, suggesting that extreme events may represent an underappreciated dimension in modeling efforts.

Phylogeographic analyses detect population structure and limited gene flow in the Peacock Grouper Cephalopholis argus across Micronesia - Pavithiran Amirthalingam; Samuel Greaves; Joseph M. O’Malley; Eva Schemmel; Victoria Marciante; Michelle R. Gaither (Frontiers in Marine Science, 2025)
Coral reefs are patchily distributed across vast areas of Earth’s tropical and subtropical oceans. Dispersal of individuals between habitat patches is essential to maintain genetic connectivity between subpopulations and plays an important role in population persistence. While the biotic and abiotic factors that influence patterns of dispersal have received a great deal of attention, fundamental questions about genetic connectivity in marine systems remain largely unanswered. Micronesia, in the northern central Pacific, is comprised of over two thousand islands that stretch across 7,400,000 km 2 and is thought to provide stepping-stones for dispersal between the central and western Pacific. Despite its size and importance, few phylogeographic studies have focused on Micronesia and none have been conducted in the Mariana Archipelago in northern Micronesia. Here we examined population structure in the peacock grouper Cephalopholis argus across the region. Based on ~15,000 SNPs we found three population clusters: the Mariana Archipelago, western Micronesia (Palau) and eastern Micronesia (Pohnpei and Kwajalein). These findings are largely concordant with two previous studies and taken together they highlight the influence of the North Equatorial Current and the North Equatorial Countercurrent in the Central Pacific and indicate that perhaps broad scale ecosystem level processes and not species-level traits are driving population patterns in the region. Furthermore, we detected little genetic structure across 800 km of the Mariana Archipelago and found that rates of gene flow among the islands were higher in the north but diminished at Anatahan and continued to decrease southward toward Saipan and Guam. Our data also indicate that the Mariana Islands receives more migrants from the Central Micronesian islands to the south then it exports, and that Guam, the southernmost island in the archipelago, may serve as an important gateway from the Central Pacific into the Mariana Islands.

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Philippine functional foods: A new frontier in noncommunicable diseases prevention - Myra O. Villareal; Lotis E. Mopera; Gladys C. Completo; Ruel C. Nacario; Marissa V. Romero; Katherine Ann T. Castillo-Israel; Rona Camille M. Lizardo-Agustin; Marianne Joy G. Laya; Roi Miguel M. Obdosantos; Christel Leo O. Romano; Jocelyn E. Serrano; Samuel C. Bobiles; et al. (Food and Humanity, 2025)

Bridging in vitro and in vivo inhalation toxicity: Volatile organic compounds elicit similar transcriptomic points of departure in human airway cells and mouse respiratory tract - Thomas W. Jackson; Jessica R. Murray; Celia M. Schacht; Paul A. Evansky; Michael E. Monsees; Joshua A. Harrill; M. Ian Gilmour; Andrew F. Johnstone; Wanda C. Williams; Rachel D. Grindstaff; Mette C. Schladweiler; Samuel A. Vance; et al. (Environmental Pollution, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Emerging Pollutants in Soil and Water: Sources, Risks, and Advances in Removal Technologies for Sustainable Management - Rashmi Singh; M. K. Harsha Varthan; R. S. Rejith Kumar; M. Rohinth; Z. H. Tawfeeq Ahmed; S. M. Indumathi; Suvarshitha Pusuluru; Sai Kumar Punna; Karrun Velmurugan; Melvin Samuel; Selvarajan Ethiraj (Environmental Management, 2025)

Land cover, drought, and dust emission in arid Succulent Karoo shrublands - Heleen C. Vos; Johanna R. von Holdt; Helga van der Merwe; Igshaan Samuels; Ute Schmiedel; Norbert Jürgens; Juliane Krenz; Mmoto L. Masubelele; Bavisha Koovarjee; Wolfgang Fister; Frank D. Eckardt; Clement Cupido; et al. (Aeolian Research, 2025)

The Genomics Revolution in Nonmodel Species: Predictions vs. Reality for Salmonids - Samuel A. May; Samuel W. Rosenbaum; Devon E. Pearse; Marty Kardos; Craig R. Primmer; Diana S. Baetscher; Robin S. Waples (Molecular Ecology, 2025)
The increasing feasibility of whole‐genome sequencing has been highly anticipated, promising to transform our understanding of the biology of nonmodel species. Notably, dramatic cost reductions beginning around 2007 with the advent of high‐throughput sequencing inspired publications heralding the ‘genomics revolution’, with predictions about its future impacts. Although such predictions served as useful guideposts, value is added when statements are evaluated with the benefit of hindsight. Here, we review 10 key predictions made early in the genomics revolution, highlighting those realised while identifying challenges limiting others. We focus on predictions concerning applied aspects of genomics and examples involving salmonid species which, due to their socioeconomic and ecological significance, have been frontrunners in applications of genomics in nonmodel species. Predicted outcomes included enhanced analytical power, deeper insights into the genetic basis of phenotype and fitness variation, disease management and breeding program advancements. Although many predictions have materialised, several expectations remain unmet due to technological, analytical and knowledge barriers. Additionally, largely unforeseen advancements, including the identification and management applicability of large‐effect loci, close‐kin mark–recapture, environmental DNA and gene editing have added under‐anticipated value. Finally, emerging innovations in artificial intelligence and bioinformatics offer promising new directions. This retrospective evaluation of the impacts of the genomic revolution offers insights into the future of genomics for nonmodel species.

Individual identification of bony fishes using unique body markings: Implications and applications - Katie Dunkley; Samuel R. Matchette; Cheuk Yu Hau; Christian Drerup; Roxanne B. Holmes; Yvonne Sadovy de Mitcheson; James E. Herbert‐Read (Journal of Fish Biology, 2025)
The natural variation in animal body markings, such as spots, stripes and blotches, offers a powerful tool for researchers, conservationists, citizen scientists and resource managers to distinguish specific individuals within species. By building libraries of photo‐identified individuals, we can track and differentiate individuals over time and space, thereby non‐invasively and often cost‐effectively studying species' biology and behaviour. This, in turn, enhances our understanding of species' ecological roles, and informs and supports effective conservation strategies. Although photo‐identification has been successfully applied to various aquatic species, including cetaceans, sharks and rays, it remains surprisingly underutilised for bony fishes. Indeed, despite their striking diversity of colours and patterns, relatively few studies have used natural markings to non‐invasively investigate bony fish biology and conservation. In this review, we highlight the potential of photo‐identification as a valuable research and management tool for these fishes in both field and laboratory environments. We outline the scientific, practical and ethical benefits of this approach, illustrating how individual identification can advance our understanding of fish biology and support their conservation efforts. We also discuss previous applications of photo‐identification in bony fishes, examine barriers to its broader adoption and address common misconceptions that may limit its use. We propose strategies to overcome these challenges driven by advancements in camera technology and artificial intelligence, and discuss scenarios where photo‐identification may prove particularly effective. Through this review, we therefore aim to encourage the broader use of natural body markings as a non‐invasive method in bony fish research, management and conservation.

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

Response of land plants to the Toarcian Oceanic Anoxic Event: Palynology of a Pliensbachian–Toarcian section from the Rodiles Formation at Lastres (Asturias, NW Spain) - Samuel F. Rial; Artai A. Santos; Sam M. Slater; Iván R. Barreiro; Laura Piñuela; José Carlos García-Ramos; José B. Diez (Global and Planetary Change, 2025)

Isolating the light dependence of carbon isotope fractionation in Gephyrocapsa (Emiliania) huxleyi - Ann Pearson; Pratigya J. Polissar; Susan J. Carter; Elida Kocharian; Samuel R. Phelps; Oscar D. Hover; Raquel P. Reis; Emily Kuang; Lorelei M. Wolf (Geochimica et Cosmochimica Acta, 2025)

Chronic sublethal exposure to methylmercury lengthens telomeres in developing zebra finches - Rachel L. Davis; Samuel D. Mason; Christian Wake; Giulia Fabozzi; William L. Catalano; Chaim A. Schramm; Amy R. Henry; Cokie L. Parker; Farida Laboune; Casey L. McLaughlin; Jeffrey D. Kittilson; John P. Swaddle; et al. (Environmental Pollution, 2025)

In-situ measurements reveal alkalinity release from cold-temperate seagrass meadows - Samuel Scott-Askin; Isaac R. Santos; Gerli Albert; Maria E. Asplund; Diana Deyanova; Sara C. Forsberg; Aurora M. Ricart; Martin Gullström; Mats Björk; Gloria M.S. Reithmaier (Estuarine, Coastal and Shelf Science, 2025)

Spatial patterns of sandy beach habitat use by mobile invertebrates vary with wrack type and tide phase - Kyle A. Emery; Samuel G. Rivera; Andrew Pettit; Jessica R. Madden; Nicholas K. Schooler; David M. Hubbard; Jenifer E. Dugan (Estuarine, Coastal and Shelf Science, 2025)

The coupled oxygen and carbon dynamics in the subsurface waters of the Gulf and Lower St. Lawrence Estuary and implications for artificial oxygenation - William A. Nesbitt; Samuel W. Stevens; Alfonso O. Mucci; Lennart Gerke; Toste Tanhua; Gwénaëlle Chaillou; Douglas W. R. Wallace (Ocean Science, 2025)
The Gulf and Lower St. Lawrence Estuary have experienced major environmental change over the past century, including the development of hypoxic bottom waters and their simultaneous warming and acidification. Here, we use biogeochemical observations collected during the 2021–2023 TReX project as well as historical data, integrated with a tracer-calibrated 1D Advection-Diffusion model with variable boundary conditions to represent dissolved oxygen (DO) and dissolved inorganic carbon (DIC) dynamics within the core of the oxygen minimum zone (27.15–27.3 kg m−3 isopycnals) of the Laurentian Channel. The rate of in-channel oxygen utilization in the deep layer was nearly invariant from 2003 to 2023 at 21.1 ± 2.5 µmol kg−1 yr−1 and the DIC accumulation rate was estimated to be 18.3 ± 2.5 µmol kg−1 yr−1. Using δ13CDIC data, we assess the effect of microbial organic matter remineralization processes and dilution of the 13CDIC pool (-6.6×10-3 ‰ µmol−1 of added metabolic DIC). This combination of long-term observations and tracer-informed transport modeling helps reconcile differences in prior estimates of biogeochemical transformation rates and improves our ability to predict deepwater DO and DIC cycling. Finally, we apply the model to the mitigation scenario proposed by Wallace et al. (2023) for artificial re-oxygenation of the Laurentian Channel bottom waters using pure oxygen. We estimate that the injection of ∼ 8.3 × 105 t yr−1 of oxygen, equivalent to an additional 55 µmol kg−1 relative to the 2023 boundary concentration proximal to the Cabot Strait, would be required to achieve and maintain above hypoxic levels (>62.5 µmol kg−1) at the head of the Laurentian Channel. Using the model, we estimate the time required to re-establish steady-state along-channel distributions of DO and DIC following a change in offshore boundary conditions to be about 10 years, or twice the along-channel transit time. This study provides new long-term characterizations of deepwater DO and DIC cycling and offers a first-order assessment of the feasibility of large-scale re-oxygenation in the Gulf and Lower St. Lawrence Estuary.

Oropharyngeal aspiration of particulate hexavalent chromium increases chromium levels in lung and liver, and induces essential metal dyshomeostasis in lung, liver, and blood - Idoia Meaza; Jamie L. Wise; Sandra S. Wise; Haiyan Lu; Aggie R. Williams; Morgan Delnicki; Jack Easley; J. Calvin Kouokam; John Pierce Wise; Samuel T. Vielee; James T.F. Wise; Rachel M. Wise; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Association Between Household Food Security, Dietary Quality and Breastfeeding Duration: An Analysis of NHANES 2015-2018 - S. Samuel; R. Mathews; J. Komakech; M. Yang (Journal of the Academy of Nutrition and Dietetics, 2025)

Mapping Plant Functional Traits Using Gap‐Filled Datasets to Inform Management and Modelling - Samuel C. Andrew; Irene Martín‐Forés; Greg R. Guerin; David Coleman; Daniel S. Falster; Elizabeth Wenk; Ian J. Wright; Rachael V. Gallagher (Global Ecology and Biogeography, 2025)
Aim Plant traits are used to describe the functional properties of vegetation that are critical to terrestrial ecosystem services. Functional trait metrics for plant communities can be valuable for modelling important ecosystem properties such as fuel loads and nutrient cycling, future plant diversity and responses to global change. However, the vast scale of plant diversity means collecting trait and distribution data for all species globally is logistically challenging. Here, we evaluate the utilisation of gap‐filling methods for providing more comprehensive functional trait metrics for plant communities. Location Australia. Time Period Current. Major Taxa Studied Australian native plants. Methods Here we use gap‐filled species‐level functional trait data and species distributions for Australia to map continental scale averages and variability in four core traits related to resource competition, energy budgeting and reproductive investment (maximum height, seed mass, leaf area and leaf mass per area [LMA]). We explore how trait patterns relate to climate (temperature and precipitation) and validate our mapping using comparable trait metrics derived from a network of 747 plot‐based plant species inventories across the continent (AusPlots). Results Trait maps for maximum height, seed mass and leaf area were strongly and positively correlated, while mean LMA and LMA variability were negatively correlated with other trait means. Biogeographic patterns of trait averages and variability could be mostly explained (78% to 92% of variance) by annual precipitation and mean annual temperature, and their interaction. LMA was an exception, with only 46% of variance in spatial patterns explained. Main Conclusions Similar trait‐climate trends from trait maps and plot‐based inventories give clarity to an outstanding question of whether trait mapping captures patterns also evident in higher‐resolution field‐based studies. Our results indicate that trait maps reliably recreate known patterns, albeit at a greater scale, and can be applied to ecosystem dynamics modelling and other pursuits such as conservation prioritisation.

Delirium in hospitalized COVID-19 patients is associated with dynamic changes in peripheral immune gene expression - Sara C. LaHue; Naoki Takegami; Rubinee Simmasalam; Abiya Baqai; Elena Munoz; Anya Sikri; Thibault du Buisson de Courson; Nilika S. Singhal; Walter Eckalbar; Charles R. Langelier; Carolyn M. Hendrickson; Carolyn S. Calfee; et al. (GeroScience, 2025)
Delirium is a neurologic syndrome characterized by inattention and cognitive impairment frequently encountered in medically ill older adults. As a hallmark of age-related brain vulnerability, delirium offers a clinical model to investigate how peripheral immune responses contribute to acute brain dysfunction. Peripheral inflammation is a key trigger of delirium, but the patient-specific immune responses that drive delirium onset and recovery remain poorly understood. This retrospective cohort study of prospectively collected biospecimens examines RNA sequencing from peripheral blood mononuclear cells of adults hospitalized for COVID-19 to better understand patient-specific factors associated with delirium ( n = 64). Longitudinal transcriptomic analyses highlight persistent immune dysregulation in delirium, marked by increasing expression trajectories of genes linked to innate immune pathways, including complement activation, cytokine production, and monocyte/macrophage recruitment. Genes involved adaptive immunity showed a declining trajectory over time in patients with delirium. Although corticosteroid treatment suppressed some aspects of immune hyperactivation, aberrant responses contributing to delirium were exacerbated. Delirium resolution was characterized by normalization of key transcripts such as CCL2 and innate immune markers. Novel associations with delirium included transcripts related to stress granule assembly and the T cell regulators DUSP2 and KLF10 . Delirium in COVID-19 is associated with distinct and dynamic peripheral immune trajectories that are modulated by corticosteroids. Further understanding these mechanisms has important implications for preventing delirium in older adults. These findings provide novel mechanistic insights with translational relevance for immunomodulatory strategies targeting maladaptive immune responses to prevent or treat delirium in medically ill populations.

Evaluation of antifouling surfaces using a method that employs mussel larvae settlement quantified by machine learning - Thomas B. LeFevre; Joseph D. Daddona; Wilaiwan Chouyyok; Gordon King; Samuel M. Pennell; Andrew E. Plymale; Stony Akins; Lance W. Miller; Navaj Nune; Clare N. Hermanson; George T. Bonheyo; Curtis Larimer; et al. (Biofouling, 2025)

Assessing hand hygiene in food manufacturing: The feasibility of CCTV surveillance - Ellen W. Evans; Emma J. Samuel; Sharon Mayho; Claudiu-Alin Turila; Helen R. Taylor; Elizabeth C. Redmond (Food Control, 2025)

A review of the utility and application of relatedness and kinship in elasmobranchs - Samuel R. Amini; Pierre Feutry; Nicole M. Phillips; Peter M. Kyne (Reviews in Fish Biology and Fisheries, 2025)
Understanding relatedness is fundamental to the fields of reproductive and social behaviour, trait-based analysis, population connectivity, and threatened species management. While relatedness has been studied in a broad range of terrestrial and aquatic taxa, research is often limited for species that are difficult to sample or persist in low densities. Elasmobranchs (sharks and rays) are one the most imperilled vertebrate clades in the world, with one third of all species being threatened with extinction. In this review, we examine the application of relatedness in studies of elasmobranchs, explore common challenges and limitations faced, provide best practice recommendations, and highlight knowledge gaps to guide future work. A systematic search identified 107 studies published between 2001 and November 2024 that focus on 65 species from 10 orders and 25 families. These studies used relatedness to investigate the reproductive behaviour, population genetics, demography, and social behaviour of elasmobranchs. Results highlight significant taxonomic biases, temporal patterns in marker use and research categories, and the need for a unified analytical framework to guide future work. This review provides a foundation for understanding how relatedness has been applied to date in studies of elasmobranchs and outlines future directions to advance the field.

Reconstructing Late Pleistocene relative sea levels on transgressed shelves: an example from central California - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad; Devin Rand (Quaternary Science Reviews, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

On the sensitivity of Optimum Multiparameter Analysis: a California Current System case study - Mercedes Pozo Buil; Isaac Schroeder; Steven J. Bograd; Michael G. Jacox; Elliott L. Hazen; Dianne Deauna; Emanuele Di Lorenzo; Nicole S. Lovenduski; Samuel Mogen; Ryan R. Rykaczewski (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Decreases in chimpanzee respiratory disease signs and enteric viral quantity following implementation of anthroponotic disease prevention protocols at a long-term research site - Jacob D. Negrey; Samuel Angedakin; Rachna B. Reddy; Aaron A. Sandel; Salmah Jombela; Erone Akamumpa; Christopher Aliganyira; Charles Birungi; Davis Kalunga; Brian Kamugyisha; Diana Kanweri; Godfrey Mbabazi; et al. (Biological Conservation, 2025)

Scrutinizing Acalitus simplex Flechtmann et Etienne (Eriophyidae): an eriophyoid mite associated with Ruellia spp. (Acanthaceae) - Marcello De Giosa; Livia M. S. Ataide; Adam G. Dale; Daniel A. Hahn; Xingbo Wu; Ronald Ochoa; Samuel Bolton; Kevin R. Cloonan; Alexandra M. Revynthi (Experimental and Applied Acarology, 2025)

Was Scotland covered by an ice sheet during Marine Isotope Stage 4? Insights from the pre‐Last Glacial Maximum marine terraces of northwest Scotland - Alexander R. Simms; Regina DeWitt; Sarah L. Bradley; Emily Huffman; Louise Best; Tom Bradwell; Jeremy M. Lloyd; Samuel B. Kachuck (Journal of Quaternary Science, 2025)
Raised shorelines provide important constraints on past sea levels, glacial isostatic adjustment (GIA), and rates and directions of vertical crustal motion. Although most raised shorelines across NW Scotland relate to post‐Last Glacial Maximum (LGM) glacial‐isostatic rebound, many undated shorelines lie above the marine limit established from isolation basins. Here, we present new optically stimulated luminescence (OSL) ages for a raised marine terrace at an elevation of 28 m in Slaggan Bay of NW Scotland. Four OSL ages suggest the feature is pre‐LGM, likely Marine Isotope Stage (MIS) 3. Global mean sea levels (GMSL) during MIS 3 are thought to have been ~40–60 m below present across most of the globe. We use a pair of GIA models to determine what ice sheet and sea‐level scenarios might provide an explanation for these anomalously high sea levels during MIS 3. Our results suggest that in the absence of tectonic activity, such high MIS 3 shorelines across NW Scotland require a MIS 4 ice sheet in Scotland, with postglacial rebound of the crustal depression following its demise during MIS 3 responsible for the elevated shoreline features at that time.

Editorial Expression of Concern: Human placental mesenchymal stromal cell therapy restores the cytokine efflux and insulin signaling in the skeletal muscle of obesity-induced type 2 diabetes rat model - Nagasuryaprasad Kotikalapudi; Samuel Joshua Pragasam Sampath; Sukesh Narayan Sinha; R. Bhonde; Sathish Kumar Mungamuri; Vijayalakshmi Venkatesan (Human Cell, 2025)

Deep learning approach to detect and visualize sexual dimorphism in monomorphic species - Nicolas J. Silva; André C. Ferreira; Liliana R. Silva; Samuel Perret; Sonia Tieo; Julien P. Renoult; Rita Covas; Claire Doutrelant (Animal Behaviour, 2025)

Barbatimão bark as an alternative to sodium lasalocid in finishing diets for lambs: Carcass characteristics and meat quality - Aylpy R.D. Santos; Cristiane R. Barbosa; Carla G. Souza; Tatiane Fernandes; Renata A. Chagas; Samuel R. Navarro; Alexandre R.M. Fernandes; Fernando M. Vargas Junior (Meat Science, 2025)

The Relationship Between Perceived Discrimination and Reported Nutrient Intake Among Pregnant Individuals of Minoritized Racial and Ethnic Groups - Tatyana Johnson; Ann K. Kan; Lauren B. Bonner; Linda Van Horn; Kiarri N. Kershaw; William A. Grobman; Karen L. Lindsay; Michelle P. Debbink; Brian M. Mercer; David M. Haas; George R. Saade; Uma Reddy; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Reliability of satellite-based vegetation maps for planning wildfire-fuel treatments in shrub steppe: Inferences from two contrasting national parks - Samuel “Jake” Price; Chad R. Kluender; Matthew J. Germino; Thomas Rodhouse (Journal of Environmental Management, 2025)

Recovery of Saltmarsh Macroinfauna After the Deepwater Horizon Oil Spill - Manisha Pant; John W. Fleeger; David Samuel Johnson; Rita Riggio; Aixin Hou; Donald R. Deis; Scott Zengel (Estuaries and Coasts, 2025)
To examine invertebrate community recovery after the 2010 Deepwater Horizon oil spill, we monitored the recovery of macroinfauna in replicated reference, moderately and heavily oiled salt marshes in Barataria Bay Louisiana for 8.5 years after the spill. Plants suffered near 100% mortality in heavily oiled marshes, profoundly altering the sedimentary environment. Plants in moderately oiled marshes did not suffer extensive mortality but experienced reduced above- and belowground plant biomass. A community analysis based on 40 macroinfaunal taxa was conducted during early (2011–2012), middle (2013–2017), and late (2017–2018) stages of recovery. The early stage was marked by very low taxonomic diversity (< 1–4 taxa per sample) and low total macroinfaunal abundance (0– < 8000 m −2 ) across all marshes, while the middle stage was denoted by relatively high diversity (7–8 taxa per sample) and very high abundances in heavily oiled marshes where densities exceeded reference and regional means by factors of 4–5. The community in the heavily oiled marshes diverged from reference and moderately oiled marshes during the middle recovery period when the crustaceans Apocorophium louisianum and Leptochelia rapax , the polychaete Alitta succinea , and oligochaetes dramatically increased in abundance, while at the same time, abundance increases of the polychaetes Manayunkia aestuarina , Streblospio gynobrachiata , and Capitellidae sp. lagged behind increasing trends at reference and moderately oiled sites. Macroinfaunal community similarity in moderately oiled marshes differed from reference and heavily oiled marshes in the middle recovery stage but did not differ from reference sites the during late recovery stage. Heavily oiled community similarity not only differed from moderately oiled and reference marshes in all three recovery stages but remained different from reference sites on the last collection date. These observations indicate that moderately oiled marshes recovered by about 8 years, but that heavily oiled marshes will likely require more than a decade to reach equivalency with reference sites.

A Framework for Modelling Thermal Load Sensitivity Across Life - Pieter A. Arnold; Daniel W. A. Noble; Adrienne B. Nicotra; Michael R. Kearney; Enrico L. Rezende; Samuel C. Andrew; Verónica F. Briceño; Lauren B. Buckley; Keith A. Christian; Susana Clusella‐Trullas; Sonya R. Geange; Lydia K. Guja; et al. (Global Change Biology, 2025)
Forecasts of vulnerability to climate warming require an integrative understanding of how species are exposed to, are damaged by, and recover from thermal stress in natural environments. The sensitivity of species to temperature depends on the frequency, duration, and magnitude of thermal stress. Thus, there is a generally recognized need to move beyond physiological metrics based solely on critical thermal limits and integrate them with natural heat exposure regimes. Here we propose the thermal load sensitivity (TLS) framework, which integrates biophysical principles for quantifying exposure with physiological principles of the dynamics of damage and repair processes in driving sublethal impacts on organisms. Building upon the established thermal death time (TDT) model, which integrates both the magnitude and duration of stress, the TLS framework attempts to disentangle the accumulation of damage and subsequent repair processes that alter responses to thermal stress. With the aid of case studies and reproducible simulation examples, we discuss how the TLS framework can be applied to enhance our understanding of the ecology and evolution of heat stress responses. These include assessing thermal sensitivity across diverse taxonomic groups, throughout ontogeny, and for modular organisms, as well as integrating additional stressors in combination with temperature. We identify critical research opportunities, knowledge gaps, and novel ways of integrating physiological measures of thermal sensitivity to improve understanding and predictions of thermal vulnerability at various scales across life.

Machine learning and physics-based model hybridization to assess the impact of climate change on single- and dual-axis tracking solar-concentrated photovoltaic systems - Samuel Chukwujindu Nwokolo; Anthony Umunnakwe Obiwulu; Paul C. Okonkwo; Rita Orji; Theyab R. Alsenani; Ibrahim B. Mansir; Chukwuka Orji (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Unveiling growth and carbon composition of macroalgae with different strategies under global change - Camino F. de la Hoz; Paul R. Brooks; Jennifer Coughlan; Inés Mazarrasa; Elvira Ramos; Samuel Sainz-Villegas; Araceli Puente; Jose A. Juanes; Tasman P. Crowe (Marine Environmental Research, 2025)

Cryptic species, biogeography, and patterns of introgression in the fish genus Mogurnda (Eleotridae) from the Australian wet tropics: A purple patch for purple-spots - Samuel R. Amini; Mark Adams; Michael P. Hammer; Glenn Briggs; James A. Donaldson; Brendan C. Ebner; Peter J. Unmack (Molecular Phylogenetics and Evolution, 2025)

Excessive Gestational Weight Gain, Independent of Body Mass Index, Is Associated With Child Fat Mass Index at Age 2 Years in the Growing life, Optimizing Wellness Study - Margaret Ballard; Jessica L. Saben; Rebecca A. Krukowski; Elisabet Børsheim; Clark R. Sims; Hallie Samuel; Lisa Jansen; Aline Andres (Journal of the Academy of Nutrition and Dietetics, 2025)

Nanoparticulate and colloidal uranium and plutonium in spent nuclear fuel storage pond effluents - Thomas S. Neill; Katherine Morris; Scott Harrison; Pete Apps; Nick Bryan; Stephen Parry; J. Frederick W. Mosselmans; Giannantonio Cibin; Bruce Rigby; Francis R. Livens; Samuel Shaw (Journal of Hazardous Materials, 2025)

Citizen science reveals relationships between human hunting pressure and the abundance and behaviour of invasive lionfish (Pterois spp.) - Roxanne B. Holmes; Samuel R. Matchette; James E. Herbert-Read (Biological Invasions, 2025)
Predation can shape the distribution and abundance of animals in an environment, with a major source of predation in some systems now coming from humans. However, measuring the influence of human activities on animal behaviour across large geographic ranges can prove challenging. Here we use a citizen science approach to assess relationships between human hunting pressure and invasive lionfish abundance and behaviour across the Western Atlantic and Caribbean. We collected information from SCUBA diving lionfish hunters about their hunting frequency and observations of lionfish abundance and behaviour. Areas which had been more recently invaded had the highest abundances of lionfish, but the number of lionfish hunters reported in recently invaded areas was lowest. While there was no relationship between the number of hunters in an area and the propensity of lionfish to form groups or utilise shelters, lionfish were more likely to be encountered deeper in areas where there were more hunters. In addition, larger maximum group sizes of lionfish were found at locations with more hunters, and this coincided with areas where lionfish were encountered deeper and where larger maximum catch sizes were reported. This study demonstrates how citizen science can be used to approximate differences in the abundance of organisms and collate observations of their behaviour across wide geographic areas. This approach could be particularly valuable in tracking invasion fronts as invasive species spread.

Interspecific carnivore competition and ungulate predation correlate with predator species richness - Nathaniel H. Wehr; Hailey M. Boone; Merijn van den Bosch; Alejandra Zubiria Perez; Katelyn L. Wehr; Samuel R. Wehr; Jerrold L. Belant (Ecology, 2025)
Competition for resources underlies the development of ecological community structure and function. Niche compression occurs when species reduce resource use due to competition, and niche complementarity posits resource competition should occur sequentially among habitat, time, and food. Within this context, interspecific predator competition can be influenced by prey characteristics and landscape attributes. We examined drivers of interspecific competition among carnivores using a database of North American ungulate cause‐specific mortality published during 1970–2021. We used weighted logit‐linked beta‐binomial generalized linear mixed models to assess the influence of seven predator species, ungulate age class, and landscape characteristics (i.e., human footprint, terrain ruggedness, and forest cover) on ungulate predation mortality. We predicted that (1) predation by individual predator species would decrease with increasing predator species richness mediated by predator size, (2) landscape characteristics would mediate predation by individual predator species, and (3) juvenile ungulate predation would increase with increasing predator species richness. As predator species richness increased, the proportions of predation attributed to individual predator species decreased, but the overall proportion of ungulate mortality attributed to predation increased. Juvenile ungulates experienced greater predation mortality than adults, with smaller predators predating proportionally more juveniles than larger predators. Landscape metrics altered observed predation patterns among caribou ( Rangifer tarandus ), wherein predation corresponded to terrain ruggedness but not predator species richness, and mule deer ( Odocoileus hemionus ), wherein predation increased with greater forest cover. We provide evidence for niche compression and complementarity using a top–down predator‐centric approach by showing compression in prey resources and increased predation mortality with increasing predator species richness. However, landscape characteristics had limited effects on predator competition at large spatial extents, which counters niche complementarity. Collectively, our results support the importance of large predators to ecosystem structure and efforts to conserve and restore predator guilds.

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Solid rocket motor insulation adhesives with sporicidal activity promote planetary protection for deep space missions - Natalie R. Williams; Morgan R. Sisk; Thomas P. Lampton; Yo-Ann Velez Justiniano; Samuel W. Harris; Courtney M. Higgins; Zahra A. Hooda; Gianni Z. Parello; Ashley E. DeSilva; Chelsi D. Cassilly; Mark H. Bray; Mark R. Liles (Life Sciences in Space Research, 2025)

Energy options for brackish groundwater desalination in Western Australia - Hao Wu; Samuel R. West; Jennifer A. Hayward (Desalination, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Spatial distribution and radiological hazards assessment of naturally occurring radionuclide materials in soil from quarry sites in Ogun State, Nigeria - David O. Jegede; T. Adeniyi Afolabi; Foluso O. Agunbiade; T. Adeleke Afolabi; Olusegun O. Ogundiran; Muideen R. Gbadamosi; Samuel O. Sojinu; Oluseyi Z. Ojekunle; Pakorn Varanusupakul (Environmental Monitoring and Assessment, 2025)
Workers and dwellers around quarrying sites are exposed to naturally occurring radioactive materials (NORMs) during various activities done on the rock and earth crust. This study investigated the spatial distribution and radiological health effects of quarrying activities in ten quarry sites in three districts (Odeda, Ajebo, and Ijebu Ode) around Ogun State, Nigeria. The NORMs ( 40 K, 238 U, 232 Th) were assessed using a gamma spectrometer with a NaI(Tl) detector. The radiological hazards of NORMs were assessed and statistically analyzed. The activity concentration of NORMs (Bq/kg) ranged from 40 K (76.8 ± 44.8–2647.9 ± 179.4), 238 U (3.2 ± 1.8–55.4 ± 24.9), and 232 Th (5.2 ± 3.9–244.4 ± 89.8) revealing 70% of all samples above the world average limit 420( 40 K), 33( 238 U), and 45 ( 232 Th). The activity concentration of NORMs in all the sites followed in the order 238 U < 232 Th < 40 K. The radiological and health parameter ranges for the adsorbed dose rate (D R ) 3.0–339.92 (nGy/h), radium equivalent (Ra eq ) 5.88–739.4 (Bq/kg), annual effective dose equivalent outdoor (AEDEout) 3.72–417.16(µSvy −1 ), excess lifetime cancer risk (ELCR × 10 −3 ) 0.01–1.46, and exposure rate (ER) 13.10–1531.47(µRh −1 ). The radiological hazard parameters are 2–3 times higher than their world averages in most of the samples thus discouraging the usage of the soil for building and ecological activities. This study showed that radionuclides are priority pollutants with high impact and with high exposure risk tendencies in all the quarry sites investigated and therefore unsuitable for ecological and building activities.

How land property rights affect the effectiveness of payment for ecosystem services: A review - Haojie Chen; Matthew R. Sloggy; Samuel Evans (Land Use Policy, 2025)

A Cryptococcus neoformans polysaccharide conjugate vaccine made with filtered polysaccharide elicits protective immunity in mice - Piotr R. Stempinski; Paola Ramos Irizarry; Scott A. McConnell; Livia C. Liporagi Lopes; Samuel Rodrigues Dos Santos Júnior; Maggie P. Wear; Arturo Casadevall (Fungal Biology, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Spermidine toxicity in Saccharomyces cerevisiae due to mitochondrial complex III deficiency - Wei-Hsuan Su; Jessica J. Smith; Evien Cheng; Megan S. Nishitani; Catherine Y. Choi; Kelsey R. Lee; Alexia Pardos Salzano; Samuel E. Schriner (Biogerontology, 2025)
Spermidine is a naturally occurring polyamine present in all cells and is necessary for viability in eukaryotic cells. The cellular levels of spermidine decline as an organism ages, and its supplementation has been found to extend lifespan in yeast, worms, flies, mice, and human cultured cells. The lifespan extending effect of spermidine is thought to be due to its ability to induce autophagy, a turnover of cellular components. Mitochondrial dysfunction is believed to be a major driver of the aging process. We asked whether spermidine could rescue mitochondrial dysfunction using the yeast Saccharomyces cerevisiae lacking mtDNA (ρ 0 cells) as a model. Not only was spermidine unable to rescue survival in ρ 0 cells, but it appeared to exhibit toxicity resulting in a shortened lifespan. This toxicity appears to not be due to the loss of mitochondrial respiration, elevated oxidative stress, or depleted ATP. Spermidine toxicity could be recapitulated by the genetic or pharmacological inactivation of mitochondrial complex III. It can also be prevented by the impairment of autophagy, through the inactivation of ATG8 , or by impairment of mitochondrial complex II through the inactivation of SDH2 . Spermidine toxicity in ρ 0 cells was present in yeast strains BY4741 and W303, but not D273-10B, demonstrating genetic variance in the phenotype. Thus, caution may be suggested regarding the use of spermidine to alleviate aging in humans. Depending on the genotype of the individual, spermidine could potentially harm the very individuals it is intended to help. Graphical abstract

Responses of Non-Target Arthropods to the dsRNA Bioinsecticide Calantha™ and Conventional Insecticides Targeting Colorado Potato Beetle, Leptinotarsa Decemlineata (Say) - Erik J. Wenninger; Samuel P. DeGrey; Jonas Insinga; Eric Knopf; Andrei Alyokhin; Ethann R. Barnes; Ben Bradford; Russell L. Groves; Brian Manley; Julia Piaskowski (American Journal of Potato Research, 2025)
Management of the Colorado potato beetle ( Leptinotarsa decemlineata ) is reliant on conventional insecticides that can negatively affect non-target arthropods. Calantha™ (active ingredient: ledprona) is a sprayable double-stranded RNA biopesticide specific for L decemlineata proteasome subunit beta 5 gene that triggers the RNA-interference pathway and is designed to have limited non-target effects. To test this hypothesis, we conducted two years of field trials in Idaho, Wisconsin, and Maine comparing arthropod responses to different insecticide regimes, with and without Calantha, targeting the Colorado potato beetle. Comparisons of arthropod abundance among treatments showed no evidence of effects of Calantha on non-target arthropods, including beneficials (predators, parasitoids), “neutrals” (i.e., non-pests), and other beetle species. Conventional insecticides generally showed more non-target effects, and responses were always stronger for arthropods from vacuum samples than pitfall samples. Insecticide programs featuring Calantha, especially in rotation with other biorational products, may reduce pests while preserving beneficial arthropods and contribute to biological control of arthropod pests in potato fields.

Do Chemosynthetic and Coral Communities Defy Deep‐Sea Ecological Paradigms? - Erik E. Cordes; Ryan Gasbarro; Andrea M. Quattrini; April Stabbins; Samuel E. Georgian; Robert S. Carney; Charles R. Fisher (Global Ecology and Biogeography, 2025)
Aim Broad biodiversity patterns (e.g., the latitudinal diversity gradient) are cornerstones of ecology that are fundamental in understanding the distribution of life on the planet. In the deep sea, declining faunal abundance/biomass with depth and a mid‐continental slope diversity maximum are among the most well‐defined patterns. However, they have largely been tested with samples of sediment faunal communities. Here, we synthesise new biomass, density, and diversity data with existing data from chemosynthetic and cold‐water coral (CWC) communities spanning > 3000 m depth to test the validity of these paradigmatic hypotheses in deep‐sea communities associated with hard substrata. Location Continental slope of the northern Gulf of Mexico (~200–4000 m depth). Time Period Present day. Major Taxa Studied Deep‐sea macrofaunal communities associated with soft‐sediment and hardgrounds (e.g., CWCs and cold seeps). Methods Relationships between macrofaunal abundance and biodiversity versus depth were tested with Generalised Additive Models. Habitat suitability model outputs were used to assess changes in CWC habitat over depth. Beta diversity partitioning was used to quantify richness and replacement components of community turnover with depth. Results We did not find support for these paradigmatic patterns in either chemosynthetic or CWC communities; instead, we found idiosyncratic biodiversity patterns with high abundance and diversity maintained across depths. Main Conclusions Our results suggest that seascape‐scale biodiversity patterns of the seafloor should be reappraised with due consideration for geological and biogenic habitat heterogeneity. We discuss the roles of localised energy sources, nutrient recycling/retention, and species adaptations as potential drivers of the high biodiversity and steady or increasing abundance at depths with relatively little sinking detrital carbon. Our results have major implications for the management of regional and global marine biodiversity, with the increasing evidence that chemosynthetic, cold‐water coral, and other hard‐substratum ecosystems are widespread throughout the global ocean and increasingly threatened by anthropogenic and climate stressors.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Environmental visual complexity increases the foraging success of mesopredators by promoting explorative behaviours - Samuel R. Matchette; Samuel J. Butler; Charles E. Redfern Llanos; James E. Herbert-Read (Animal Behaviour, 2025)

Managing the recovering saltwater crocodile population in a marine protected area with human-wildlife conflict: A population viability analysis approach - V. Deepak Samuel; J. Joyson Joe Jeevamani; Yusuke Fukuda; R. Muruganandam; Meeta Biswal; R. Ramesh; R. Purvaja (Journal for Nature Conservation, 2025)

Eco-phenological drivers of black gram (Vigna mungo (L) Hepper) productivity in diverse environments and their implications for crop improvement - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Anil K. Singh; Jai Dev; Samuel Jaberson; Ajaj A. Lone; S.P. Das; Shayla Bindra; R.K. Panwar; Ashok Kumar; et al. (Field Crops Research, 2025)

Functional Diversity of Seagrass-associated Macrofaunal Assemblages in a Brackishwater Lagoon of India: A multi-trait Approach - K. Paramasivam; K.R. Abhilash; C. Praveen Raj; C. Viswanathan; R. Sankar; J. Joyson Joe Jeevamani; Darwin Ramteke; V. Deepak Samuel; R. Purvaja (Thalassas: An International Journal of Marine Sciences, 2025)

In Vitro-In Vivo Correlation Of Amorphous Solid Dispersion Enabled Itraconazole Tablets - Ana L. Coutinho; Asmita Adhikari; Samuel Krug; Maureen Kane; R. Gary Hollenbeck; Stephen W. Hoag; James E. Polli (Pharmaceutical Research, 2025)

Correction: Dysfunctional cardiac energy transduction, mitochondrial oxidative stress, oncogenic and apoptotic signaling in DiNP-induced asthma in murine model - Samuel Abiodun Kehinde; Abosede Temitope Olajide; Tolulope Peter Fatokun; Dalia Fouad; Najah R. Hadi; Ahmed M. Elgazzar; Adewale Segun James; Mohamed H. Mazhar Ashour (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dysfunctional cardiac energy transduction, mitochondrial oxidative stress, oncogenic and apoptotic signaling in DiNP-induced asthma in murine model - Samuel Abiodun Kehinde; Abosede Temitope Olajide; Tolulope Peter Fatokun; Dalia Fouad; Najah R. Hadi; Ahmed M. Elgazzar; Adewale Segun James; Mohamed H. Mazhar Ashour (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Root Growth, Leaf and Root Chemical Composition Along Coffee Fruit Development - Welliton de Magalhães; Samuel Coelho Araújo; Paulo R. Cecon; Mateus Antero Nogueira; Herminia E. Prieto Martinez (Journal of Soil Science and Plant Nutrition, 2025)

Potential Crawling Distance for an Invading Urban Tree Pest: Implications for Settling Decisions and Between-Tree Movement - Erika R. Wright; David E. Long; Kristy M. McAndrew; Thomas G. Paul; Afsoon Sabet; Isaac O. Riggins; Ariadna Santos Chaves; Rebecca M. Ward; Samuel F. Ward (Journal of Insect Behavior, 2025)
Scale insects are prevalent urban landscape pests and are considered to move between neighboring trees via wind-aided and phoretic dispersal by cryptic, short-lived crawlers. Crawling likely plays a central role in these dispersal processes by shaping their ability to move onto phoretic hosts or to locate host plants and/or settling locations after being blown off a tree. Additionally, walking capabilities of crawlers drive on-tree movement, such as how far they disperse before settling. Here, we studied movement of the damaging, non-native crapemyrtle bark scale (CMBS), Acanthococcus lagerstroemiae (Hemiptera: Eriococcidae). We aimed to determine survival times for crawlers under starved conditions, evaluated crawler walking distances on various substrates, and combined survival times and walking distances from these experiments to simulate potential walking distances over the lifetime of the crawler stage and 1, 6, 12, 18, 24, 48, and 72-h intervals. We found that half of the crawlers survived approximately three days, with < 25% surviving up to seven days. On different substrates, crawlers walked five times farther on average on carboard than white posterboard over 15-min periods; crawling distances did not significantly vary during 5-min trials using colored construction paper, however. Combining these results, we estimated crawlers could move a median distance of 62 m (range: 2–211 m) if they walked for the entirety of their life as a crawler. These findings provide insight into a vulnerable life stage of scale insects and suggest that crawlers blown off of trees could walk to new hosts and easily move between adjacent trees.

Climate change risk assessment for adaptation planning in Indian agriculture - C. A. R. Rao; B. M. K. Raju; A. Islam; AVMS Rao; K. V. Rao; R. C. Gajjala; N. K. Ramaraju; P. Matyam; S. R. Kotha; S. Bhaskar; S. K. Chaudhari; V. K. Singh; et al. (Mitigation and Adaptation Strategies for Global Change, 2025)

Socioecological drivers of injuries and aggression in female and male rhesus macaques (Macaca mulatta) - Melissa A. Pavez-Fox; Erin R. Siracusa; Samuel Ellis; Clare M. Kimock; Nahiri Rivera-Barreto; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Noah Snyder-Mackler; James P. Higham; Delphine De Moor; Lauren J. N. Brent (Behavioral Ecology and Sociobiology, 2025)
Competition over access to resources, such as food and mates, is one of the major costs associated with group living. Two socioecological factors believed to drive the intensity of competition are group size and sex ratio. However, empirical evidence linking these factors to physical aggression and injuries is scarce. Here, we leveraged 10 years of data from free-ranging female and male rhesus macaques to test whether group size and adult sex ratio predicted the risk of inter and intrasexual aggression, as well as injury risk. We found evidence for an optimal group size at which the risk of intragroup aggression was minimized for both sexes. Despite male-male aggression being lowest in mid-sized groups, males in smaller groups experienced higher injury risk, suggesting within-group aggression might not be the main cause of male injury. Additionally, we found that sex ratio influenced aggression, but not injury risk. Specifically, female aggression toward other females was heightened during the birth season when groups had fewer available males, suggesting either female competition for male friends or exacerbated female-female competition due to the energetic costs of lactation. Male aggression towards females was higher in female-biased groups during the birth season and in male-biased groups during the mating season, which could reflect male competition with females over feeding opportunities and male coercion of females, respectively. Together, these findings provide insights into fitness costs (i.e., injury risk) of inter and intrasexual competition in primates in relation to key aspects of social organization. Significance statement While theory suggests that group size and sex ratio influence competition, studies linking these factors to aggression and injury rates are limited. Using long-term data on demography, aggression, and injury from a group-living primate, we show that both males and females experience aggression less often at intermediate group sizes. However, males in smaller groups faced higher injury risks. Although sex ratio did not predict injury risk, it did influence intra- and intersexual aggression, with patterns varying by reproductive season. Overall, our findings provide insights into how competition shapes intra and intersexual dynamics in relation to aspects of social organization.

Using eDNA to Supplement Population Genetic Analyses for Cryptic Marine Species: Identifying Population Boundaries for Alaska Harbour Porpoises - Kim M. Parsons; Samuel A. May; Zachary Gold; Marilyn Dahlheim; Christine Gabriele; Janice M. Straley; John R. Moran; Kimberly Goetz; Alexandre N. Zerbini; Linda Park; Phillip A. Morin (Molecular Ecology, 2025)
Isolation by distance and biogeographical boundaries define patterns of population genetic structure for harbour porpoise along the Pacific coast from California to British Columbia. Until recently, inadequate sample sizes in many regions constrained efforts to characterise population genetic structure throughout the coastal waters of Alaska. Here, tissue samples from beachcast strandings and fisheries bycatch were supplemented with targeted environmental DNA (eDNA) samples in key regions of Alaska coastal and inland waters. Using a geographically explicit, hierarchical approach, we examined the genetic structure of Alaska harbour porpoises, using both mitochondrial DNA (mtDNA) sequence data and multilocus SNP genotypes. Despite a lack of evidence of genetic differentiation from nuclear SNP loci, patterns of relatedness and genetic differentiation from mtDNA suggest natal philopatry at multiple geographic scales, with limited gene flow among sites possibly mediated by male dispersal. A priori clustering of sampled areas at an intermediate scale (eastern and western Bering Sea, Gulf of Alaska and Southeast Alaska) best explained the genetic variance (12.37%) among regions. In addition, mtDNA differentiation between the Gulf of Alaska and eastern Bering Sea, and among regions within the Gulf of Alaska, indicated significant genetic structuring of harbour porpoise populations in Southeast Alaska. The targeted collection of eDNA samples from strata within Southeast Alaska was key for elevating the statistical power of our mtDNA dataset, and findings indicate limited dispersal between neighbouring strata within coastal and inland waters. These results provide evidence supporting a population boundary within the currently recognised Southeast Alaska Stock. Together, these findings will prove useful for ongoing management efforts to reduce fisheries conflict and conserve genetic diversity in this iconic coastal species.

From bench to bedside: murine models of inherited and sporadic brain arteriovenous malformations - Ashely R. Ricciardelli; Gael Genet; Nafiisha Genet; Samuel T. McClugage; Peter T. Kan; Karen K. Hirschi; Jason E. Fish; Joshua D. Wythe (Angiogenesis, 2025)
Brain arteriovenous malformations are abnormal vascular structures in which an artery shunts high pressure blood directly to a vein without an intervening capillary bed. These lesions become highly remodeled over time and are prone to rupture. Historically, brain arteriovenous malformations have been challenging to treat, using primarily surgical approaches. Over the past few decades, the genetic causes of these malformations have been uncovered. These can be divided into (1) familial forms, such as loss of function mutations in TGF-β (BMP9/10) components in hereditary hemorrhagic telangiectasia, or (2) sporadic forms, resulting from somatic gain of function mutations in genes involved in the RAS-MAPK signaling pathway. Leveraging these genetic discoveries, preclinical mouse models have been developed to uncover the mechanisms underlying abnormal vessel formation, and thus revealing potential therapeutic targets. Impressively, initial preclinical studies suggest that pharmacological treatments disrupting these aberrant pathways may ameliorate the abnormal pathologic vessel remodeling and inflammatory and hemorrhagic nature of these high-flow vascular anomalies. Intriguingly, these studies also suggest uncontrolled angiogenic signaling may be a major driver in bAVM pathogenesis. This comprehensive review describes the genetics underlying both inherited and sporadic bAVM and details the state of the field regarding murine models of bAVM, highlighting emerging therapeutic targets that may transform our approach to treating these devastating lesions.

Use of alternatives to animal testing for Environmental Safety Assessment (ESA): Report from the 2023 EPAA partners’ forum - Jose V. Tarazona; Ana Fernandez-Agudo; Ondrej Adamovsky; Marta Baccaro; Natalie Burden; Bruno Campos; Björn Hidding; Karen Jenner; David John; Katia Lacasse; Adam Lillicrap; Delina Lyon; et al. (Regulatory Toxicology and Pharmacology, 2025)

Test and tune: evaluating, adjusting and optimising the stiffness of hydrogels to influence cell fate - Peiqi Yang; Gareth Boer; Finn Snow; Alysha Williamson; Samuel Cheeseman; Rasika M. Samarasinghe; Aaqil Rifai; Ayushi Priyam; Roey Elnathan; Roseanne Guijt; Anita Quigley; Rob Kaspa; et al. (Chemical Engineering Journal, 2025)

Fuzzy logic modelling of the pollution pattern of potentially toxic elements and naturally occurring radionuclide materials in quarry sites in Ogun State, Nigeria - David O. Jegede; T. Adeniyi Afolabi; Foluso O. Agunbiade; Olatunde S. Oladeji; Muideen R. Gbadamosi; Samuel O. Sojinu; Oluseyi Z. Ojekunle; Pakorn Varanusupakul (Environmental Geochemistry and Health, 2025)
The accumulation pattern of some inorganic pollutants in quarry sites around Ogun State was modeled using a Fuzzy comprehensive assessment (FCA). Potentially toxic elements (PTEs) and naturally occurring radionuclides materials (NORMs) were assessed from soil samples collected from ten quarry sites in three districts (Odeda, Ajebo, and Ijebu Ode) in Ogun State. Three (3) NORMs ( 40 K, 238 U, and 232 Th) were assessed using gamma spectrometer with a NaI detector while ten (10) PTEs (As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) were determined by digestion method using Inductively coupled plasma optical emission spectrophotometer. The FCA was used to evaluate soil contamination, and SPSS version 21.0 was used for statistical analysis. Concentration range of PTEs(mg/kg) and NORMs(Bq/kg) in all the site are: As (5.62 ± 0.85 – 15.93 ± 2.40), Cd (BDL—1.26 ± 0.60), Co (5.56 ± 1.34 – 27.25 ± 1.14), Cr (18.68 ± 1.54 -61.43 ± 6.33), Cu (12.40 ± 1.31—82.43 ± 7.94), Fe (15,035.00 ± 81.12 – 36,520.00 ± 292.20), Mn (168.97 ± 5.93 – 353.30 ± 20.84), Ni (5.63 ± 1.99- 25.54 ± 2.50),),Pb (4.44 ± 0.8 – 17.87 ± 2.80) and Zn (42.97 ± 413 – 147.00 ± 7.50); 40 K (76.78 ± 44.76—2647.88 ± 179.44), 238 U (3.24 ± 1.82—55.42 ± 24.88),and 232 Th (5.24 ± 3.90—244.36 ± 89.84). The results were modeled into a membership function matrix of three pollution classes. The FCA of NORMs revealed that 30, 10, and 60% of the sites were pristine, moderately polluted, and heavily polluted. In comparison, the FCA of PTEs confirmed 100% of the sites to be heavily polluted due to the accumulative effect of the PTEs. A high percentage of membership in the extremely impacted class is linked to a high concentration of Fe in all the sites due to the soil's geological structure and natural activities. At the same time, 40 K and 238 U have high-impact membership in all the quarry sites. Based on the findings, there is a need for stringent pollution control measures, targeted monitoring of PTEs and NORMs and the development of region-specific environmental regulations to protect both public health and ecosystems.

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

The relative influence of climate extremes and species richness on the temporal variability of bird communities - Samantha M. Cady; Samuel D. Fuhlendorf; Craig A. Davis; Barney Luttbeg; Caleb P. Roberts; Scott R. Loss (Ecology, 2025)
Understanding the relationship between biodiversity and ecological stability is increasingly urgent as rapid species extinction continues. Though evidence of positive diversity–stability relationships is accumulating, empirical results are inconsistent, and effect sizes tend to be small, raising questions about relative contributions of intrinsic (i.e., species composition/interactions) and extrinsic (i.e., environmental) drivers of stability. Community stability may be more strongly influenced by environmental conditions than by community diversity in some contexts, yet little is known about the comparative importance of diversity and climate means, extremes, and variability in regulating stability. We used a half‐century of continental‐scale bird data to quantify avian community temporal variability (a metric often used to approximate ecological stability) at 1379 sites and compared relative effects of climatic variables and species richness. We found that extreme heat and extremely low precipitation at decadal scales are associated with high bird community variability and these climate variables outperformed species richness in terms of variance explained and magnitude of effect. This provides empirical support for the theoretical concept that, at a continental, decadal scale, environmental conditions can play a larger role than intrinsic factors in determining community stability. Our findings also increase understanding of how climate extremes cause diverse ecological responses.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Corrigendum to “In vitro anticoagulant effects of Bungarus venoms on human plasma which are effectively neutralized by the PLA2-inhibitor varespladib” [Toxicon Volume 252, December 2024, 108178] - Abhinandan Chowdhury; Bryan G. Fry; Stephen P. Samuel; Ashish Bhalla; Sakthivel Vaiyapuri; Parul Bhargava; Rebecca W. Carter; Matthew R. Lewin (Toxicon, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

Root length as a bioindicator of pesticide concentration in irrigation water - Amanda M. Queiroz; Montcharles S. Pontes; Marisa D. Scherer; Daniela E. Graciano; Anderson R. L. Caires; Samuel L. Oliveira (Environmental Science and Pollution Research, 2024)

Challenges and opportunities for integrating aquaculture with commercial fishing in Maine - Caitlin Cleaver; Teresa R. Johnson; Samuel P. Hanes (Marine Policy, 2024)

In vitro anticoagulant effects of Bungarus venoms on human plasma which are effectively neutralized by the PLA2-inhibitor varespladib - Abhinandan Chowdhury; Bryan G. Fry; Stephen P. Samuel; Ashish Bhalla; Sakthivel Vaiyapuri; Parul Bhargava; Rebecca W. Carter; Matthew R. Lewin (Toxicon, 2024)

Using mercury and lead stable isotopes to assess mercury, lead, and trace metal source contributions to Great Salt Lake, Utah, USA - Samuel F. Lopez; Sarah E. Janssen; Michael T. Tate; Diego P. Fernandez; Christopher R. Anderson; Grace J. Armstrong; Thomas C. Wang; William P. Johnson (Science of The Total Environment, 2024)

Decadal changes in microplastic accumulation in freshwater sediments: Evaluating influencing factors - Jutamas Bussarakum; William D. Burgos; Samuel B. Cohen; Kimberly Van Meter; Jon N. Sweetman; Patrick J. Drohan; Raymond G. Najjar; Jill M. Arriola; Katharina Pankratz; Lisa A. Emili; Nathaniel R. Warner (Science of The Total Environment, 2024)

Differences in urban arthropod communities may not limit the nestling diet of a generalist songbird - Isaac J. VanDiest; Korin R. Jones; Taylor E. Fossett; Samuel J. Lane; Kendra B. Sewall (Science of The Total Environment, 2024)

Factors contributing to pesticide contamination in riverine systems: The role of wastewater and landscape sources - Samuel A. Miller; Kaycee E. Faunce; Larry B. Barber; Jacob A. Fleck; Daniel W. Burns; Jeramy R. Jasmann; Michelle L. Hladik (Science of The Total Environment, 2024)

Aerobic performance in rats subjected to incremental-speed running exercise: A multiple regression analysis study emphasizing thermoregulation-related variables - Marcelo T. Andrade; Nicolas H.S. Barbosa; Roberto C.S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V.R. Andrade; Alexandre S.R. Hudson; Thales N. Prímola-Gomes; et al. (Journal of Thermal Biology, 2024)

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

Autophobic polydimethylsiloxane nanodroplets enable abrasion-tolerant omniphobic surfaces - Behrooz Khatir; Peter Serles; Tao Wen; Thu V. Vuong; Ali Shayesteh; Samuel Au; David Sinton; Emma R. Master; Tobin Filleter; Kevin Golovin (Chemical Engineering Journal, 2024)

Groundwater storage trend in headwater basins in different Brazilian regions - Victoria S. Wojahn; Tamara L. C. Beskow; Carlos R. Mello; Samuel Beskow (Sustainable Water Resources Management, 2024)

Molecular basis of hyper-thermostability in the thermophilic archaeal aldolase MfnB - Rosie M. A. Maddock; Carl O. Marsh; Samuel T. Johns; Lynden D. Rooms; Phillip W. Duke; Marc W. van der Kamp; James E. M. Stach; Paul R. Race (Extremophiles, 2024)
Methanogenic archaea are chemolithotrophic prokaryotes that can reduce carbon dioxide with hydrogen gas to form methane. These microorganisms make a significant contribution to the global carbon cycle, with methanogenic archaea from anoxic environments estimated to contribute > 500 million tons of global methane annually. Archaeal methanogenesis is dependent on the methanofurans; aminomethylfuran containing coenzymes that act as the primary C 1 acceptor molecule during carbon dioxide fixation. Although the biosynthetic pathway to the methanofurans has been elucidated, structural adaptations which confer thermotolerance to Mfn enzymes from extremophilic archaea are yet to be investigated. Here we focus on the methanofuran biosynthetic enzyme MfnB, which catalyses the condensation of two molecules of glyceralde-3-phosphate to form 4‑(hydroxymethyl)-2-furancarboxaldehyde-phosphate. In this study, MfnB enzymes from the hyperthermophile Methanocaldococcus jannaschii and the mesophile Methanococcus maripaludis have been recombinantly overexpressed and purified to homogeneity. Thermal unfolding studies, together with steady-state kinetic assays, demonstrate thermoadaptation in the M. jannaschii enzyme. Molecular dynamics simulations have been used to provide a structural explanation for the observed properties. These reveal a greater number of side chain interactions in the M. jannaschii enzyme, which may confer protection from heating effects by enforcing spatial residue constraints.

Effects of fruit novelty on feeding preference in four globally invasive frugivorous birds - Samuel B. Case; Kapua Kawelo; Josephine Hoh; Dylan O’hearn; Jinelle H. Sperry; Jeffrey T. Foster; Donald R. Drake; Jeferson Vizentin-Bugoni; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2024)

Macrofaunal Biodiversity and Patch Mosaics on the Deep Gulf of Mexico Seafloor - Craig R. McClain; Granger Hanks; Samuel Copley; S. River D. Bryant; Brian A. Schubert (Marine Ecology, 2024)
The deep‐sea benthos often exhibit exceptional biodiversity. The patch‐mosaic hypothesis proposes that this deep‐sea diversity arises from varied microhabitats with prolonged temporal persistence filtering for distinctive communities thereby increasing beta‐diversity. This study investigated environmental, community, and macrofaunal species turnover at four deep‐sea sites (~2000 m) in the northern Gulf of Mexico. Using precise small‐scale sampling with a ROV, we analyzed patterns across spatial scales from centimeters to approximately 400 km among 67 sediment cores. We examined the relationships between sedimentary carbon, sediment grain size, and macrofaunal alpha‐ and beta‐diversity. Subsequently, we explored the role of these environmental properties and their spatial arrangement in shaping communities and species distributions. We observed a consistent trend where the overall abundance and diversity of a community increased with higher carbon but decreased with increasing grain size. Substantial faunal turnover was observed among cores, even at centimeter scales, with the contribution of centimeter‐scale spatial distance rivaling that of 100‐km scales in faunal dissimilarity. Similar to alpha‐diversity, beta‐diversity exhibited strong correlations with sediment carbon and grain size. The observed random spatial structure in grain size and carbon appear to translate into randomness in both community and species distribution. These findings align with the patch‐mosaic model, underscoring the complexity of deep‐sea ecosystems. These findings suggest an intricate relationship between sedimentary attributes, faunal composition, and spatial arrangement in the deep‐sea benthos, shedding light on the mechanisms driving biodiversity in seemingly homogeneous environments.

Predicting population‐level impacts of projected climate heating on a temperate freshwater fish - Kate S. Mintram; A. Ross Brown; Samuel K. Maynard; Pernille Thorbek; Charles R. Tyler (Journal of Fish Biology, 2024)
Climate heating has the potential to drive changes in ecosystems at multiple levels of biological organization. Temperature directly affects the inherent physiology of plants and animals, resulting in changes in rates of photosynthesis and respiration, and trophic interactions. Predicting temperature‐dependent changes in physiological and trophic processes, however, is challenging because environmental conditions and ecosystem structure vary across biogeographical regions of the globe. To realistically predict the effects of projected climate heating on wildlife populations, mechanistic tools are required to incorporate the inherent physiological effects of temperature changes, as well as the associated effects on food availability within and across comparable ecosystems. Here we applied an agent‐based bioenergetics model to explore the combined effects of projected temperature increases for 2100 (1.4, 2.7, and 4.4°C), and associated changes in prey availability, on three‐spined stickleback ( Gasterosteus aculeatus ) populations representing latitudes 50, 55, and 60°N. Our results showed a decline in population density after a simulated 1.4°C temperature increase at 50°N. In all other modeled scenarios there was an increase (inflation) in population density and biomass (per unit area) with climate heating, and this inflation increased with increasing latitude. We conclude that agent‐based bioenergetics models are valuable tools in discerning the impacts of climate change on wild fish populations, which play important roles in aquatic food webs.

A strategy for quantifying microplastic particles in membrane filtration processes using flow cytometry - Ryan J. LaRue; Samuel Koo; Ashleigh Warren; Yves G. McKay; David R. Latulippe (Chemosphere, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Demographic History and Adaptive Evolution of Indo‐Pacific Bottlenose Dolphins ( Tursiops aduncus ) in Western Australia - Svenja M. Marfurt; Delphine B. H. Chabanne; Samuel Wittwer; Manuela R. Bizzozzero; Simon J. Allen; Livia Gerber; Krista Nicholson; Michael Krützen (Molecular Ecology, 2024)
Demographic processes can substantially affect a species' response to changing ecological conditions, necessitating the combined consideration of genetic responses to environmental variables and neutral genetic variation. Using a seascape genomics approach combined with population demographic modelling, we explored the interplay of demographic and environmental factors that shaped the current population structure in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) along the Western Australian coastline. We combined large‐scale environmental data gathered via remote sensing with RADseq genomic data from 133 individuals at 19 sampling sites. Using population genetic and outlier detection analyses, we identified three distinct genetic clusters, coinciding with tropical, subtropical and temperate provincial bioregions. In contrast to previous studies, our demographic models indicated that populations occupying the paleo‐shoreline split into two demographically independent lineages before the last glacial maximum (LGM). A subsequent split after the LGM 12—15 kya gave rise to the Shark Bay population, thereby creating the three currently observed clusters. Although multi‐locus heterozygosity declined from north to south, dolphins from the southernmost cluster inhabiting temperate waters had higher heterozygosity in potentially adaptive loci compared to dolphins from subtropical and tropical waters. These findings suggest ongoing adaptation to cold‐temperate waters in the southernmost cluster, possibly linked to distinct selective pressures between the different bioregions. Our study demonstrated that in the marine realm, without apparent physical boundaries, only a combined approach can fully elucidate the intricate environmental and genetic interactions shaping the evolutionary trajectory of marine mammals.

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

Reconciling Pollen Limitation Theories: Insights From Temperate Oak Masting - Emilie Fleurot; Léa Keurinck; Vincent Boulanger; François Debias; Nicolas Delpierre; Sylvain Delzon; Jean R. Lobry; Camille Mermet‐Bouvier; Marie‐Claude Bel‐Venner; Samuel Venner (Ecology Letters, 2024)
Pollen limitation has a considerable influence on forest masting, the highly variable and synchronised seed production, on which forest regeneration and ecosystem dynamics largely rely. Depending on the various mechanisms possibly involved in pollen limitation, the consequences of climate change on masting could be very different. These mechanisms were investigated in 10 oak populations along a climatic gradient using surveys of airborne pollen and fruiting rate as a proxy of pollen limitation. We found no support for the widely accepted hypothesis of the intra‐annual synchrony of flower phenology when considered in isolation. Instead, the fruiting rate was largely explained by a combination of intra‐annual flower phenology synchrony, annual investment in flowering and the effects of weather on pollen maturation and diffusion. These findings highlight the need for a cohesive theoretical framework for pollen limitation to accurately predict the impact of climate change on oak‐dominated ecosystems.

Nitrogen isotope variability of macroalgae from a small fishing village, Staithes Harbour, Yorkshire, UK - Freya C. Alldred; Darren R. Gröcke; Samuel E. Jackson (Marine Pollution Bulletin, 2024)

A comprehensive molecular phylogeny of the terrestrial Parasitengona (Acariformes, Prostigmata) provides insights into the evolution of their metamorphosis, invasion into aquatic habitats and classification - Samuel G.S. Costa; Andrei Tolstikov; Alireza Saboori; Dante Batista-Ribeiro; Javad Noei; Mark S. Harvey; Matthew D. Shaw; Pavel B. Klimov; Zhi-Qiang Zhang; Almir R. Pepato (Molecular Phylogenetics and Evolution, 2024)

Validation of aerosol chemical composition and optical properties provided by Copernicus Atmosphere Monitoring Service (CAMS) using ground-based global data - Ana Carolina Amarillo; Gabriele Curci; Davide De Santis; Cristiana Bassani; Francesca Barnaba; Samuel Rémy; Luca Di Liberto; Christopher R. Oxford; Eli Windwer; Fabio Del Frate (Atmospheric Environment, 2024)

Host diet drives gut microbiome convergence between coral reef fishes and mammals - Samuel Degregori; Nina M. D. Schiettekatte; Jordan M. Casey; Simon J. Brandl; Alexandre Mercière; Katherine R. Amato; Florent Mazel; Valeriano Parravicini; Paul H. Barber (Molecular Ecology, 2024)
Animal gut microbiomes are critical to host physiology and fitness. The gut microbiomes of fishes—the most abundant and diverse vertebrate clade—have received little attention relative to other clades. Coral reef fishes, in particular, make up a wide range of evolutionary histories and feeding ecologies that are likely associated with gut microbiome diversity. The repeated evolution of herbivory in fishes and mammals also allows us to examine microbiome similarity in relationship to diet across the entire vertebrate tree of life. Here, we generate a large coral reef fish gut microbiome dataset ( n = 499 samples, 19 species) and combine it with a diverse aggregation of public microbiome data ( n = 447) to show that host diet drives significant convergence between coral reef fish and mammalian gut microbiomes. We demonstrate that this similarity is largely driven by carnivory and herbivory and that herbivorous and carnivorous hosts exhibit distinct microbial compositions across fish and mammals. We also show that fish and mammal gut microbiomes share prominent microbial taxa, including Ruminoccocus spp. and Akkermansia spp., and predicted metabolic pathways. Despite the major evolutionary and ecological differences between fishes and mammals, our results reveal that their gut microbiomes undergo similar dietary selective pressures. Thus, diet, in addition to phylosymbiosis must be considered even when comparing the gut microbiomes of distantly related hosts.

Enhanced perfluorooctanoic acid (PFOA) degradation by electrochemical activation of peroxydisulfate (PDS) during electrooxidation for water treatment - Melvin S. Samuel; Govindan Kadarkarai; Donald R. Ryan; Sean T. McBeath; Brooke K. Mayer; Patrick J. McNamara (Science of The Total Environment, 2024)

Effects of organic selenium-containing diets on Penaeus vannamei molecular response under induced heat stress challenge - Medhat R. Elfadadny; Samuel M. Mwamburi; Hidehiro Kondo; Ikuo Hirono (Fisheries Science, 2024)

Recent Development in Nanoparticle-Assisted Microbial Fuel Cell for Enhanced Reduction of Chromium - G. Vijay Samuel; Nibedita Dey; R. Govindarajan; Kuppusamy Sathishkumar; Muthusamy Govarthanan; J. Sakthidasan; J. Sandhya; Lakshmi Sundeep (Current Microbiology, 2024)

Senolytic intervention improves cognition, metabolism, and adiposity in female APPNL−F/NL−F mice - Yimin Fang; Mackenzie R. Peck; Kathleen Quinn; Jenelle E. Chapman; David Medina; Samuel A. McFadden; Andrzej Bartke; Erin R. Hascup; Kevin N. Hascup (GeroScience, 2024)
Senescent cells accumulate throughout the body and brain contributing to unhealthy aging and Alzheimer’s disease (AD). The APP NL−F/NL−F amyloidogenic AD mouse model exhibits increased markers of senescent cells and the senescence-associated secretory phenotype (SASP) in visceral white adipose tissue and the hippocampus before plaque accumulation and cognitive decline. We hypothesized that senolytic intervention would alleviate cellular senescence thereby improving spatial memory in APP NL−F/NL−F mice. Thus, 4-month-old male and female APP NL−F/NL−F mice were treated monthly with vehicle, 5 mg/kg dasatinib + 50 mg/kg quercetin, or 100 mg/kg fisetin. Blood glucose levels, energy metabolism, spatial memory, amyloid burden, and senescent cell markers were assayed. Dasatinib + quercetin treatment in female APP NL−F/NL−F mice increased oxygen consumption and energy expenditure resulting in decreased body mass. White adipose tissue mass was decreased along with senescence markers, SASP, blood glucose, and plasma insulin and triglycerides. Hippocampal senescence markers and SASP were reduced along with soluble and insoluble amyloid-β (Aβ) 42 and senescence-associated-β-gal activity leading to improved spatial memory. Fisetin had negligible effects on these measures in female APP NL−F/NL−F mice while neither senolytic intervention altered these parameters in the male mice. Considering women have a greater risk of dementia, identifying senotherapeutics appropriate for sex and disease stage is necessary for personalized medicine. Graphical Abstract

Evaluation of the EMA log kow trigger for fish BCF testing based on data for several human pharmaceuticals - Lisa A. Constantine; Natalie Burden; Todd Davidson; David G. Dolan; Gemma Janer; Andreas Häner; Michael R. Lee; Samuel K. Maynard; Erick Nfon; Alison Nimrod Perkins; James J. Ryan; Joan Tell (Regulatory Toxicology and Pharmacology, 2024)

The SPICE Project: Calibrated production rates of cosmogenic 3He and 21Ne in olivine and pyroxene from the 72 ka SP basalt flow, Arizona, USA - Cassandra R. Fenton; Samuel Niedermann; Tibor Dunai (Quaternary Geochronology, 2024)

Why aren't more landowners enrolling in land-based carbon credit exchanges? - Landon R. Schofield; Micayla E. Pearson; Samuel Newell; Nathan Clackum; Benjamin L. Turner (Rangelands, 2024)

Bottom-up formulations for the multi-criteria decision analysis of oil and gas pipeline decommissioning in the North Sea: Brent field case study - Shahin Jalili; Georgios Leontidis; Samuel R. Cauvin; Kate Gormley; Malcolm Stone; Richard Neilson (Journal of Environmental Management, 2024)

Spatial and temporal variability of martian water-ice cloud effective radius in EMIRS thermal infrared observations - Samuel A. Atwood; Michael D. Smith; Michael J. Wolff; Khalid Badri; Christopher S. Edwards; Philip R. Christensen; Alain S.J. Khayat; M.R. El-Maarry (Icarus, 2024)

Snow leopards exhibit non-stationarity in scale-dependent habitat selection between two national protected areas in China - Guoliang Pan; Ho Yi Wan; David R. Nash; Kun Shi; Samuel Cushman (Ecological Modelling, 2024)

Assessment of beach morphological characteristics and conservation strategies for blue flag beaches on the West Coast of India - J. Selvin Pitchaikani; Subbareddy Bonthu; R. Muruganandam; C. Viswanathan; K. K. Manodheepan; V. Deepak Samuel; Purvaja Ramachandran; R. Ramesh (Journal of Coastal Conservation, 2024)

Soft Drinks as a Dietary Source of Fluoride Exposure - Samuel Alejandro-Vega; Arturo Hardisson; Carmen Rubio; Ángel J. Gutiérrez; Juan R. Jaudenes-Marrero; Soraya Paz-Montelongo (Biological Trace Element Research, 2024)
High fluoride exposures can lead to adverse effects such as dental and bone fluorosis, as well as endocrine and cognitive developmental problems. Water is the main dietary source of this ion, although significant concentrations have also been detected in other beverages widely consumed by the population such as soft drinks. A total of 200 soft drink samples (60 flavoured, 70 extracts, 60 fruit juice and 10 soft drinks) were analysed by fluoride ion selective potentiometry. A consumption of 330 mL was estimated for exposure assessment and subsequent F-risk assessment by soft drink consumption. The highest average concentration was found in extract soft drinks (2.45 ± 1.15 mg/L), followed by flavoured (1.71 ± 2.29 mg/L) and carbonated soft drinks (1.38 ± 0.40 mg/L), while the lowest was found in fruit juice soft drinks (1.09 ± 0.62 mg/L). The flavours with the highest concentration were tea-melon and tea-passion fruit with 3.66 ± 0.40 and 3.17 ± 0.56 mg/L respectively and the lowest was lemon flavour with 0.69 mg/L. The contribution of these beverages, considering the UL (Upper level) reference values set by EFSA (European Food Safety Authority) are between 3.28–41.78%, depending on age group and sex.

Further investigation into the impact of manuring on stable carbon (δ13C) and nitrogen isotope (δ15N) values in pulses: a four-year experiment examining Celtic bean (Vicia faba) - Edward R. Treasure; Darren R. Gröcke; Jonathan J. Lester; Rosie R. Bishop; Samuel E. Jackson; Mike J. Church (Archaeological and Anthropological Sciences, 2024)
Plant stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values can be used to directly investigate crop husbandry practices such as manuring; a key variable in understanding the scale and intensity of past farming practices. We present new results from a four-year experiment examining the impact of manuring on the δ 13 C and δ 15 N values of a heritage cultivar of the broad or faba bean ( Vicia faba ), the ‘Celtic black broad bean’. This paper builds upon our previous pilot study (Treasure ER, Church MJ, Gröcke DR (2016) The influence of manuring on stable isotopes (δ 13 C and δ 15 N) in Celtic bean ( Vicia faba L.): archaeobotanical and palaeodietary implications. Archaeol Anthropol 8:555–562. https://doi.org/10.1007/s12520-015-0243-6 ). Our results indicate that manuring increased δ 15 N values in beans, with a mean value of 0.5 ± 0.4‰ in control samples compared to a mean value of 2.1 ± 1.3‰ in the most intensively manured plots. It was not always possible to distinguish between an unmanured and manured crop on the basis of δ 15 N values, although manured crops consistently exhibited larger variation in δ 15 N. Bean δ 13 C values show no clear relationship with manuring, although large variability (> 3‰) was found within crops cultivated under the same conditions. Manuring also increased plant biomass production, seed-size and the bean per plant ratio. Overall, we suggest that high δ 15 N values (> 1.5‰) in archaeobotanical remains of pulses can be attributed to small-scale, intensive cultivation that is typical of gardens where manuring rates are very intensive.

neonPlantEcology: An R package for preparing NEON plant data for use in ecological research - Adam L. Mahood; Ranjan Muthukrishnan; Jacob A. Macdonald; David T. Barnett; Eric R. Sokol; Samuel M. Simkin (Ecological Modelling, 2024)

Targeted and non-targeted mass spectrometry to explore the chemical diversity of the genus Gambierdiscus in the Atlantic Ocean - Thomas Yon; Damien Réveillon; Manoëlla Sibat; Chris Holland; R. Wayne Litaker; Silvia M. Nascimento; Araceli E. Rossignoli; Pilar Riobó; Philipp Hess; Samuel Bertrand (Phytochemistry, 2024)

Plant-level establishment can result from a single female Acanthococcus lagerstroemiae propagule - Erika R. Wright; Kevin D. Chase; Samuel F. Ward (Journal of Pest Science, 2024)
Crapemyrtle bark scale (CMBS), Acanthococcus lagerstroemiae (Kuwana) (Hemiptera: Eriococcidae), is a non-native scale insect that has spread throughout many urban areas of the Southeast and Middle Atlantic regions of the United States following its initial detection near Dallas, Texas in 2004, severely reducing the aesthetic value and health of the popular ornamental crapemyrtle tree ( Lagerstroemia spp.). We infested crapemyrtles with known numbers of CMBS to determine the minimum number of individuals required for establishment after initial arrival on plants. We also investigated how netting—implemented to understand differences in establishment when scale dispersal and predation are inhibited—influenced population growth. We determined that one female CMBS egg sac can successfully establish a new population ~ 92% of the time and that netting had negligible effects on establishment. Our results underscore the importance of surveying and managing CMBS and scale insects with similar biology when attempting to prevent infestation of nursery stock, which is widely implicated as a vector for long-distance dispersal of scale insects.

Bioturbation by Benthic Stingrays Alters the Biogeomorphology of Tidal Flats - Janne Nauta; Guido Leurs; Brian O. Nieuwenhuis; Donné R. A. H. Mathijssen; Han Olff; Tjeerd J. Bouma; Daphne van der Wal; Nadia Hijner; Aissa Regalla; Samuel Ledo Pontes; Laura L. Govers (Ecosystems, 2024)
Fishing-down-marine-food-webs has resulted in alarming declines of various species worldwide. Benthic rays are one examples of such overexploited species. On tidal flats, these rays are highly abundant and play an ecologically important role. They use tidal flats as refuge, feeding and resting grounds, during which they bury into the sediment, which results in sediment bioturbation. Changes in bioturbation intensity, following ray removal, may affect the biogeomorphology of tidal flats with possible cascading effects on the macrozoobenthic community. However, it is poorly understood how these indirect effects could influence ecosystem function. We therefore studied the geomorphic impact of benthic rays (specifically the pearl whipray/stingray Fontitrygon margaritella ) on the tropical tidal flats of the Bijagós Archipelago, Guinea-Bissau, on a landscape scale. We investigated 1) bioturbation rates by rays using drone and ground surveys, 2) the spatial distribution of ray pits on multiple tidal flats, 3) the impact of rays on sediment properties and macrozoobenthos by experimental exclusion (15 months). Benthic rays bioturbated 3.7 ± 0.35% of the tidal flat’s sediment surface per day over one single 24-h period, which equals a complete top-sediment-surface turnover every 27 days. The spatial distribution of ray pits was affected by tidal flat geomorphology since pits decayed faster at areas exposed to strong hydrodynamic forces. Predator exclusion altered sediment properties, leading to changes in sedimentation (− 17%) and erosion (− 43%) rates. In addition, macrozoobenthic species composition changed, marked by an increase in Capitellidae worms and a greater biomass of Malacostraca over time. These changes indicated substantial effects of ray bioturbation on the biotic and geomorphic landscape of tidal flats. Overall, we conclude that changing abundances of benthic rays can have clear landscape-wide geomorphological effects on intertidal ecosystems. These indirect consequences of fisheries should be incorporated in integrative management plans to preserve tidal flats and connected ecosystems.

Studying interactions among anthropogenic stressors in freshwater ecosystems: A systematic review of 2396 multiple‐stressor experiments - James A. Orr; Samuel J. Macaulay; Adriana Mordente; Benjamin Burgess; Dania Albini; Julia G. Hunn; Katherin Restrepo‐Sulez; Ramesh Wilson; Anne Schechner; Aoife M. Robertson; Bethany Lee; Blake R. Stuparyk; et al. (Ecology Letters, 2024)
Understanding the interactions among anthropogenic stressors is critical for effective conservation and management of ecosystems. Freshwater scientists have invested considerable resources in conducting factorial experiments to disentangle stressor interactions by testing their individual and combined effects. However, the diversity of stressors and systems studied has hindered previous syntheses of this body of research. To overcome this challenge, we used a novel machine learning framework to identify relevant studies from over 235,000 publications. Our synthesis resulted in a new dataset of 2396 multiple‐stressor experiments in freshwater systems. By summarizing the methods used in these studies, quantifying trends in the popularity of the investigated stressors, and performing co‐occurrence analysis, we produce the most comprehensive overview of this diverse field of research to date. We provide both a taxonomy grouping the 909 investigated stressors into 31 classes and an open‐source and interactive version of the dataset ( https://jamesaorr.shinyapps.io/freshwater‐multiple‐stressors/ ). Inspired by our results, we provide a framework to help clarify whether statistical interactions detected by factorial experiments align with stressor interactions of interest, and we outline general guidelines for the design of multiple‐stressor experiments relevant to any system. We conclude by highlighting the research directions required to better understand freshwater ecosystems facing multiple stressors.

A century of statistical Ecology - Neil A. Gilbert; Bruna R. Amaral; Olivia M. Smith; Peter J. Williams; Sydney Ceyzyk; Samuel Ayebare; Kayla L. Davis; Wendy Leuenberger; Jeffrey W. Doser; Elise F. Zipkin (Ecology, 2024)
As data and computing power have surged in recent decades, statistical modeling has become an important tool for understanding ecological patterns and processes. Statistical modeling in ecology faces two major challenges. First, ecological data may not conform to traditional methods, and second, professional ecologists often do not receive extensive statistical training. In response to these challenges, the journal Ecology has published many innovative statistical ecology papers that introduced novel modeling methods and provided accessible guides to statistical best practices. In this paper, we reflect on Ecology 's history and its role in the emergence of the subdiscipline of statistical ecology, which we define as the study of ecological systems using mathematical equations, probability, and empirical data. We showcase 36 influential statistical ecology papers that have been published in Ecology over the last century and, in so doing, comment on the evolution of the field. As data and computing power continue to increase, we anticipate continued growth in statistical ecology to tackle complex analyses and an expanding role for Ecology to publish innovative and influential papers, advancing the discipline and guiding practicing ecologists.

Can nutritional programming in Atlantic salmon (Salmo salar) be optimised with a reduced stimulus period? - Stuart McMillan; Samuel A.M. Martin; Elżbieta Król; Fernando Norambuena; Simon Baumgärtner; Xu Gong; Marwa Mamdouh Tawfik; Brett Glencross; John F. Taylor; Douglas R. Tocher; Mónica B. Betancor (Aquaculture, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Investigating speleothem magnetism as a proxy for dust mobilization and rainfall - Kimberly Hess; Roger R. Fu; Samuel Piascik; Nicolas M. Stríkis; Ricardo I.F. Trindade; Tyler Kukla; Alec R. Brenner; Plinio Jaqueto; Michail I. Petaev; Francisco W. Cruz; Placido Fabricio Silva Melo Buarque; Carlos Pérez-Mejías; et al. (Quaternary Science Reviews, 2024)

Antimicrobial cetylpyridinium chloride causes functional inhibition of mitochondria as potently as canonical mitotoxicants, nanostructural disruption of mitochondria, and mitochondrial Ca2+ efflux in living rodent and primary human cells - Sasha R. Weller; John E. Burnell; Brandon M. Aho; Bright Obeng; Emily L. Ledue; Juyoung K. Shim; Samuel T. Hess; Julie A. Gosse (Food and Chemical Toxicology, 2024)

The telomere-to-telomere, gapless, phased diploid genome and methylome of the green alga Scenedesmus obliquus UTEX 3031 reveals significant heterozygosity and genetic divergence of the haplotypes - Thomas C. Biondi; Colin P.S. Kruse; Samuel I. Koehler; Taehyung Kwon; Aubrey K. Davis; Wyatt Eng; Yuliya Kunde; Cheryl D. Gleasner; Kayley T. You Mak; Juergen Polle; Blake T. Hovde; Erik R. Hanschen; et al. (Algal Research, 2024)

Harassment and killing of porpoises (“phocoenacide”) by fish‐eating Southern Resident killer whales ( Orcinus orca ) - Deborah A. Giles; Sarah J. Teman; Samuel Ellis; John K. B. Ford; Monika W. Shields; M. Bradley Hanson; Candice K. Emmons; Paul E. Cottrell; Robin W. Baird; Richard W. Osborne; Michael Weiss; David K. Ellifrit; et al. (Marine Mammal Science, 2024)
Endangered Southern Resident killer whales ( Orcinus orca ) are fish‐eaters that preferentially prey on adult Chinook salmon ( Oncorhynchus tshawytscha ). Despite being salmon specialists, individuals from all three killer whale pods (J, K, L) have been observed harassing and killing porpoises (family Phocoenidae) without consuming them. Retrospectively, we identified and analyzed 78 episodes of Southern Resident killer whales harassing porpoises between 1962 and 2020, of which 28 resulted in the porpoise's death (“phocoenacide”). Fifty‐six episodes involved harbor porpoise ( Phocoena phocoena ), 13 involved Dall's porpoise ( Phocoenoides dalli ), and the porpoise species was unreported for nine episodes. Southern Resident killer whales often targeted young porpoises that were similar in size to adult Chinook salmon. Both sexes participated in porpoise harassment. Juveniles engaged in the behavior the most; however, their rates of engagement were not found to differ significantly from most other age classes. The behavior was passed through generations and social groupings, as it was first observed in L pod and spread to the other two pods. Killer whales are highly complex animals known to exhibit social learning and cultural transmission of learned behaviors, but the reason(s) for this behavior is unknown. Hypotheses include the social and developmental benefits of play, hunting practice, or displaced epimeletic behavior.

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Production of Escovopsis conidia and the potential use of this parasitic fungus as a biological control agent of leaf-cutting ant fungus gardens - Raymyson R. S. Queiroz; Thais B. P. Teodoro; Aline T. Carolino; Ricardo O. B. Bitencourt; Willians G. Souza; Marcela S. B. Boechat; Roberto R. Sobrinho; Gerson A. Silva; Richard I. Samuels (Archives of Microbiology, 2024)

Revising economic injury levels for Lygus spp. in canola: The value of historical yield and insect data to improve decision making - Héctor Cárcamo; Carolyn Herle; Timothy Schwinghamer; Samuel Robinson; Patty Reid; R. Keith Gabert; Tyler Wist; Breanne Tidemann; Alejandro C. Costamagna (Crop Protection, 2024)

Differential content of leaf and fruit pigment in tomatoes culminate in a complex metabolic reprogramming without growth impacts - Auderlan M. Pereira; Auxiliadora O. Martins; William Batista-Silva; Jorge A. Condori-Apfata; Victor F. Silva; Leonardo A. Oliveira; Eduarda Santos Andrade; Samuel C.V. Martins; David B. Medeiros; Vitor L. Nascimento; Alisdair R. Fernie; Adriano Nunes-Nesi; et al. (Journal of Plant Physiology, 2024)

Yersinia enterocolitica biovar 1A: An underappreciated potential pathogen in the food chain - Raphaёlle Palau; Samuel J. Bloomfield; Claire Jenkins; David R. Greig; Frieda Jorgensen; Alison E. Mather (International Journal of Food Microbiology, 2024)

Strategies for optimizing biovivianite production using dissimilatory Fe(III)-reducing bacteria. - Lordina E. Eshun; Victoria S. Coker; Samuel Shaw; Jonathan R. Lloyd (Environmental Research, 2024)

Microplastics in oral healthcare products (OHPs) and their environmental health risks and mitigation measures - G.B Protyusha; Kavitha B; R.S Robin; Nithin A; T.R Ineyathendral; S. Shruthi Shivani; Anandavelu I; Shyam Sivasamy; V. Deepak Samuel; Purvaja R (Environmental Pollution, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Stem wound healing is dependent upon bark and trunk growth rates in Brazilian savanna - William A. Hoffmann; Samuel W. Flake; Davi R. Rossatto; Ariadne C. De Antonio; Giselda Durigan; Rodolfo C. R. Abreu (Trees, 2024)

Paint Speckle Application Recommendations for Digital Image Correlation Analysis of Brazilian Tensile Strength Tests on Low-Porosity Rocks - Samuel K. Woodland; Émelie Gagnon; Timothy R. M. Packulak; Agatha Dobosz; Jennifer J. Day (Rock Mechanics and Rock Engineering, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

A framework to support the identification of critical habitat for wide-ranging species at risk under climate change - Lionel Leston; Francisco V. Dénes; Teegan D. S. Docherty; Junior A. Tremblay; Yan Boulanger; Steven L. Van Wilgenburg; Diana Stralberg; Peter Sólymos; Samuel Haché; Kathy St. Laurent; Russ Weeber; Bruno Drolet; et al. (Biodiversity and Conservation, 2024)
To recover species at risk, it is necessary to identify habitat critical to their recovery. Challenges for species with large ranges (thousands of square kilometres) include delineating management unit boundaries within which habitat use differs from other units, along with assessing any differences among units in amounts of and threats to habitat over time. We developed a reproducible framework to support identification of critical habitat for wide-ranging species at risk. The framework (i) reviews species distribution and life history; (ii) delineates management units across the range; (iii) evaluates and compares current and (iv) potential future habitat and population size and (v) prioritizes areas within management units based on current and future conditions under various scenarios of climate change and land-use. We used Canada Warbler ( Cardellina canadensis ) and Wood Thrush ( Hylocichla mustelina ) in Canada as case studies. Using geographically weighted regression models and cluster analysis to measure spatial variation in model coefficients, we found geographic differences in habitat association only for Canada Warbler. Using other models to predict current habitat amount for each species in different management units, then future habitat amount under land use and climate change, we projected that: (1) Canada Warbler populations would decrease in Alberta but increase in Nova Scotia and (2) Wood Thrush populations would increase under most scenarios run in Quebec, New Brunswick and Nova Scotia, but not in Ontario. By comparing results from future scenarios and spatial prioritization exercises, our framework supports identification of critical habitat in ways that incorporate climate and land-use projections.

Complete sequence and genome characterization of miscanthus virus M, a new betaflexivirus from Miscanthus sp. - Peter Abrahamian; Samuel Grinstead; Gary R. Kinard; Ricardo Goenaga; Philippe Rott; Dimitre Mollov (Archives of Virology, 2024)

Evidence of a small, island-associated population of common bottlenose dolphins in the Mariana Islands - Karen K. Martien; Marie C. Hill; Frederick I. Archer; Robin W. Baird; Andrea R. Bendlin; Louella Dolar; Allan D. Ligon; Erin M. Oleson; Kelly M. Robertson; Samuel M. Woodman; Adam C. Ü; Kymberly M. Yano; et al. (Frontiers in Marine Science, 2024)
Small, island-associated populations of cetaceans have evolved around numerous oceanic islands, likely due to habitat discontinuities between nearshore and offshore waters. However, little is known about the ecology and structure of cetacean populations around the Mariana Islands, a remote archipelago in the western Pacific Ocean. We present sighting, photo-identification, and genetic data collected during twelve years of surveys around these islands that reveal the existence of a small, island-associated population of bottlenose dolphins. Nearly half of the photo-identified individuals were encountered in more than one year. Both haplotypic and nuclear genetic diversity among sampled individuals was low (haplotypic diversity = 0.701, nuclear heterozygosity = 0.658), suggesting low abundance. We used mark-recapture analysis of photo-identification data to estimate yearly abundance in the southern portion of the population’s range from 2011 to 2018. Each abundance estimate was less than 54 individuals, with each upper 95% confidence interval below 100. Additional survey effort is necessary to generate a full population abundance estimate. We found extensive introgression of Fraser’s dolphin DNA into both the mitochondrial and nuclear genomes of the population, suggesting at least two hybridization events more than two generations in the past. The Mariana Islands are used extensively by the U.S. military for land and sea training operations. Thus, this unique bottlenose dolphin population likely faces high exposure to multiple threats.

Vertically distinct sources modulate stable isotope signatures and distribution of Mesozooplankton in central Patagonia: The Golfo de Penas - Baker Channel connection and analogies with the Beagle Channel - Leonardo R. Castro; Samuel Soto-Mendoza; Luciana Riccialdelli; María L. Presta; Pamela Barrientos; Humberto E. González; Giovanni Daneri; Marcelo Gutiérrez; Paulina Montero; Italo Masotti; Beatriz Díez (Journal of Marine Systems, 2024)

Differential gene expression and developmental pathologies associated with persistent organic pollutants in sentinel fish in Troutman Lake, Sivuqaq, Alaska - Renee Jordan-Ward; Frank A. von Hippel; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Elise Contreras; Alison Gardell; Michael R. Minicozzi; Tom Titus; Bobby Ungwiluk; Pamela Miller; David Carpenter; et al. (Environmental Pollution, 2024)

Meeting the costs of decarbonising industry – The potential effects on prices and competitiveness (a case study of the UK) - Samuel J.G. Cooper; Stephen R. Allen; Ahmed Gailani; Jonathan B. Norman; Anne Owen; John Barrett; Peter Taylor (Energy Policy, 2024)

Expectancy for Adderall influences subjective mood and drug effects regardless of concurrent caffeine ingestion: A randomized controlled trial - Alison Looby; Annalisa V. Piccorelli; Lauren Zimmerman; Caitlin Falco; Nicholas R. Livingston; Cody Akin; Samuel Benton; Laura M. Juliano (Psychopharmacology, 2024)

Divergent ecological responses to typhoon disturbance revealed via landscape‐scale acoustic monitoring - Samuel R. P.‐J. Ross; Nicholas R. Friedman; Kenneth L. Dudley; Takuma Yoshida; Masashi Yoshimura; Evan P. Economo; David W. Armitage; Ian Donohue (Global Change Biology, 2024)
Climate change is increasing the frequency, intensity, and duration of extreme weather events across the globe. Understanding the capacity for ecological communities to withstand and recover from such events is critical. Typhoons are extreme weather events that are expected to broadly homogenize ecological dynamics through structural damage to vegetation and longer‐term effects of salinization. Given their unpredictable nature, monitoring ecological responses to typhoons is challenging, particularly for mobile animals such as birds. Here, we report spatially variable ecological responses to typhoons across terrestrial landscapes. Using a high temporal resolution passive acoustic monitoring network across 24 sites on the subtropical island of Okinawa, Japan, we found that typhoons elicit divergent ecological responses among Okinawa's diverse terrestrial habitats, as indicated by increased spatial variability of biological sound production (biophony) and individual species detections. This suggests that soniferous communities are capable of a diversity of different responses to typhoons. That is, spatial insurance effects among local ecological communities provide resilience to typhoons at the landscape scale. Even though site‐level typhoon impacts on soundscapes and bird detections were not particularly strong, monitoring at scale with high temporal resolution across a broad spatial extent nevertheless enabled detection of spatial heterogeneity in typhoon responses. Further, species‐level responses mirrored those of acoustic indices, underscoring the utility of such indices for revealing insight into fundamental questions concerning disturbance and stability. Our findings demonstrate the significant potential of landscape‐scale acoustic sensor networks to capture the understudied ecological impacts of unpredictable extreme weather events.

A novel approach to environmental pollution management/remediation techniques using derived advanced materials - Rashmi Singh; Melvin S. Samuel; Madhumita Ravikumar; Selvarajan Ethiraj; V.S. Kirankumar; Mohanraj Kumar; R. Arulvel; Sagadevan Suresh (Chemosphere, 2023)

Assessment of benthic habitats of highly threatened oyster reefs of Pulicat Lake, India - Darwin Ramteke; K. Paramasivam; C. Viswanathan; K.R. Abhilash; J. Joyson Joe Jeevamani; V. Deepak Samuel; R. Sankar; R. Muruganandam; R. Purvaja; R. Ramesh (Regional Studies in Marine Science, 2023)

Fungal diversity in homes and asthma morbidity among school-age children in New York City - Samuel J. Cochran; Luis Acosta; Adnan Divjan; Angela R. Lemons; Andrew G. Rundle; Rachel L. Miller; Edward Sobek; Brett J. Green; Matthew S. Perzanowski; Karen C. Dannemiller (Environmental Research, 2023)

Functionalized magnetic graphene oxide composites for selective toxic metal adsorption - Jessica M.A. Freire; Ícaro O. Moreira; Antonia M. de M. França; Luiz T.V. da Silva; Luis P.M. dos Santos; Samuel Lucas Santos Medeiros; Igor F. de Vasconcelos; Adonay R. Loiola; Renato A. Antunes; Ronaldo F. do Nascimento; Elisane Longhinotti (Environmental Nanotechnology, Monitoring & Management, 2023)

Molecular camouflage by a context-specific hydrogel as the key to unlock the potential of viral vector gene therapy - Shiva Soltani Dehnavi; Arianna Cembran; Negar Mahmoudi; Lilith M Caballero Aguilar; Yi Wang; Samuel Cheeseman; Nicolo Malagutti; Stephanie Franks; Benjamin Long; Leszek Lisowski; Alan R Harvey; Clare L. Parish; et al. (Chemical Engineering Journal, 2023)

Small-scale fishing has affected abundance and size distributions of deepwater snappers and groupers in the MesoAmerican region - Ivy E. Baremore; Rachel T. Graham; Samuel R. D. Owen; Matthew J. Witt (Reviews in Fish Biology and Fisheries, 2023)
Deepwater fisheries in the Caribbean Sea are poorly studied and mostly unmanaged, despite their importance to local economies and food security. In the MesoAmerican region, deepwater fisheries are nearshore and easily accessible in many locations by small vessels, but historical and contemporary fishing effort varies by country. We used standardized fishery-independent methods, including vertical longlines and baited remote underwater video (BRUV) to assess the relative abundance and distribution of deepwater (100–550 m) snappers and groupers in Belize and Honduras. Fishery-dependent samples were used to supplement spatial distribution and body length data. Gathered data revealed that Belize, with a smaller fishing population and shorter history of deepwater fishing, had overall higher abundance of groupers and snappers and that fish were significantly larger than those in Honduras, which has a well-established and larger deepwater fishery. Water temperature was found to influence the abundance and occurrence of deepwater snappers more than depth. Deepwater snappers were widely-distributed throughout available habitat in both countries, but groupers were more patchy, and rarely encountered in the more heavily fished areas off Honduras. Our results suggest that a precautionary approach to fisheries management and targeted biological research of these stocks is required, which is particularly relevant for Belize, where climate change and overfishing mitigation measures are focused on an expansion of the deepwater fishery.

Impact of Leifsonia xyli subsp. xyli titer on nutritional status, and metabolism of sugar cane - Fernando Henrique Silva Garcia; Adilson Pereira Domingues-Júnior; Marina Lima Nogueira; Samuel de Paula; Jacson Ferreira; José Lavres; Samuel J. Martins; Alisdair R. Fernie; Ricardo Alfredo Kluge (Plant and Soil, 2023)

Energy reference guidance for drag-modulated aerocapture - Samuel W. Albert; Ethan R. Burnett; Hanspeter Schaub; P. Daniel Burkhart; Alex Austin (Advances in Space Research, 2023)

Mineralogy of explosive and effusive volcanic edifices in the Marius Hills Volcanic Complex - Marie J.B. Henderson; Briony H.N. Horgan; Samuel J. Lawrence; Julie D. Stopar; Lisa R. Gaddis (Icarus, 2023)

Soil erosion assessment in the Amazon basin in the last 60 years of deforestation - Nelva B. Riquetti; Samuel Beskow; Li Guo; Carlos R. Mello (Environmental Research, 2023)

Miocene cave sediments record topographic, erosional and drainage development in the Western European Alps - François Lemot; Pierre G. Valla; Peter van der Beek; Marianna Jagercikova; Samuel Niedermann; Julien Carcaillet; Edward R. Sobel; Sergio Andò; Eduardo Garzanti; Xavier Robert; Mélanie Balvay; Matthias Bernet; et al. (Earth and Planetary Science Letters, 2023)

Tidal gradients, fine‐scale homing and a potential cryptic ecotype of wild spawning pink salmon ( Oncorhynchus gorbuscha ) - Samuel A. May; Kyle R. Shedd; Peter S. Rand; Peter A. H. Westley (Molecular Ecology, 2023)
The homing behaviour of salmon is a remarkable natural phenomenon, critical for shaping the ecology and evolution of populations yet the spatial scale at which it occurs is poorly understood. This study investigated the spatial scale and mechanisms driving homing as depicted by spawning site‐choice behaviour in pink salmon ( Oncorhynchus gorbuscha ) in Prince William Sound, Alaska. Molecular pedigree analyses of over 30,000 adult spawners in four streams revealed that pink salmon exhibit fine‐scale site fidelity within a stream, returning to within

Involvement of phospholipase A2 in the neuromuscular blockade caused by coralsnake (Micrurus spp.) venoms in mouse phrenic nerve-diaphragm preparations in vitro - Fernanda Y.G.M. Couceiro; Poliana J. Demico; Samuel R. Dias; Isabele N. Oliveira; Francis L. Pacagnelli; Elisangela O. Silva; Sávio S. Sant’Anna; Kathleen F. Grego; Karen Morais-Zani; Kristian A. Torres-Bonilla; Stephen Hyslop; Rafael S. Floriano (Toxicon, 2023)

Detailed hydrocarbon speciation and particulate matter emissions during cold-start from turbocharged and naturally aspirated trucks - Melanie Moses-DeBusk; John M.E. Storey; Samuel A. Lewis Sr.; R. Maggie Connatser; Shannon M. Mahurin; Shean Huff; Cyril V. Thompson; Yensil Park (Fuel, 2023)

Plant fruit extracts enhance the in vitro propagation of cowpea (Vigna unguiculata) on Murashige and Skoog media - Grace Markin; John S. Y. Eleblu; Jacqueline N. Amissah; Samuel Reynolds; Charline Soraru; Melanie S. Craze; Emma J. Wallington; Alison R. Bentley; Eric Y. Danquah (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Cowpea ( Vigna unguiculata ) is a versatile legume with diverse nutritional and nutraceutical properties that serve as a food security and medicinal crop for millions of households across Africa. An efficient protocol was developed to propagate shoot tip and cotyledonary node explants from six cowpea breeding accessions in vitro on Murashige and Skoog (MS) basal media supplemented with either banana extract, coconut water, orange or tomato juice. Micropropagation performance was compared to MS medium supplemented with B5 vitamins. A total of 500 plantlets were obtained in vitro across treatments and MS basal media supplemented with tomato juice had the highest micropropagation performance (154 plantlets), followed by banana extract (112 plantlets), orange juice (107 plantlets), and coconut water (82 plantlets). Three accessions (AGRAC 216, TA, and Asontem) were found to be the most amenable to in vitro propagation using plant-derived extracts. Overall, this study successfully established that plant-derived extracts can support in vitro cowpea propagation in the absence of synthetic plant growth regulators.

Correction to: Island characteristics and species traits predict mammal diversity across islands of the great lakes of North America - Nathaniel H. Wehr; Hailey M. Boone; Samuel R. Wehr; Jerrold L. Belant (Biodiversity and Conservation, 2023)

The potential role of biofilms in promoting fouling formation in radioactive discharge pipelines - Franky Barton; Ben F. Spencer; Romain Tartèse; James Graham; Samuel Shaw; Katherine Morris; Jonathan R. Lloyd (Biofouling, 2023)

LP-57: Increasing Confidence in New Approach Methodologies for Inhalation Risk Assessment with Multiple End Point Assays Using 5-day RepeatExposure to 1,3-dichloropropene - I. Paudel; R. Barutcu; R. Samuel; M. Moreau; S. Slattery; J. Scaglione; L. Recio (Toxicology Letters, 2023)

Enzymatically hydrolyzed fluorescence-based chemical probe enables in situ mapping of chitinase activity in the rhizosphere - Elias K. Zegeye; Vivian S. Lin; Jamie R. Nuñez; Nick A. Sconzo; Samuel O. Purvine; Aaron T. Wright; James J. Moran (Soil Biology and Biochemistry, 2023)

Wet air oxidation of HTL aqueous waste - Uriah J. Kilgore; Senthil Subramaniam; Samuel P. Fox; Dylan J. Cronin; Mond F. Guo; Andrew J. Schmidt; Karthikeyan K. Ramasamy; Michael R. Thorson (Biomass and Bioenergy, 2023)

The age and potential causes of the giant Green Lake Landslide, Fiordland, New Zealand - Shaun R. Eaves; Samuel T. McColl; Levan G. Tielidze; Kevin P. Norton; Jenni L. Hopkins; Alan J. Hidy (Landslides, 2023)
Landslide deposits preserved in the geological record afford opportunities to better inform hillslope and seismic hazard and risk models, particularly in regions where observational records are short. In the Southern Alps of New Zealand, small coseismic landslides are frequent, but the geological record preserves several instances of more substantial (> 1 km 3 ) but infrequent mass failures. With an estimated volume of 27 km 3 , the giant Green Lake Landslide represents one of the largest subaerial landslides on Earth. Previous work has suggested this deep-seated mass movement was most likely triggered by high-intensity seismic shaking, but that local structural weakness and/or glacial debuttressing may help to explain the anomalously large failure volume. Resolving the potential contribution of the latter is important given predictions concerning alpine deglaciation in the coming decades to centuries. Key to resolution are secure chronologies of landslide emplacement and past glacier change. Here we present in situ cosmogenic 10 Be exposure ages from the Green Lake Landslide that suggest an emplacement age of 15.5 ± 0.7 ka. Recent work shows that glacial retreat in the region was underway by 19 ka, indicating that the Green Lake Landslide was emplaced 3–4 kyr after the onset of glacier retreat. Given the geometry of the former confining valley glacier, we expect that the deglaciation-landslide age gap is closer to the upper end of this estimate. If correct, this conclusion places greater weight on the roles of local geological structure and/or a great earthquake as factors contributing to the exceptionally large volume of this event.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Human‐induced salinity changes impact marine organisms and ecosystems - Till Röthig; Stacey M. Trevathan‐Tackett; Christian R. Voolstra; Cliff Ross; Samuel Chaffron; Paul J. Durack; Laura M. Warmuth; Michael Sweet (Global Change Biology, 2023)
Climate change is fundamentally altering marine and coastal ecosystems on a global scale. While the effects of ocean warming and acidification on ecology and ecosystem functions and services are being comprehensively researched, less attention is directed toward understanding the impacts of human‐driven ocean salinity changes. The global water cycle operates through water fluxes expressed as precipitation, evaporation, and freshwater runoff from land. Changes to these in turn modulate ocean salinity and shape the marine and coastal environment by affecting ocean currents, stratification, oxygen saturation, and sea level rise. Besides the direct impact on ocean physical processes, salinity changes impact ocean biological functions with the ecophysiological consequences are being poorly understood. This is surprising as salinity changes may impact diversity, ecosystem and habitat structure loss, and community shifts including trophic cascades. Climate model future projections (of end of the century salinity changes) indicate magnitudes that lead to modification of open ocean plankton community structure and habitat suitability of coral reef communities. Such salinity changes are also capable of affecting the diversity and metabolic capacity of coastal microorganisms and impairing the photosynthetic capacity of (coastal and open ocean) phytoplankton, macroalgae, and seagrass, with downstream ramifications on global biogeochemical cycling. The scarcity of comprehensive salinity data in dynamic coastal regions warrants additional attention. Such datasets are crucial to quantify salinity‐based ecosystem function relationships and project such changes that ultimately link into carbon sequestration and freshwater as well as food availability to human populations around the globe. It is critical to integrate vigorous high‐quality salinity data with interacting key environmental parameters (e.g., temperature, nutrients, oxygen) for a comprehensive understanding of anthropogenically induced marine changes and its impact on human health and the global economy.

Contrasting effects of biochar application rate in an alkaline desert cropland soil - Shelby R. Hoglund; Samuel J. Rathke; Rivka B. Fidel; Joseph C. Blankinship (Journal of Arid Environments, 2023)

Common fear molecules induce defensive responses in marine prey across trophic levels - Sarah H. Roney; Marisa R. Cepeda; Benjamin A. Belgrad; Samuel G. Moore; Delbert L. Smee; Julia Kubanek; Marc J. Weissburg (Oecologia, 2023)

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Correction to: Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)

Island characteristics and species traits predict mammal diversity across islands of the great lakes of North America - Nathaniel H. Wehr; Hailey M. Boone; Samuel R. Wehr; Jerrold L. Belant (Biodiversity and Conservation, 2023)

Analysing the distribution of strictly protected areas toward the EU2030 target - Roberto Cazzolla Gatti; Piero Zannini; Gianluca Piovesan; Nicola Alessi; Alberto Basset; Carl Beierkuhnlein; Michele Di Musciano; Richard Field; John M. Halley; Samuel Hoffmann; Jacopo Iaria; Athanasios Kallimanis; et al. (Biodiversity and Conservation, 2023)
Protecting global biodiversity is one of the most urgent tasks for the coming decades. Area-based conservation is a pillar for preserving ecosystems and species. Strictly protected areas specifically preserve biodiversity and ecosystem processes. The “EU Biodiversity Strategy for 2030” targets strict protection for 10% of land area. Here we performed the first analysis of strictly protected areas (as IUCN type Ia, Ib, and II) across Europe, by investigating their area coverage at the level of biogeographical regions, countries and elevation gradients. We show that, with few exceptions, the amount of strictly protected area is very limited and the spatial distribution of such protected areas is biased towards higher elevation sites, as in the case of other protected areas. Then, we suggest that potential areas should be identified to expand strictly protected areas with low economic and social costs including, for instance, areas with high biodiversity value, low population, and low productive land use. Finally, we propose that a coordinated effort and a strategic plan to achieve continental-scale conservation are fundamental, and at least half of this land under strict conservation (i.e. 5%) should be under the protection categories Ia and Ib.

Natural gas odorants: A scoping review of health effects - Drew R. Michanowicz; Olivia M. Leventhal; Jeremy K. Domen; Samuel R. Williams; Eric D. Lebel; Lee Ann L. Hill; Jonathan J. Buonocore; Curtis L. Nordgaard; Aaron S. Bernstein; Seth B.C. Shonkoff (Current Environmental Health Reports, 2023)
Purpose of Review Organosulfur compounds are intentionally added to natural gas as malodorants with the intent of short-term nasal inhalation to aid in leak detection. Regulatory exposure limits have not been established for all commonly used natural gas odorants, and recent community-level exposure events and growing evidence of indoor natural gas leakage have raised concerns associated with natural gas odorant exposures. We conducted a scoping review of peer-reviewed scientific publications on human exposures and animal toxicological studies of natural gas odorants to assess toxicological profiles, exposure potential, health effects and regulatory guidelines associated with commonly used natural gas odorants. Recent Findings We identified only 22 studies which met inclusion criteria for full review. Overall, there is limited evidence of both transient nonspecific health symptoms and clinically diagnosed causative neurotoxic effects associated with prolonged odorant exposures. Across seven community-level exposure events and two occupational case reports, consistent symptom patterns included: headache, ocular irritation, nose and throat irritation, respiratory complaints such as shortness of breath and asthma attacks, and skin irritation and rash. Of these, respiratory inflammation and asthma exacerbations are the most debilitating, whereas the high prevalence of ocular and dermatologic symptoms suggest a non-inhalation route of exposure. Summary The limited evidence available raises the possibility that organosulfur odorants may pose health risks at exposures much lower than presently understood, though additional dose-response studies are needed to disentangle specific toxicologic effects from nonspecific responses to noxious organosulfur odors. Numerous recommendations are provided including more transparent and prescriptive natural gas odorant use practices.

No-till cover crop effects on the thermal properties of a Paleudult - Samuel I. Haruna; Zoey A. Ward; Ashlen L. Cartwright; Avie A. Wunner; Chelsea A. Jackson; Callie R. Berry (Soil and Tillage Research, 2023)

Characterization of canine intestinal microRNA expression in inflammatory bowel disease and T-cell lymphoma - Jennifer R. Irving; Thomas K. Hiron; Lucy J. Davison; Dong Xia; Samuel Beck; Dirk Werling; Jonathan Williams (Journal of Comparative Pathology, 2023)

Exploring options for increasing maize yields and grain Zn concentrations in sub-Saharan Africa - Mirjam S. Breure; Samuel Njoroge; Heather R. Pasley; Ellis Hoffland (Plant and Soil, 2023)
Background Increasing zinc (Zn) concentrations in maize grains could contribute to alleviating widespread human Zn deficiency in sub-Saharan Africa (SSA). However, trade-offs between grain Zn concentrations and maize yields have been observed. Scope Using data from researcher-managed, on-farm and on-station field trials in Kenya, Zambia and Zimbabwe, we aimed (i) to confirm whether this trade-off is found in current farming systems in SSA and (ii) to explore whether genotypic and management options, relevant for the African context, can increase both yields and grain Zn concentrations across several environments. Results An overall negative, but weak relation between maize yields and grain Zn concentrations was found. High yields and high grain Zn concentrations did not co-occur. The negative relation between grain Zn concentrations and yields cannot be bypassed by selecting one of the commercially available varieties used in this study. Nitrogen application increased yields, but had contrasting effects on grain Zn concentrations depending on variety and site. Grain Zn concentrations were positively related with soil organic carbon and P and K availability. Conclusions Attaining grain Zn concentrations above the HarvestPlus target of 38 mg kg −1 , considered adequate for reducing human Zn deficiency, with current commercially available maize varieties and presented management options, is not possible without compromising yield levels. Increasing soil organic matter content and balanced application of N, P and K fertilisers could increase grain Zn concentrations. These practices likely will also increase yields and could be a viable option to bypass the trade-off between maize yields and grain Zn concentrations.

Anthocyanins and reactive oxygen species: a team of rivals regulating plant development? - João Victor A. Cerqueira; Moab T. de Andrade; Diego D. Rafael; Feng Zhu; Samuel V. C. Martins; Adriano Nunes-Nesi; Vagner Benedito; Alisdair R. Fernie; Agustin Zsögön (Plant Molecular Biology, 2023)
Anthocyanins are a family of water-soluble vacuolar pigments present in almost all flowering plants. The chemistry, biosynthesis and functions of these flavonoids have been intensively studied, in part due to their benefit for human health. Given that they are efficient antioxidants, intense research has been devoted to studying their possible roles against damage caused by reactive oxygen species (ROS). However, the redox homeostasis established between antioxidants and ROS is important for plant growth and development. On the one hand, high levels of ROS can damage DNA, proteins, and lipids, on the other, they are also required for cell signaling, plant development and stress responses. Thus, a balance is needed in which antioxidants can remove excessive ROS, while not precluding ROS from triggering important cellular signaling cascades. In this article, we discuss how anthocyanins and ROS interact and how a deeper understanding of the balance between them could help improve plant productivity, nutritional value, and resistance to stress, while simultaneously maintaining proper cellular function and plant growth.

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

Sex-specific respiratory and systemic endocrine effects of acute acrolein and trichloroethylene inhalation - Devin I. Alewel; Thomas W. Jackson; Samuel A. Vance; Mette C. Schladweiler; Paul A. Evansky; Andres R. Henriquez; Rachel Grindstaff; Stephen H. Gavett; Urmila P. Kodavanti (Toxicology Letters, 2023)

Quantifying the impacts of predation by Great Black-backed Gulls Larus marinus on an Atlantic Puffin Fratercula arctica population: Implications for conservation management and impact assessments - Samuel Langlois Lopez; Francis Daunt; Jared Wilson; Nina J. O'Hanlon; Kate R. Searle; Sophie Bennett; Mark A. Newell; Michael P. Harris; Elizabeth Masden (Marine Environmental Research, 2023)

Brevetoxin induces a shift in the redox state of the proteome and unfolded protein response in human lymphoblast cells that can be alleviated with the acrolein scavenger MESNA - Jordan Jobson; Pawlos S. Tsegay; Mayra Tabares Beltran; Eman A. Taher; Samuel R. Rein; Yuan Liu; Kathleen S. Rein (Environmental Toxicology and Pharmacology, 2023)

Implementation During a Pandemic: Findings, Successes, and Lessons Learned from Community Grantees - Wilhelmenia Mathias; Karen A. Nichols; Jewel Golden-Wright; Ciaran M. Fairman; Tisha M. Felder; Lauren Workman; Karen E. Wickersham; Kimberly J. Flicker; Jingxi Sheng; Samuel B. Noblet; Swann Arp Adams; Jan M. Eberth; et al. (Journal of Cancer Education, 2023)

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

Linked disturbance in the temperate forest: Earthworms, deer, and canopy gaps - Samuel P. Reed; Dustin R. Bronson; Jodi A. Forrester; Leah M. Prudent; Anna M. Yang; Austin M. Yantes; Peter B. Reich; Lee E. Frelich (Ecology, 2023)
Despite the large body of theory concerning multiple disturbances, relatively few attempts have been made to test the theoretical assumptions of how and if disturbances interact. Of particular importance is whether disturbance events are linked, as this can influence the probability and intensity of ecological change. Disturbances are linked when one disturbance event increases or decreases the likelihood or extent of another. To this end, we used two long‐term, multi‐disturbance experiments in northern Wisconsin to determine whether earthworm invasion is linked to canopy gap creation and white‐tailed deer browsing. These three disturbances are common and influential within North American temperate forests, making any interactions among them particularly important to understand. We expected both deer and canopy gaps to favor invasive earthworms, particularly species that live close to or on the soil surface. However, we found only partial support of our hypotheses, as both deer exclosures and canopy gaps decreased earthworms in each experiment. Further, earthworm density increased the most over time in areas far from the gap center and in areas with deer present. Deer exclosures primarily decreased Aporrectodea and Lumbricus species, while gaps decreased Dendrobaena and Lumbricus species. Our findings show that earthworm invasion is linked to deer presence and gap‐creating disturbances, which provides new insight in multiple disturbance theory, aboveground–belowground dynamics, and temperate forest management.

Contrasting ecological information content in whaling archives with modern cetacean surveys for conservation planning and identification of historical distribution changes - Tom B. Letessier; Laura Mannocci; Brittney Goodwin; Clare Embling; Asha de Vos; R. Charles Anderson; Simon N. Ingram; Andy Rogan; Samuel T. Turvey (Conservation Biology, 2023)
Many species are restricted to a marginal or suboptimal fraction of their historical range due to anthropogenic impacts, making it hard to interpret their ecological preferences from modern‐day data alone. However, inferring past ecological states is limited by the availability of robust data and biases in historical archives, posing a challenge for policy makers . To highlight how historical records can be used to understand the ecological requirements of threatened species and inform conservation, we investigated sperm whale ( Physeter macrocephalus ) distribution in the Western Indian Ocean. We assessed differences in information content and habitat suitability predictions based on whale occurrence data from Yankee whaling logs (1792–1912) and from modern cetacean surveys (1995–2020). We built maximum entropy habitat suitability models containing static (bathymetry‐derived) variables to compare models comprising historical‐only and modern‐only data. Using both historical and modern habitat suitability predictions we assessed marine protected area (MPA) placement by contrasting suitability in‐ and outside MPAs. The historical model predicted high habitat suitability in shelf and coastal regions near continents and islands, whereas the modern model predicted a less coastal distribution with high habitat suitability more restricted to areas of steep topography. The proportion of high habitat suitability inside versus outside MPAs was higher when applying the historical predictions than the modern predictions, suggesting that different marine spatial planning optimums can be reached from either data sources. Moreover, differences in relative habitat suitability predictions between eras were consistent with the historical depletion of sperm whales from coastal regions, which were easily accessed and targeted by whalers, resulting in a modern distribution limited more to steep continental margins and remote oceanic ridges. The use of historical data can provide important new insights and, through cautious interpretation, inform conservation planning and policy, for example, by identifying refugee species and regions of anticipated population recovery.

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

TRPV1 inactivation alters core body temperature and serum corticosterone levels: Impacts on clock genes expression in the liver and adrenal glands - Nayara AC. Horta; Paola Fernandes; Thais SR. Cardoso; Frederico SM. Machado; Lucas R. Drummond; Cândido C. Coimbra; Samuel P. Wanner; Ana Maria L Castrucci; Maristela O. Poletini (Journal of Thermal Biology, 2023)

Determinants of body core temperatures at fatigue in rats subjected to incremental-speed exercise: The prominent roles of ambient temperature, distance traveled, initial core temperature, and measurement site - Marcelo T. Andrade; Nicolas H. S. Barbosa; Roberto C. S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V. R. Andrade; Alexandre S. R. Hudson; Pedro H. Paula; et al. (International Journal of Biometeorology, 2023)

Shape from spectra - Nimrod Carmon; Alexander Berk; Niklas Bohn; Phillip G. Brodrick; Jeff Dozier; Margaret Johnson; Charles E. Miller; David R. Thompson; Michael Turmon; Charles M. Bachmann; Robert O. Green; Regina Eckert; et al. (Remote Sensing of Environment, 2023)

Demand reduction and energy saving potential of thermal energy storage integrated heat pumps - Jason Hirschey; Zhenning Li; Kyle R. Gluesenkamp; Tim J. LaClair; Samuel Graham (International Journal of Refrigeration, 2023)

An observing campaign to search for meteoroids of Bennu at Earth - Peter Jenniskens; Dante S. Lauretta; Lindsey R. Koelbel; Martin C. Towner; Phil Bland; Steve Heathcote; Timothy M.C. Abbott; Emmanuel Jehin; Toni Hanke; Elise Fahl; Rynault van Wyk; Tim Cooper; et al. (Icarus, 2023)

Rate of onset of dopamine transporter inhibitors assessed with intracranial self-stimulation and in vivo dopamine photometry in rats - Tyson R. Baird; Kimberly N. Karin; Samuel A. Marsh; F. Ivy Carroll; J. M. L. Medina-Contreras; S. Stevens Negus; Jose M. Eltit (Psychopharmacology, 2023)

Native solitary bee reproductive success depends on early season precipitation and host plant richness - Lila R. Westreich; Samuel T. Westreich; Patrick C. Tobin (Oecologia, 2023)

Resistance to mild cold stress is greater in both wild-type and long-lived GHR-KO female mice - Yimin Fang; David Medina; Robert Stockwell; Samuel McFadden; Erin R. Hascup; Kevin N. Hascup; Andrzej Bartke (GeroScience, 2023)

DiceCT for fishes: recommendations for pairing iodine contrast agents with μCT to visualize soft tissues in fishes - Matthew A. Kolmann; Ramon S. Nagesan; James V. Andrews; Samuel R. Borstein; Rodrigo Tinoco Figueroa; Randal A. Singer; Matt Friedman; Hernán López‐Fernández (Journal of Fish Biology, 2023)
Computed tomography (CT) scanning and other high‐throughput three‐dimensional (3D) visualization tools are transforming the ways we study morphology, ecology and evolutionary biology research beyond generating vast digital repositories of anatomical data. Contrast‐enhanced chemical staining methods, which render soft tissues radio‐opaque when coupled with CT scanning, encompass several approaches that are growing in popularity and versatility. Of these, the various diceCT techniques that use an iodine‐based solution like Lugol's have provided access to an array of morphological data sets spanning extant vertebrate lineages. This contribution outlines straightforward means for applying diceCT techniques to preserved museum specimens of cartilaginous and bony fishes, collectively representing half of vertebrate species diversity. This study contrasts the benefits of using either aqueous or ethylic Lugol's solutions and reports few differences between these methods with respect to the time required to achieve optimal tissue contrast. It also explores differences in minimum stain duration required for different body sizes and shapes and provides recommendations for staining specimens individually or in small batches. As reported by earlier studies, the authors note a decrease in pH during staining with either aqueous or ethylic Lugol's. Nonetheless, they could not replicate the drastic declines in pH reported elsewhere. They provide recommendations for researchers and collections staff on how to incorporate diceCT into existing curatorial practices, while offsetting risk to specimens. Finally, they outline how diceCT with Lugol's can aid ichthyologists of all kinds in visualizing anatomical structures of interest: from brains and gizzards to gas bladders and pharyngeal jaw muscles.

Vadose-zone alteration of metaschoepite and ceramic UO2 in Savannah River Site field lysimeters - Connaugh M. Fallon; William R. Bower; Brian A. Powell; Francis R. Livens; Ian C. Lyon; Alana E. McNulty; Kathryn Peruski; J. Frederick W. Mosselmans; Daniel I. Kaplan; Daniel Grolimund; Peter Warnicke; Dario Ferreira-Sanchez; et al. (Science of The Total Environment, 2023)

A chromosome-level genome assembly reveals that a bipartite gene cluster formed via an inverted duplication controls monoterpenoid biosynthesis in Schizonepeta tenuifolia - Chanchan Liu; Samuel J. Smit; Jingjie Dang; Peina Zhou; Grant T. Godden; Zheng Jiang; Wukun Liu; Licheng Liu; Wei Lin; Jinao Duan; Qinan Wu; Benjamin R. Lichman (Molecular Plant, 2023)

A re-analysis that replicated a replication: Rejoinder to - Neil R. Caton; Samuel G. Pearson; Barnaby J.W. Dixson (Evolution and Human Behavior, 2023)

Revisiting Salvucci’s Semi-analytical Solution for Bare Soil Evaporation with New Consideration of Vapour Diffusion and Film Flow - Simon A. Mathias; Graham C. Sander; Jessica Leung; Samuel R. Newall (Transport in Porous Media, 2023)
Bare soil evaporation is controlled by a combination of capillary flow, vapour diffusion and film flow. Relevant analytical solutions mostly assume horizontal flow conditions and ignore gravitational effects. Salvucci (1997) provided a rare example of a semi-analytical solution for vertical bare soil evaporation. However, they did not explicitly represent vapour diffusion and film flow, which are likely to account for a significant proportion of total flow during vertical evaporation from soils. Vapour diffusion and film flow can be incorporated via Salvucci’s desorptivity parameter, which represents the proportionality constant relating Stage 2 cumulative evaporation to the square root of time under horizontal flow conditions. The objective of this article is to implement vapour diffusion and film flow within Salvucci’s semi-analytical solution and test its performance by comparison with isothermal numerical simulation and relevant experimental data. The following important conclusions are drawn. Analytical solutions that assume horizontal flow conditions are inadequate for understanding vertical evaporation problems because they overestimate evaporation rates and mostly predict vapour diffusion and film flow to be of negligible influence. Salvucci’s semi-analytical solution is effective at predicting the order-of-magnitude reduction in evaporation caused by gravitational effects. However, it is unable to identify the correct importance of vapour diffusion and film flow because these processes can only be represented through its desorptivity parameter.

Correction to: A strong backbone for an invertebrate group: anchored phylogenomics improves the resolution of genus-level relationships within the Lumbricidae (Annelida, Crassiclitellata) - Daniel F. Marchán; Samuel W. James; Alan R. Lemmon; Emily Moriarty Lemmon; Marta Novo; Jorge Domínguez; Darío J. Díaz Cosín; Dolores Trigo (Organisms Diversity & Evolution, 2023)

Role of Vertically Migrating and Not-Migrating Large Crustacean Zooplankton as Potential Consumers of Spring Phytoplankton in an Inshore Patagonian Gulf - Leonardo R. Castro; José Luis Iriarte; Samuel Soto; Humberto González (Estuaries and Coasts, 2023)

Fur removal promotes an earlier expression of involution-related genes in mammary gland of lactating mice - Elżbieta Król; Frances Turner; Davina Derous; Sharon E. Mitchell; Samuel A. M. Martin; Alex Douglas; John R. Speakman (Journal of Comparative Physiology B, 2023)
Peak lactation occurs when milk production is at its highest. The factors limiting peak lactation performance have been subject of intense debate. Milk production at peak lactation appears limited by the capacity of lactating females to dissipate body heat generated as a by-product of processing food and producing milk. As a result, manipulations that enhance capacity to dissipate body heat (such as fur removal) increase peak milk production. We investigated the potential correlates of shaving-induced increases in peak milk production in laboratory mice. By transcriptomic profiling of the mammary gland, we searched for the mechanisms underlying experimentally increased milk production and its consequences for mother–young conflict over weaning, manifested by advanced or delayed involution of mammary gland. We demonstrated that shaving-induced increases in milk production were paradoxically linked to reduced expression of some milk synthesis-related genes. Moreover, the mammary glands of shaved mice had a gene expression profile indicative of earlier involution relative to unshaved mice. Once provided with enhanced capacity to dissipate body heat, shaved mice were likely to rear their young to independence faster than unshaved mothers.

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Reproductive ecology of muskellunge ( Esox masquinongy ), an introduced predator, in the lower Wolastoq/Saint John River, New Brunswick, Canada - Kaleb Zelman; Phillip Harrison; Antóin M. O'Sullivan; Samuel Andrews; Stephen Peake; Tommi Linnansaari; Scott A. Pavey; R. Allen Curry (Journal of Fish Biology, 2023)
Introduced predators can have harmful top‐down effects on their newly colonized system through competition with and direct predation on native species. Following an initial introduction of muskellunge in Lac Frontière, Québec in the 1970s at the headwaters of the Wolastoq/Saint John River, the species rapidly migrated downstream, expanding its range by ~500 km over ~20 years. Despite this expansive colonization and concern over possible threats to native species, little is known about the basic ecology of muskellunge in this system. The last downstream barrier is the hydroelectric facility, Mactaquac Generating Station (MGS), 150 km upstream of the sea. While there are no downstream fish passage facilities at MGS, adult muskellunge have been recorded downstream. In this study, muskellunge ( n = 23) were surgically tagged with very‐high‐frequency (VHF) radio or combined acoustic radio telemetry (CART) tags and tracked over two spawning seasons. We sought to determine if there was a reproducing population downstream of MGS and tracked Tagged muskellunge over two spawning seasons. We tracked fish to locate and confirm spawning sites, and followed up with egg and/or juvenile sampling surveys. Tagged muskellunge (90%) moved upstream towards the MGS during the spawning period in each year (2016 and 2017), where they remained throughout the entire spawning period. No spawning or nursery sites were confirmed near MGS, but in 2016 three distinct spawning locations and six distinct nursery sites were confirmed 10–12 km downstream amongst a chain of flooded islands. In 2016, eggs, sac‐fry and juveniles were collected and confirmed as muskellunge by genetic sequencing, providing the first empirical observation of successful spawning downstream of MGS.

Glycocalyx-targeted therapy ameliorates age-related arterial dysfunction - Daniel R. Machin; Daniel W. Trott; Venkateswara R. Gogulamudi; Md. Torikul Islam; Samuel I. Bloom; Hans Vink; Lisa A. Lesniewski; Anthony J. Donato (GeroScience, 2023)

Meta-analysis of global soil data identifies robust indicators for short-term changes in soil organic carbon stock following land use change - Samuel Eze; Matthew Magilton; Daniel Magnone; Sandra Varga; Iain Gould; Theresa G. Mercer; Matthew R. Goddard (Science of The Total Environment, 2023)

Evaluation of iGDGT carbon isotope fractionation in high performance liquid chromatography - Katherine J. Keller; Samuel R. Phelps; Ann Pearson (Organic Geochemistry, 2023)

Subaqueous clinoforms created by sandy wave-supported gravity flows: Lessons from the Central California shelf - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad (Marine Geology, 2023)

Chromium stable isotope distributions in the southwest Pacific Ocean and constraints on hydrothermal input from the Kermadec Arc - David J Janssen; Delphine Gilliard; Jörg Rickli; Philipp Nasemann; Andrea Koschinsky; Christel S Hassler; Andrew R Bowie; Michael J Ellwood; Charlotte Kleint; Samuel L Jaccard (Geochimica et Cosmochimica Acta, 2023)

Protecting biodiversity via conservation networks: Taxonomic, functional, and phylogenetic considerations - Michael R. Willig; Steven J. Presley; Brian T. Klingbeil; Evsey Kosman; Tao Zhang; Samuel M. Scheiner (Biological Conservation, 2023)

Increasing contribution of alluvial groundwater to riparian cottonwood forest water use through warm and dry summers - Oscar R. Zimmerman; David W. Pearce; Samuel G. Woodman; Stewart B. Rood; Lawrence B. Flanagan (Agricultural and Forest Meteorology, 2023)

Benthic foraminifera as an environmental proxy for pollutants along the coast of Chennai, India - K. Balachandar; C. Viswanathan; R.S. Robin; K.R. Abhilash; R. Sankar; V. Deepak Samuel; R. Purvaja; R. Ramesh (Chemosphere, 2023)

A precipitation reconstruction based on pinyon pine tree rings from the northeastern Mexican subtropic - Samuel Arroyo-Morales; Claudia C. Astudillo-Sánchez; Oscar Alberto Aguirre-Calderón; José Villanueva-Díaz; Leroy Soria-Díaz; Aldo R. Martínez-Sifuentes (Theoretical and Applied Climatology, 2023)

A method to sample small mammals in the subnivium - Samuel R. Jolly; Allison M. Scott; Tanya R. Aldred; Jonathan H. Gilbert; Jonathan N. Pauli (Mammal Research, 2023)

Placental mesenchymal stem cells restore glucose and energy homeostasis in obesogenic adipocytes - Nagasuryaprasad Kotikalapudi; Samuel Joshua Pragasam Sampath; Sukesh Narayan Sinha; Bhonde R; Sathish Kumar Mungamuri; Vijayalakshmi Venkatesan (Cell and Tissue Research, 2023)

The effects of marine heatwaves on acute heat tolerance in corals - Magena R. Marzonie; Line K. Bay; David G. Bourne; Andrew S. Hoey; Samuel Matthews; Josephine J. V. Nielsen; Hugo B. Harrison (Global Change Biology, 2023)
Scleractinian coral populations are increasingly exposed to conditions above their upper thermal limits due to marine heatwaves, contributing to global declines of coral reef ecosystem health. However, historic mass bleaching events indicate there is considerable inter‐ and intra‐specific variation in thermal tolerance whereby species, individual coral colonies and populations show differential susceptibility to exposure to elevated temperatures. Despite this, we lack a clear understanding of how heat tolerance varies across large contemporary and historical environmental gradients, or the selective pressures that underpin this variation. Here we conducted standardised acute heat stress experiments to identify variation in heat tolerance among species and isolated reefs spanning a large environmental gradient across the Coral Sea Marine Park. We quantified the photochemical yield ( F v /F m ) of coral samples in three coral species, Acropora cf humilis , Pocillopora meandrina , and Pocillopora verrucosa , following exposure to four temperature treatments (local ambient temperatures, and + 3°C, +6°C and + 9°C above local maximum monthly mean). We quantified the temperature at which F v /F m decreased by 50% (termed ED50) and used derived values to directly compare acute heat tolerance across reefs and species. The ED50 for Acropora was 0.4–0.7°C lower than either Pocillopora species, with a 0.3°C difference between the two Pocillopora species. We also recorded 0.9°C to 1.9°C phenotypic variation in heat tolerance among reefs within species, indicating spatial heterogeneity in heat tolerance across broad environmental gradients. Acute heat tolerance had a strong positive relationship to mild heatwave exposure over the past 35 years (since 1986) but was negatively related to recent severe heatwaves (2016–2020). Phenotypic variation associated with mild thermal history in local environments provides supportive evidence that marine heatwaves are selecting for tolerant individuals and populations; however, this adaptive potential may be compromised by the exposure to recent severe heatwaves.

Capacity of deep‐sea corals to obtain nutrition from cold seeps aligned with microbiome reorganization - Eslam O. Osman; Samuel A. Vohsen; Fanny Girard; Rafaelina Cruz; Orli Glickman; Lena M. Bullock; Kaitlin E. Anderson; Alexis M. Weinnig; Erik E. Cordes; Charles R. Fisher; Iliana B. Baums (Global Change Biology, 2023)
Cold seeps in the deep sea harbor various animals that have adapted to utilize seepage chemicals with the aid of chemosynthetic microbes that serve as primary producers. Corals are among the animals that live near seep habitats and yet, there is a lack of evidence that corals gain benefits and/or incur costs from cold seeps. Here, we focused on Callogorgia delta and Paramuricea sp. type B3 that live near and far from visual signs of currently active seepage at five sites in the deep Gulf of Mexico. We tested whether these corals rely on chemosynthetically‐derived food in seep habitats and how the proximity to cold seeps may influence; (i) coral colony traits (i.e., health status, growth rate, regrowth after sampling, and branch loss) and associated epifauna, (ii) associated microbiome, and (iii) host transcriptomes. Stable isotope data showed that many coral colonies utilized chemosynthetically derived food, but the feeding strategy differed by coral species. The microbiome composition of C. delta , unlike Paramuricea sp., varied significantly between seep and non‐seep colonies and both coral species were associated with various sulfur‐oxidizing bacteria (SUP05). Interestingly, the relative abundances of SUP05 varied among seep and non‐seep colonies and were strongly correlated with carbon and nitrogen stable isotope values. In contrast, the proximity to cold seeps did not have a measurable effect on gene expression, colony traits, or associated epifauna in coral species. Our work provides the first evidence that some corals may gain benefits from living near cold seeps with apparently limited costs to the colonies. Cold seeps provide not only hard substrate but also food to cold‐water corals. Furthermore, restructuring of the microbiome communities (particularly SUP05) is likely the key adaptive process to aid corals in utilizing seepage‐derived carbon. This highlights that those deep‐sea corals may upregulate particular microbial symbiont communities to cope with environmental gradients.

A strong backbone for an invertebrate group: anchored phylogenomics improves the resolution of genus-level relationships within the Lumbricidae (Annelida, Crassiclitellata) - Daniel F. Marchán; Samuel W. James; Alan R. Lemmon; Emily Moriarty Lemmon; Marta Novo; Jorge Domínguez; Darío J. Díaz Cosín; Dolores Trigo (Organisms Diversity & Evolution, 2022)

JM-20, a Benzodiazepine-Dihydropyridine Hybrid Molecule, Inhibits the Formation of Alpha-Synuclein-Aggregated Species - Cleonice Creusa Santos; Thyago R. Cardim-Pires; Liana Shvachiy; Luis Arturo Fonseca-Fonseca; Patricia Muñoz; Áurea Maria A. N. Almeida; Ana Carla S. Costa; Jéssica Teles-Souza; Estael Ochoa-Rodríguez; Maria de Fátima Dias Costa; Fernando L. Palhano; Juan Segura-Aguilar; et al. (Neurotoxicity Research, 2022)

Aging results in DNA damage and telomere dysfunction that is greater in endothelial versus vascular smooth muscle cells and is exacerbated in atheroprone regions - Samuel I. Bloom; Jordan R. Tucker; Jisok Lim; Tyler G. Thomas; Gregory J. Stoddard; Lisa A. Lesniewski; Anthony J. Donato (GeroScience, 2022)

Non-pharmacological interventions for vascular health and the role of the endothelium - Samuel R. C. Weaver; Catarina Rendeiro; Rebekah A. I. Lucas; N. Timothy Cable; Tom E. Nightingale; Helen M. McGettrick; Samuel J. E. Lucas (European Journal of Applied Physiology, 2022)
The most common non-pharmacological intervention for both peripheral and cerebral vascular health is regular physical activity (e.g., exercise training), which improves function across a range of exercise intensities and modalities. Numerous non-exercising approaches have also been suggested to improved vascular function, including repeated ischemic preconditioning (IPC); heat therapy such as hot water bathing and sauna; and pneumatic compression. Chronic adaptive responses have been observed across a number of these approaches, yet the precise mechanisms that underlie these effects in humans are not fully understood. Acute increases in blood flow and circulating signalling factors that induce responses in endothelial function are likely to be key moderators driving these adaptations. While the impact on circulating factors and environmental mechanisms for adaptation may vary between approaches, in essence, they all centre around acutely elevating blood flow throughout the circulation and stimulating improved endothelium-dependent vascular function and ultimately vascular health. Here, we review our current understanding of the mechanisms driving endothelial adaptation to repeated exposure to elevated blood flow, and the interplay between this response and changes in circulating factors. In addition, we will consider the limitations in our current knowledge base and how these may be best addressed through the selection of more physiologically relevant experimental models and research. Ultimately, improving our understanding of the unique impact that non-pharmacological interventions have on the vasculature will allow us to develop superior strategies to tackle declining vascular function across the lifespan, prevent avoidable vascular-related disease, and alleviate dependency on drug-based interventions.

Characterization of Multidrug-Resistant Staphylococcus aureus Isolates and Comparison of Methods of Susceptibility to Vancomycin - Danillo S. Rosa; Samily A. S. Oliveira; Renata F. S. Souza; Amaro A. S. Neto; Letícia S. B. Cunha; Antônio W. C. Fernandes; Ianka F. S. Soares; Sarah K. R. Teixeira; Samuel R. Aquino; Gisele V. Gouveia; Jackson R. G. S. Almeida; Carine R. Naue; et al. (Current Microbiology, 2022)

Feeding habits influence species habitat associations at the landscape scale in a diverse clade of Neotropical fishes - Karold Viviana Coronado‐Franco; Pablo A. Tedesco; Matthew A. Kolmann; Samuel R. Borstein; Kristine O. Evans; Sandra Bibiana Correa (Journal of Biogeography, 2022)
Aim A primary goal of community ecology is to understand the mechanisms that drive species' spatial distribution and habitat associations. Species' geographic distribution can be influenced by the distribution of their prey partly because consumers' behaviour is oriented to optimal energy use during foraging. We analysed how differences in dietary preferences influence the spatial distribution and habitat associations of species at the landscape scale. We hypothesized that differences in feeding guilds will lead to divergent habitat association patterns among species. Location Amazon River drainage basin. Taxon Characiform fishes in the family Serrasalmidae (piranhas and pacus). Methods We used diet data to classify species into feeding guilds (frugivores, herbivores, piscivores, fin and scale feeders and planktivores). We used three proxies of habitat association derived from satellite products: floodplain extent, landscape heterogeneity and flood duration, in three distance buffers. We implemented phylogenetic generalized least squares models to evaluate the relationship between habitat association and feeding guilds. Results Frugivores, piscivores and fin and scale feeders presented similar patterns of habitat associations, with frugivores occupying wider areas of floodplain and greater landscape heterogeneity. Herbivores and planktivores were associated with smaller floodplain extents and lower landscape heterogeneity. All feeding guilds were associated with similar levels of flood duration. Main conclusions Differences in resource distribution (assessed through feeding guilds) can influence habitat association. Considering the hydrological variability (i.e. floodplain extent) and landscape heterogeneity that characterize floodplains, the patterns of habitat association vary with the spatial scale considered. This work highlights the importance of understanding species habitat associations by fish as well as food resource dynamics and floodplain dependence. This realization is critical for assessing the impact of anthropogenic activities on freshwater ecosystems.

Avoiding growing pains in reproductive trait databases: the curse of dimensionality - Samuel C. Ginther; Hayley Cameron; Craig R. White; Dustin J. Marshall (Global Ecology and Biogeography, 2022)
Aim Reproductive output features prominently in many trait databases, but the metrics describing it vary and are often untethered to temporal and volumetric dimensions (e.g., fecundity per bout). The use of such ambiguous reproductive measures to make broad‐scale comparisons across taxonomic groups will be meaningful only if they show a 1:1 relationship with a reproductive measure that explicitly includes both a volumetric and a temporal component (i.e., reproductive mass per year). We sought to map the prevalence of ambiguous and explicit reproductive measures across taxa and to explore their relationships with one another to determine the cross‐compatibility and utility of reproductive metrics in trait databases. Location Global. Time period 1990–2021. Major taxa studied We searched for reproductive measures across all Metazoa and identified 19,785 vertebrate species (Chordata), and 440 invertebrate species (Arthropoda, Cnidaria or Mollusca). Methods We included 37 databases, from which we summarized the commonality of reproductive metrics across taxonomic groups. We also quantified scaling relationships between ambiguous reproductive traits (fecundity per bout, fecundity per year and reproductive mass per bout) and an explicit measure (reproductive mass per year) to assess their cross‐compatibility. Results Most species were missing at least one temporal or volumetric dimension of reproductive output, such that reproductive mass per year could be reconstructed for only 4,786 vertebrate species. Ambiguous reproductive measures were poor predictors of reproductive mass per year; in no instance did these measures scale at 1:1. Main conclusions Ambiguous measures systematically misestimate reproductive mass per year. Until more data are collected, we suggest that researchers should use the clade‐specific scaling relationships provided here to convert ambiguous reproductive measures to reproductive mass per year.

Impact of salinity origin on microbial communities in saline springs within the Illinois Basin, USA - Linduo Zhao; Hongbo Shao; Li Zhang; Samuel V. Panno; Walton R. Kelly; Tzu‐Yu Lin; Wen‐Tso Liu; Theodore M. Flynn; Peter Berger (Environmental Microbiology, 2022)
Saline springs within the Illinois Basin result from the discharge of deep‐seated evaporated seawater (brine) and likely contain diverse and complex microbial communities that are poorly understood. In this study, seven saline/mineral springs with different geochemical characteristics and salinity origins were investigated using geochemical and molecular microbiological analyses to reveal the composition of microbial communities inhabiting springs and their key controlling factors. The 16S rRNA sequencing results demonstrated that each spring harbours a unique microbial community influenced by its geochemical properties and subsurface conditions. The microbial communities in springs that originated from Cambrian/Ordovician strata, which are deep confined units that have limited recharge from overlying formations, share a greater similarity in community composition and have a higher species richness and more overlapped taxa than those that originated from shallower Pennsylvanian strata, which are subject to extensive regional surface and groundwater recharge. The microbial distribution along the spring flow paths at the surface indicates that 59.8%–94.2% of total sequences in sedimentary samples originated from spring water, highlighting the role of springs in influencing microbiota in the immediate terrestrial environment. The results indicate that the springs introduce microbiota with a high biodiversity into surface terrestrial or aquatic ecosystems, potentially affecting microbial reservoirs in downstream ecosystems.

Perspectives on strengthening local food systems in Small Island Developing States - Cornelia Guell; Catherine R. Brown; Otto W. Navunicagi; Viliamu Iese; Neela Badrie; Morgan Wairiu; Arlette Saint Ville; Nigel Unwin; Sashi Kiran; T. Alafia Samuels; Ian Hambleton; Colin Tukuitonga; et al. (Food Security, 2022)
Small Island Developing States (SIDS) share high burdens of nutrition-related conditions, including non-communicable diseases, associated with an increasing reliance on imported, processed foods. Improving health through increasing the production and consumption of local, nutritious foods is a policy objective of many SIDS governments. This study aimed to understand contemporary challenges and opportunities to strengthening local food systems in two case study settings, Fiji and St. Vincent and the Grenadines. Fifty-two in-depth, semi-structured interviews were conducted with key stakeholders involved in local food production. Interviews were analysed by both country teams using thematic analysis. Local food production networks in both settings included formal governance bodies as well as more informal connections through civil society and communities. Their main function was the sharing of resources and knowledge, but levels of trust and cooperation between the stakeholders varied in a market open to intense competition from imports. Local food production was hindered by few and slow investments by local governments, dated technology, and lack of knowledge. Stakeholders believed this marginalisation was occurring against a background of rising preferences for imported foods in the population, and increasing disinterest in employment in the sector. Despite the challenges, strong narratives of resilience and opportunity were highlighted such as national pride in local produce for commercialisation and local diets. Efforts to support local food production in SIDS should focus on strengthening governance structures to prioritise local produce over corporate and import markets, assist collaboration and co-learning, and support alternative agro-food practices.

Introduced galliforms as seed predators and dispersers in Hawaiian forests - Samuel B. Case; Katherine Postelli; Donald R. Drake; Jeferson Vizentin-Bugoni; Jeffrey T. Foster; Jinelle H. Sperry; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2022)

Biofloc meal incorporated diet improves the growth and physiological responses of Penaeus vannamei - M. Nethaji; B. Ahilan; A. Kathirvelpandiyan; N. Felix; A. Uma; T. L. S. Samuel Mosses; R. Somu Sunder Lingam (Aquaculture International, 2022)

Vertical space use and thermal range of the great hammerhead ( Sphyrna mokarran ), (Rüppell, 1837) in the western North Atlantic - Tristan L. Guttridge; Lukas Müller; Bryan A. Keller; Mark E. Bond; R Dean. Grubbs; William Winram; Lucy A. Howey; Bryan S. Frazier; Samuel H. Gruber (Journal of Fish Biology, 2022)
The great hammerhead ( Sphyrna mokarran ) is a highly mobile, large‐bodied shark primarily found in coastal‐pelagic and semi‐oceanic waters across a circumtropical range. It is a target or by‐catch species in multiple fisheries, and as a result, rapid population declines have occurred in many regions. These declines have contributed to the species being assessed as globally critically endangered on the IUCN Red List. Although conservation and management measures have yielded promising results in some regions, such as the United States, high levels of at‐vessel and post‐release mortality remain a major concern to the species population recovery. This examined the vertical space use and thermal range of pop‐off archival satellite–tagged S. mokarran in the western North Atlantic Ocean, expanding the understanding of the ecological niche of this species and providing insight into by‐catch mitigation strategies for fisheries managers. The results showed that S. mokarran predominantly used shallow depths (75% of records S. mokarran may be vulnerable to incidental capture in the western North Atlantic commercial longline fisheries due to substantial vertical overlap between the species and the gear. The results can be incorporated into conservation and management efforts to develop and/or refine mitigation measures focused on reducing the by‐catch and associated mortality of this species, which can ultimately aide S. mokarran population recovery in areas with poor conservation status.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Elevated [CO2] mitigates the impacts of heat stress in eucalyptus seedlings - Samuel S. Pinto; Auxiliadora O. Martins; Luiz F. P. Fontes; Franciele S. Oliveira; Iale C. Almeida; Iagor B. Detoni; Leonardo A. Oliveira; Willian B. Silva; David B. Medeiros; Edgar A. T. Picoli; Aristides Ribeiro; Alisdair R. Fernie; et al. (Theoretical and Experimental Plant Physiology, 2022)

Genomic regions associated with resistance to soybean rust (Phakopsora pachyrhizi) under field conditions in soybean germplasm accessions from Japan, Indonesia and Vietnam - David R. Walker; Samuel C. McDonald; Donna K. Harris; H. Roger Boerma; James W. Buck; Edward J. Sikora; David B. Weaver; David L. Wright; James J. Marois; Zenglu Li (Theoretical and Applied Genetics, 2022)
Key message Eight soybean genomic regions, including six never before reported, were found to be associated with resistance to soybean rust ( Phakopsora pachyrhizi ) in the southeastern USA. Abstract Soybean rust caused by Phakopsora pachyrhizi is one of the most important foliar diseases of soybean [ Glycine max (L.) Merr.]. Although seven Rpp resistance gene loci have been reported, extensive pathotype variation in and among fungal populations increases the importance of identifying additional genes and loci associated with rust resistance. One hundred and ninety-one soybean plant introductions from Japan, Indonesia and Vietnam, and 65 plant introductions from other countries were screened for resistance to P. pachyrhizi under field conditions in the southeastern USA between 2008 and 2015. The results indicated that 84, 69, and 49% of the accessions from southern Japan, Vietnam or central Indonesia, respectively, had negative BLUP values, indicating less disease than the panel mean. A genome-wide association analysis using SoySNP50K Infinium BeadChip data identified eight genomic regions on seven chromosomes associated with SBR resistance, including previously unreported regions of Chromosomes 1, 4, 6, 9, 13, and 15, in addition to the locations of the Rpp3 and Rpp6 loci. The six unreported genomic regions might contain novel Rpp loci. The identification of additional sources of rust resistance and associated genomic regions will further efforts to develop soybean cultivars with broad and durable resistance to soybean rust in the southern USA.

Elevated carbon assimilation and metabolic reprogramming in tomato high pigment mutants support the increased production of pigments - Auderlan M. Pereira; Auxiliadora O. Martins; Willian Batista-Silva; Jorge A. Condori-Apfata; Vitor L. Nascimento; Victor F. Silva; Leonardo A. Oliveira; David B. Medeiros; Samuel C. V. Martins; Alisdair R. Fernie; Adriano Nunes-Nesi; Wagner L. Araújo (Plant Cell Reports, 2022)

A new approach to the classification of carcinogenicity - John E. Doe; Alan R. Boobis; Samuel M. Cohen; Vicki L. Dellarco; Penelope A. Fenner-Crisp; Angelo Moretto; Timothy P. Pastoor; Rita S. Schoeny; Jennifer G. Seed; Douglas C. Wolf (Archives of Toxicology, 2022)
Concern over substances that may cause cancer has led to various classification schemes to recognize carcinogenic threats and provide a basis to manage those threats. The least useful schemes have a binary choice that declares a substance carcinogenic or not. This overly simplistic approach ignores the complexity of cancer causation by considering neither how the substance causes cancer, nor the potency of that mode of action. Consequently, substances are classified simply as “carcinogenic”, compromising the opportunity to properly manage these kinds of substances. It will likely be very difficult, if not impossible, to incorporate New Approach Methodologies (NAMs) into binary schemes. In this paper we propose a new approach cancer classification scheme that segregates substances by both mode of action and potency into three categories and, as a consequence, provides useful guidance in the regulation and management of substances with carcinogenic potential. Examples are given, including aflatoxin (category A), trichlorethylene (category B), and titanium dioxide (category C), which demonstrate the clear differentiation among these substances that generate appropriate levels of concern and management options.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Development of a low-cost multifunctional scale for the study of plant transpiration using the Arduino platform - Wenderson R. F. Silva; Moab T. Andrade; Karoline G. Mendes; Samuel C. V. Martins (Theoretical and Experimental Plant Physiology, 2022)

Effects of modafinil on electroencephalographic microstates in healthy adults - Samantha R. Linton; Michael Murphy; Hans S. Schroder; Micah Breiger; Ann M. Iturra-Mena; Brian D. Kangas; Jack Bergman; William A. Carlezon; Victoria B. Risbrough; Samuel A. Barnes; Andre Der-Avakian; Diego A. Pizzagalli (Psychopharmacology, 2022)

Association patterns and community structure among female bottlenose dolphins: environmental, genetic and cultural factors - Svenja M. Marfurt; Simon J. Allen; Manuela R. Bizzozzero; Erik P. Willems; Stephanie L. King; Richard C. Connor; Anna M. Kopps; Sonja Wild; Livia Gerber; Samuel Wittwer; Michael Krützen (Mammalian Biology, 2022)
Social structuring from assortative associations may affect individual fitness, as well as population-level processes. Gaining a broader understanding of social structure can improve our knowledge of social evolution and inform wildlife conservation. We investigated association patterns and community structure of female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, assessing the role of kinship, shared culturally transmitted foraging techniques, and habitat similarity based on water depth. Our results indicated that associations are influenced by a combination of uni- and biparental relatedness, cultural behaviour and habitat similarity, as these were positively correlated with a measure of dyadic association. These findings were matched in a community level analysis. Members of the same communities overwhelmingly shared the same habitat and foraging techniques, demonstrating a strong homophilic tendency. Both uni- and biparental relatedness between dyads were higher within than between communities. Our results illustrate that intraspecific variation in sociality in bottlenose dolphins is influenced by a complex combination of genetic, cultural, and environmental aspects.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comparison Between Pure Component Modeling Approaches for Monitoring Pharmaceutical Powder Blends with Near-Infrared Spectroscopy in Continuous Manufacturing Schemes - Adam J. Rish; Samuel R. Henson; Md. Anik Alam; Yang Liu; James K. Drennen; Carl A. Anderson (The AAPS Journal, 2022)

Cryptic extinction risk in a western Pacific lizard radiation - Peter J. McDonald; Rafe M. Brown; Fred Kraus; Philip Bowles; Umilaela Arifin; Samuel J. Eliades; Robert N. Fisher; Maren Gaulke; L. Lee Grismer; Ivan Ineich; Benjamin R. Karin; Camila G. Meneses; et al. (Biodiversity and Conservation, 2022)
Cryptic ecologies, the Wallacean Shortfall of undocumented species’ geographical ranges and the Linnaean Shortfall of undescribed diversity, are all major barriers to conservation assessment. When these factors overlap with drivers of extinction risk, such as insular distributions, the number of threatened species in a region or clade may be underestimated, a situation we term ‘cryptic extinction risk’. The genus Lepidodactylus is a diverse radiation of insular and arboreal geckos that occurs across the western Pacific. Previous work on Lepidodactylus showed evidence of evolutionary displacement around continental fringes, suggesting an inherent vulnerability to extinction from factors such as competition and predation. We sought to (1) comprehensively review status and threats, (2) estimate the number of undescribed species, and (3) estimate extinction risk in data deficient and candidate species, in Lepidodactylus . From our updated IUCN Red List assessment, 60% of the 58 recognized species are threatened (n = 15) or Data Deficient (n = 21), which is higher than reported for most other lizard groups. Species from the smaller and isolated Pacific islands are of greatest conservation concern, with most either threatened or Data Deficient, and all particularly vulnerable to invasive species. We estimated 32 undescribed candidate species and linear modelling predicted that an additional 18 species, among these and the data deficient species, are threatened with extinction. Focusing efforts to resolve the taxonomy and conservation status of key taxa, especially on small islands in the Pacific, is a high priority for conserving this remarkably diverse, yet poorly understood, lizard fauna. Our data highlight how cryptic ecologies and cryptic diversity combine and lead to significant underestimation of extinction risk.

Detection of climate transitions and discontinuities by Hurst rescaling - David R. Legates; Samuel I. Outcalt (International Journal of Climatology, 2022)
The method of Outcalt et al., based on work developed originally by Hurst, is re‐examined to evaluate its efficacy in delineating changes in trends and identifying regime shifts in climatic‐related time series. This technique is based on the concept of the normalized rescaled running sum where temporal changes in the Hurst exponent can be used to identify climatic trends from one regime to another as each regime has a characteristic distribution that differs from the statistical characteristics of the complete time series. An examination of the temporal change in the amplitude of the normalized rescaled running sum can be used as a method to identify these regime changes, which may be either real (i.e., a true climatic shift) or induced (i.e., through a change in measurement bias, station location, or other nonclimatic influence). Examples shown here focus on examining time series of the Pacific Decadal Oscillation, Arctic thaw depth, the Northern Hemisphere snow cover extent, treeflow data from Lees Ferry (AZ), North Atlantic tropical cyclone frequency, and central England air temperatures.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Spatial clustering of trumpetfish shadowing behaviour in the Caribbean Sea revealed by citizen science - Samuel R. Matchette; Emily G. Mitchell; James E. Herbert-Read (Marine Biology, 2022)
The West Atlantic trumpetfish ( Aulostomus maculatus ) performs an unusual hunting strategy, termed shadowing, whereby a trumpetfish swims closely behind or next to another ‘host’ species to facilitate the capture of prey. Despite trumpetfish being observed throughout the Caribbean, observations of this behaviour appear to be concentrated to a handful of localities. Here we assess the degree of geographical clustering of shadowing behaviour throughout the Caribbean Sea, and identify ecological features associated with the likelihood of its occurrence. To do this, we used a citizen science approach by creating and distributing an online survey to target frequent divers across this region. While the vast majority of participants observed trumpetfish on nearly every dive across the Caribbean, using random labelling spatial analyses, we found the frequency of shadowing behaviour was geographically clustered; participants that were within ~ 120 km of each other reported observations of shadowing that were more similar than would be expected by chance. Our survey also highlighted that trumpetfish were more likely to be observed shadowing than observed alone in a particular habitat type, and with particular host species, suggesting potential ecological factors that could drive the uneven distribution of this behaviour. Our results demonstrate that this behavioural hunting strategy is spatially clustered and, more generally, highlight the power of using citizen science to investigate variation in animal behaviour over thousands of square kilometres.

Imaging subtle leaks in the blood–brain barrier in the aging human brain: potential pitfalls, challenges, and possible solutions - Axel Montagne; Samuel R. Barnes; Daniel A. Nation; Kassandra Kisler; Arthur W. Toga; Berislav V. Zlokovic (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recreational and occupational physical activity in relation to prostate cancer aggressiveness: the North Carolina-Louisiana Prostate Cancer Project (PCaP) - Susan E. Steck; L. Joseph Su; Samuel O. Antwi; Bonny B. Morris; Brittany Crawford; Swann Arp Adams; James R. Hebert; Elizabeth T. H. Fontham; Jeannette T. Bensen; James L. Mohler; Lenore Arab (Cancer Causes & Control, 2022)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

The effect of hypertonic saline evoked muscle pain on neurophysiological changes and exercise performance in the contralateral limb - Ryan Norbury; Samuel A. Smith; Mark Burnley; Megan Judge; Alexis R. Mauger (Experimental Brain Research, 2022)
Non-local muscle pain may impair endurance performance through neurophysiological mechanisms, but these are relatively unknown. This study examined the effects of muscle pain on neuromuscular and neurophysiological responses in the contralateral limb. On separate visits, nine participants completed an isometric time to task failure (TTF) using the right knee extensors after intramuscular injection of isotonic saline (CTRL) or hypertonic saline (HYP) into the left vastus lateralis. Measures of neuromuscular fatigue were taken before, during and after the TTF using transcranial magnetic stimulation (TMS) and peripheral nerve stimulation. Mean pain intensity was greater in the left leg in HYP (3.3 ± 1.9) compared to CTRL (0.4 ± 0.7; P < 0.001) which was combined with a reduced TTF by 9.8% in HYP (4.54 ± 0.56 min) compared to CTRL (5.07 ± 0.77 min; P = 0.005). Maximum voluntary force was not different between conditions (all P > 0.05). Voluntary activation was lower in HYP compared to CTRL ( P = 0.022). No difference was identified between conditions for doublet amplitude ( P > 0.05). Furthermore, no difference in MEP· M max −1 or the TMS silent period between conditions was observed (all P > 0.05). Non-local pain impairs endurance performance of the contralateral limb. This impairment in performance is likely due to the faster attainment of the sensory tolerance limit from a greater amount of sensory feedback originating from the non-exercising, but painful, left leg.

Warming in the upper San Francisco Estuary: Patterns of water temperature change from five decades of data - Samuel M. Bashevkin; Brian Mahardja; Larry R. Brown (Limnology and Oceanography, 2022)
Temperature is a key controlling variable from subcellular to ecosystem scales. Thus, climatic warming is expected to have broad impacts, especially in economically and ecologically valuable systems such as estuaries. The heavily managed upper San Francisco Estuary supplies water to millions of people and is home to fish species of high conservation, commercial, and recreational interest. Despite a long monitoring record (> 50 yr), we do not yet know how water temperatures have already changed or how trends vary spatially or seasonally. We fit generalized additive models on an integrated database of discrete water temperature observations to estimate long‐term trends with spatio‐seasonal variability. We found that water temperatures have increased 0.017°C yr −1 on average over the past 50 yr. Rates of temperature change have varied over time, but warming was predominant. Temperature increases were most widespread in the late‐fall to winter (November to February) and mid‐spring (April to June), coinciding with the winter development of juvenile Chinook salmon and spring spawning window of the endangered delta smelt. Warming was fastest in the northern regions, a key fish migration corridor with important tidal wetland habitat. However, no long‐term temperature trends were detected in October and were only observed in some regions in May, July, and August. These results can help identify optimal areas for restoration or refugia to buffer the effects of a warming climate, and the methods can be leveraged to understand the spatiotemporal variability in climate warming patterns in other aquatic systems.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Demographic consequences of mutualism disruption: Browsing and big‐headed ant invasion drive acacia population declines - Brandon R. Hays; Corinna Riginos; Todd M. Palmer; Daniel F. Doak; Benard C. Gituku; Nelly J. Maiyo; Samuel Mutisya; Simon Musila; Jacob R. Goheen (Ecology, 2022)
Across the globe, biological invasions have disrupted mutualisms, producing reverberating consequences for ecosystems. Although invasive species frequently trigger mutualism disruptions, few studies have quantified the demographic mechanisms by which mutualism breakdown may generate population effects. In a Kenyan savanna, the invasive big‐headed ant ( Pheidole megacephala ) has disrupted a foundational mutualism between the monodominant whistling‐thorn tree ( Acacia drepanolobium ) and native ants ( Crematogaster spp.) that deter browsing by large mammalian herbivores. We conducted experiments to quantify the demographic consequences of this mutualism disruption in the presence and absence of large mammalian herbivores. Invasion by P. megacephala exacerbated population declines of A. drepanolobium , primarily through decreased survival and reproduction of adult trees. However, these fitness reductions were small compared to those resulting from the presence of large mammalian herbivores, which negatively impacted growth and survival. Contrary to expectation, the expulsion of metabolically costly Crematogaster mutualists by P. megacephala did not result in higher population growth rates for trees protected from large mammalian herbivores. Our results suggest that invasive P. megacephala may impose a direct metabolic cost to trees exceeding that of native mutualists while providing no protection from browsing by large mammalian herbivores. Across landscapes, we expect that invasion by P. megacephala will reduce A. drepanolobium populations, but that the magnitude and demographic pathways of this effect will hinge on the presence and abundance of browsers.

Design and Development of Hot Air-assisted Continuous Infrared Drying System for Shrimps - D. S. Aniesrani Delfiya; K. Prashob; S. Murali; P. V. Alfiya; Lekshmi R. G. Kumar; Manoj P. Samuel (Journal of Aquatic Food Product Technology, 2022)

Reward processing in trichotillomania and skin picking disorder - Jon E. Grant; Tara S. Peris; Emily J. Ricketts; Richard A. I. Bethlehem; Samuel R. Chamberlain; Joseph O’Neill; Jeremiah M. Scharf; Darin D. Dougherty; Thilo Deckersbach; Douglas W. Woods; John Piacentini; Nancy J. Keuthen (Brain Imaging and Behavior, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Acetylcholinesterase inhibitory activity of Ocotea pomaderroides extracts: HPLC-MS/MS characterization and molecular modeling studies - Isabella M. A. Reis; Dayse S. A. Cassiano; Rodrigo S. Conceição; Humberto F. de Freitas; Samuel S. da R. Pita; Jorge M. David; Alexsandro Branco (Natural Product Research, 2022)

Small Differences in Diet Facilitate the Coexistence of Three Forage Fish Species in an Inshore Northern Patagonian Habitat - Lauren E. Wiesebron; Leonardo R. Castro; Samuel Soto; Jorge Castillo (Frontiers in Marine Science, 2022)
Forage fish play the crucial role of transferring energy from lower to upper trophic levels. These small pelagic fish feed on plankton and can compete with each other for food, leading to potentially complex interactions. Three forage fish species ( Sprattus fuegensis , Strangomera bentincki , and Engraulis ringens ) are commonly found in the inshore waters of Northern Chilean Patagonia, a region with large spatial variability in oceanographic conditions and in the zooplankton community. To better understand what factors may explain coexistence among these three forage fish species, we examined differences in resource availability (zooplankton community and abundances) in three locations (Chiloé, Cordillera, and Aysén regions) within Northern Patagonia. We compared the diet of the three fish species using both stable isotope and stomach content analyses, and we measured their gill rakers. S. fuegensis , the only species found in all three regions, had flexible diets which lent it greater success than the other two species at foraging in waters with fewer prey. We found little diet differentiation among the three species in the copepod-rich Cordillera region, but the diverging diets of S. bentincki and S. fuegensis in the copepod-poor Chiloé region suggest that diet partitioning in areas with fewer resources is due to competition. The small differences in diet facilitates coexistence among the three species, which may help explain the lack of correlation between the three species’ population abundances in the Cordillera region over the past 6 years. Finally, our results show that the high degree of oceanographic heterogeneity in Northern Patagonia may encourage species separation based on their specific environmental requirements.

Implementing Community-Based Prostate Cancer Education in Rural South Carolina: a Collaborative Approach Through a Statewide Cancer Alliance - Catherine Troy; Ashley Brunson; Andrew Goldsmith; Samuel Noblet; Susan E. Steck; James R. Hebert; Johnny Payne; Doug McCormick; Daniela B. Friedman (Journal of Cancer Education, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

High additions of nitrogen affect plant species-specific differences in the composition of main microbial groups and the uptake of rhizodeposited carbon in a grassland soil - Andrea Leptin; David Whitehead; Kate H. Orwin; Samuel R. McNally; John E. Hunt; Keith C. Cameron; Niklas J. Lehto (Biology and Fertility of Soils, 2022)

Complete genome sequences of two isolates of spiraea yellow leafspot virus (genus Badnavirus) from Spiraea x bumalda ‘Anthony Waterer’ - R. A. Alvarez-Quinto; Joana Serrano; Neil Olszewski; Samuel Grinstead; Dimitre Mollov; B. E. L. Lockhart (Archives of Virology, 2022)

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Fire management alters the thermal landscape and provides multi‐scale thermal options for a terrestrial turtle facing a changing climate - Ellen P. Robertson; Evan P. Tanner; R. Dwayne Elmore; Samuel D. Fuhlendorf; Jonathan D. Mays; Jennifer Knutson; John R. Weir; Scott R. Loss (Global Change Biology, 2022)
As effects of climate change intensify, there is a growing need to understand the thermal properties of landscapes and their influence on wildlife. A key thermal property of landscapes is vegetation structure and composition. Management approaches can alter vegetation and consequently the thermal landscape, potentially resulting in underappreciated consequences for wildlife thermoregulation. Consideration of spatial scale can clarify how management overlaid onto existing vegetation patterns affects thermal properties of landscapes relevant to wildlife. We examined effects of temperature, fire management, and vegetation structure on multi‐scale habitat selection of an ectothermic vertebrate (the turtle Terrapene carolina triunguis ) in the Great Plains of the central United States by linking time‐since‐fire data from 18 experimental burn plots to turtle telemetry locations and thermal and vegetation height data. Within three 60‐ha experimental landscapes, each containing six 10‐ha sub‐blocks that are periodically burned, we found that turtles select time‐since‐fire gradients differently depending on maximum daily ambient temperature. At moderate temperatures, turtles selected sub‐blocks with recent (

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Human placental mesenchymal stromal cell therapy restores the cytokine efflux and insulin signaling in the skeletal muscle of obesity-induced type 2 diabetes rat model - Nagasuryaprasad Kotikalapudi; Samuel Joshua Pragasam Sampath; Sukesh Narayan Sinha; R. Bhonde; Sathish Kumar Mungamuri; Vijayalakshmi Venkatesan (Human Cell, 2022)

A Bayesian Nonparametric Approach to Unmixing Detrital Geochronologic Data - John R. Tipton; Glenn R. Sharman; Samuel A. Johnstone (Mathematical Geosciences, 2022)

The effect of elevated muscle pain on neuromuscular fatigue during exercise - Ryan Norbury; Samuel A. Smith; Mark Burnley; Megan Judge; Alexis R. Mauger (European Journal of Applied Physiology, 2022)
Purpose Muscle pain can impair exercise performance but the mechanisms for this are unknown. This study examined the effects of muscle pain on neuromuscular fatigue during an endurance task. Methods On separate visits, twelve participants completed an isometric time-to-task failure (TTF) exercise of the right knee extensors at ~ 20% of maximum force following an intramuscular injection of isotonic saline (CTRL) or hypertonic saline (HYP) into the vastus lateralis. Measures of neuromuscular fatigue were taken before, during and after the TTF using transcranial magnetic stimulation (TMS) and peripheral nerve stimulation. Results The mean pain intensity was 57 ± 10 in HYP compared to 38 ± 18 in CTRL ( P < 0.001). TTF was reduced in HYP (4.36 ± 0.88 min) compared to CTRL (5.20 ± 0.39 min) ( P = 0.003). Maximum voluntary force was 12% lower at minute 1 ( P = 0.003) and 11% lower at minute 2 in HYP ( P = 0.013) compared to CTRL. Voluntary activation was 4% lower at minute 1 in HYP compared to CTRL ( P = 0.006) but not at any other time point (all P > 0.05). The TMS silent period was 9% longer at 100 s during the TTF in HYP compared to CTRL ( P = 0.026). Conclusion Muscle pain reduces exercise performance through the excacerbation of neuromuscular fatigue that is central in origin. This appears to be from inhibitory feedback from group III/IV nociceptors which acts to reduce central motor output.

Predators mitigate the destabilising effects of heatwaves on multitrophic stream communities - Samuel R. P.‐J. Ross; Jorge García Molinos; Atsushi Okuda; Jackson Johnstone; Keisuke Atsumi; Ryo Futamura; Maureen A. Williams; Yuichi Matsuoka; Jiro Uchida; Shoji Kumikawa; Hiroshi Sugiyama; Osamu Kishida; et al. (Global Change Biology, 2022)
Amidst the global extinction crisis, climate change will expose ecosystems to more frequent and intense extreme climatic events, such as heatwaves. Yet, whether predator species loss—a prevailing characteristic of the extinction crisis—will exacerbate the ecological consequences of extreme climatic events remains largely unknown. Here, we show that the loss of predator species can interact with heatwaves to moderate the compositional stability of ecosystems. We exposed multitrophic stream communities, with and without a dominant predator species, to realistic current and future heatwaves and found that heatwaves destabilised algal communities by homogenising them in space. However, this happened only when the predator was absent. Additional heatwave impacts on multiple aspects of stream communities, including changes to the structure of algal and macroinvertebrate communities, as well as total algal biomass and its temporal variability, were not apparent during heatwaves and emerged only after the heatwaves had passed. Taken together, our results suggest that the ecological consequences of heatwaves can amplify over time as their impacts propagate through biological interaction networks, but the presence of predators can help to buffer such impacts. These findings underscore the importance of conserving trophic structure, and highlight the potential for species extinctions to amplify the effects of climate change and extreme events.

Behavioral Interactions between a Native and an Invasive Fish Species in a Thermally Heterogeneous Experimental Chamber - Lindsy R. Ciepiela; Ryan M. Fitzpatrick; Samuel T. Lewis; Yoichiro Kanno (Fishes, 2021)
Mechanisms of the displacement of native fish by nonnative fish can include agonistic behaviors that push native fish species out of their preferred habitat, including their thermal optima. To examine these interactions, we built an experimental thermal preference chamber to evaluate: (1) the thermal preference of native, glacial relict northern redbelly dace Chrosomus eos; (2) if the thermal preference and movement changed in the presence of the invasive western mosquitofish Gambusia affinis; and (3) the direction of agonistic interactions. We hypothesized that G. affinis would express agonistic behavior toward C. eos, because G. affinis is widely recognized as an aggressive invader. Given the temperature range of the experimental chamber, i.e., 20–30 °C, C. eos selected an average of 24.3 °C as its thermal preference. After G. affinis’ introduction, the thermal preference of C. eos increased by 1.7 °C and the movement, given by distance (cm) travelled, increased by 21%. Contrary to our prediction, more agonistic interactions were observed in C. eos toward G. affinis. These results indicate that agonistic behavior of G. affinis toward native fish species may be species- and condition-specific, and may not always be the primary mechanism of native species’ displacement. Biological invasions are a global issue and altered thermal regimes are expected to continue. This study provided the novel approach using of a thermally heterogeneous thermal chamber to examine thermal preferences and aggressive interactions between a native and an invasive species. Future research should examine other life history traits that may be conveying the competitive advantage to G. affinis.

Photodynamic control of citrus crop diseases - Joana R. M. Ferreira; Isabel N. Sierra-Garcia; Samuel Guieu; Artur M. S. Silva; Raquel Nunes da Silva; Ângela Cunha (World Journal of Microbiology and Biotechnology, 2021)

Evidence That Methylphenidate Treatment Evokes Anxiety-Like Behavior Through Glucose Hypometabolism and Disruption of the Orbitofrontal Cortex Metabolic Networks - Felipe Schmitz; Josiane S. Silveira; Gianina T. Venturin; Samuel Greggio; Guilherme Schu; Eduardo R. Zimmer; Jaderson Costa Da Costa; Angela T. S. Wyse (Neurotoxicity Research, 2021)

A first genetic assessment of the newly introduced Isle Royale gray wolves (Canis lupus) - Samuel D. Hervey; Linda Y. Rutledge; Brent R. Patterson; Mark C. Romanski; John A. Vucetich; Jerrold L. Belant; Dean E. Beyer; Seth A. Moore; Kristin E. Brzeski (Conservation Genetics, 2021)

Correction to: Opportunistic spongivore fishes in a reef of Gulf of Mannar, India - Jonathan Samuel Emmett; K. Diraviya Raj; G. Mathews; R. L. Laju (Environmental Biology of Fishes, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

The codification of hazard and its impact on the hazard versus risk controversy - John E. Doe; Alan R. Boobis; Samuel M. Cohen; Vicki L. Dellarco; Penelope A. Fenner-Crisp; Angelo Moretto; Timothy P. Pastoor; Rita S. Schoeny; Jennifer G. Seed; Douglas C. Wolf (Archives of Toxicology, 2021)
The long running controversy about the relative merits of hazard-based versus risk-based approaches has been investigated. There are three levels of hazard codification: level 1 divides chemicals into dichotomous bands of hazardous and non-hazardous; level 2 divides chemicals into bands of hazard based on severity and/or potency; and level 3 places each chemical on a continuum of hazard based on severity and/or potency. Any system which imposes compartments onto a continuum will give rise to issues at the boundaries, especially with only two compartments. Level 1 schemes are only justifiable if there is no variation in severity, or potency or if there is no threshold. This is the assumption implicit in GHS/EU classification for carcinogenicity, reproductive toxicity and mutagenicity. However, this assumption has been challenged. Codification level 2 hazard assessments offer a range of choices and reduce the built-in conflict inherent in the level 1 process. Level 3 assessments allow a full range of choices between the extremes and reduce the built-in conflict even more. The underlying reason for the controversy between hazard and risk is the use of level 1 hazard codification schemes in situations where there are ranges of severity and potency which require the use of level 2 or level 3 hazard codification. There is not a major difference between level 2 and level 3 codification, and they can both be used to select appropriate risk management options. Existing level 1 codification schemes should be reviewed and developed into level 2 schemes where appropriate.

Overcoming the acquired resistance to gefitinib in lung cancer brain metastasis in vitro and in vivo - Zhongwei Liu; Neal Shah; Kent L. Marshall; Samuel A. Sprowls; Pushkar Saralkar; Afroz Mohammad; Kathryn E. Blethen; Tasneem A. Arsiwala; Ross Fladeland; Paul R. Lockman; Weimin Gao (Archives of Toxicology, 2021)

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

Coral annual growth band impregnated microplastics (Porites sp.): a first investigation report - S. Krishnakumar; S. Anbalagan; S. M. Hussain; R. Bharani; Prince Samuel Godson; S. Srinivasalu (Wetlands Ecology and Management, 2021)

Increasing signs of degradation of shallow water coral reefs due to repeated bleaching and spatial competition among benthic substrates - Bitopan Malakar; S. Venu; V. Deepak Samuel; K. R. Abhilash (Wetlands Ecology and Management, 2021)

Higher CSF Ferritin Heavy-Chain (Fth1) and Transferrin Predict Better Neurocognitive Performance in People with HIV - Harpreet Kaur; William S. Bush; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Stephanie M. Patton; James R. Connor; David C. Samuels; Donald R. Franklin; Todd Hulgan; Asha R. Kallianpur (Molecular Neurobiology, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Opportunistic spongivore fishes in a reef of Gulf of Mannar, India - Jonathan Samuel Emmett; K. Diraviya Raj; G. Mathews; R. L. Laju (Environmental Biology of Fishes, 2021)

Imaging-based indices of Neuropathology and gait speed decline in older adults: the atherosclerosis risk in communities study - Kevin J Sullivan; Radhikesh Ranadive; Dan Su; Blake R Neyland; Timothy M Hughes; Christina E Hugenschmidt; Samuel N Lockhart; Dean F Wong; Clifford R Jack; Rebecca F Gottesman; Thomas H Mosley; Michael E Griswold; et al. (Brain Imaging and Behavior, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Oceanographic influence on the early life-history stages of benthic invertebrates during the polar night - Kirstin Meyer-Kaiser; Hongju Chen; Xiaoshou Liu; Samuel R. Laney (Polar Biology, 2021)

Correction to: Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

The impact of indoor residual spraying on Plasmodium falciparum microsatellite variation in an area of high seasonal malaria transmission in Ghana, West Africa - Dionne C. Argyropoulos; Shazia Ruybal‐Pesántez; Samantha L. Deed; Abraham R. Oduro; Samuel K. Dadzie; Maxwell A. Appawu; Victor Asoala; Mercedes Pascual; Kwadwo A. Koram; Karen P. Day; Kathryn E. Tiedje (Molecular Ecology, 2021)
Here, we report the first population genetic study to examine the impact of indoor residual spraying (IRS) on Plasmodium falciparum in humans. This study was conducted in an area of high seasonal malaria transmission in Bongo District, Ghana. IRS was implemented during the dry season (November–May) in three consecutive years between 2013 and 2015 to reduce transmission and attempt to bottleneck the parasite population in humans towards lower diversity with greater linkage disequilibrium. The study was done against a background of widespread use of long‐lasting insecticidal nets, typical for contemporary malaria control in West Africa. Microsatellite genotyping with 10 loci was used to construct 392 P . falciparum multilocus infection haplotypes collected from two age‐stratified cross‐sectional surveys at the end of the wet seasons pre‐ and post‐IRS. Three‐rounds of IRS, under operational conditions, led to a >90% reduction in transmission intensity and a 35.7% reduction in the P . falciparum prevalence ( p H e : pre‐IRS = 0.79 vs. post‐IRS = 0.81, p = .048). Reduced relatedness of the parasite population ( p D = 0.0329 [95% CI: 0.0209 – 0.0473], p = .034) was identified. These data provide a genetic explanation for the resilience of P. falciparum to short‐term IRS programmes in high‐transmission settings in sub‐Saharan Africa.

Temporal dynamic and economic valuation of recreational fisheries of the lower Cuiabá River, Brazilian Pantanal - Brayan Allan R. Massaroli; Joisiane Mendes Araújo; Jean C. G. Ortega; André Valle Nunes; Lúcia Mateus; Samuel Elias Silva; Jerry Penha (Fisheries Management and Ecology, 2021)
Fisheries are the most common ecosystem service that fish provide to human populations, yet recreational fisheries are often overlooked when evaluating such services. Here, the socioeconomic profiles of fishers, the composition of their catches and catch per unit effort (CPUE) are described, to estimate the economic value of the recreational fishery on a stretch of the Cuiabá River in the Brazilian Pantanal. Questionnaires were used to obtain socioeconomic information and fishing yield from fishers for 2013 and 2014. Additionally, a census on the number of fishers and fishing platforms along the sampled region was conducted in 2018. This recreational fishery mostly involves middle class adult males, based mostly in the Cuiabá city metropolitan region. They invested, on average, US$41.1 (SD = US$16.5, median = $35.2) per fishing visit, catching around 19 fish species. Overall, mean CPUE from the recreational fishery was 42.20 fish/fisher.day (17.4 kg/fisher/day). Annual economic value of this recreational fishery was estimated at around US$1.8 million, which highlights the importance of this activity to the local economy. Greater environmental conservation efforts are recommend to ensure the long‐term viability of this ecosystem service.

Light and depth dependency of nitrogen fixation by the non‐photosynthetic, symbiotic cyanobacterium UCYN‐A - Mary R. Gradoville; Ana M. Cabello; Samuel T. Wilson; Kendra A. Turk‐Kubo; David M. Karl; Jonathan P. Zehr (Environmental Microbiology, 2021)
Summary The symbiotic cyanobacterium UCYN‐A is one of the most globally abundant marine dinitrogen (N 2 )‐fixers, but cultures have not been available and its biology and ecology are poorly understood. We used cultivation‐independent approaches to investigate how UCYN‐A single‐cell N 2 fixation rates (NFRs) and nifH gene expression vary as a function of depth and photoperiod. Twelve‐hour day/night incubations showed that UCYN‐A only fixed N 2 during the day. Experiments conducted using in situ arrays showed a light‐dependence of NFRs by the UCYN‐A symbiosis, with the highest rates in surface waters (5–45 m) and lower rates at depth (≥ 75 m). Analysis of NFRs versus in situ light intensity yielded a light saturation parameter ( I k ) for UCYN‐A of 44 μmol quanta m −2 s −1 . This is low compared with other marine diazotrophs, suggesting an ecological advantage for the UCYN‐A symbiosis under low‐light conditions. In contrast to cell‐specific NFRs, nifH gene‐specific expression levels did not vary with depth, indicating that light regulates N 2 fixation by UCYN‐A through processes other than transcription, likely including host–symbiont interactions. These results offer new insights into the physiology of the UCYN‐A symbiosis in the subtropical North Pacific Ocean and provide clues to the environmental drivers of its global distributions.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Spatial and temporal variability of deep convective clouds over the tropics using multi-year Megha - Tropiques – Sondeur Atmosphérique du Profil d’Humidité Intertropicale par Radiométrie (SAPHIR) observations - Sisma Samuel; Nizy Mathew; Manoj Kumar Mishra; R. Renju (International Journal of Remote Sensing, 2021)

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Fruit and seed traits of native and invasive plant species in Hawai‘i: implications for seed dispersal by non-native birds - Jinelle H. Sperry; Dylan O’Hearn; Donald R. Drake; Amy M. Hruska; Samuel B. Case; Jeferson Vizentin-Bugoni; Clint Arnett; Tim Chambers; Corey E. Tarwater (Biological Invasions, 2021)

Mathematical Modeling of Drying Kinetics and Quality Characteristics of Shrimps Dried under a Solar–LPG Hybrid Dryer - S. Murali; D. S. Aniesrani Delfiya; K. Sathish Kumar; Lekshmi R. G. Kumar; S. Ezhil Nilavan; P. R. Amulya; V. Soumya Krishnan; P. V. Alfiya; Manoj P. Samuel (Journal of Aquatic Food Product Technology, 2021)

Environmental change and infectious diseases in the Mediterranean region and the world: an interpretive dialectical analysis - Samuel R. Friedman (Euro-Mediterranean Journal for Environmental Integration, 2021)

An integrated approach to assess coastal vulnerability versus fisheries livelihood sustainability: Strategies for climate change adaptation in Sindhudurg, west coast of India - J. Joyson Joe Jeevamani; P. Priya; J. Amali Infantina; K. R. Abhilash; Durga Prasad Behera; V. Deepak Samuel; R. Soundararajan; R. Purvaja; R. Ramesh (Environment, Development and Sustainability, 2021)

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Intermittent post-exercise sauna bathing improves markers of exercise capacity in hot and temperate conditions in trained middle-distance runners - Nathalie V. Kirby; Samuel J. E. Lucas; Oliver J. Armstrong; Samuel R. Weaver; Rebekah A. I. Lucas (European Journal of Applied Physiology, 2021)
Purpose This study investigated whether intermittent post-exercise sauna bathing across three-weeks endurance training improves exercise heat tolerance and exercise performance markers in temperate conditions, compared to endurance training alone. The subsidiary aim was to determine whether exercise-heat tolerance would further improve following 7-Weeks post-exercise sauna bathing. Methods Twenty middle-distance runners (13 female; mean ± SD, age 20 ± 2 years, $$V$$ V O 2max 56.1 ± 8.7 ml kg −1 min −1 ) performed a running heat tolerance test (30-min, 9 km h −1 /2% gradient, 40 °C/40%RH; HTT) and temperate (18 °C) exercise tests (maximal aerobic capacity [ $$V$$ V O 2max ], speed at 4 mmol L −1 blood lactate concentration ([La − ]) before (Pre) and following three-weeks (3-Weeks) normal training (CON; n = 8) or normal training with 28 ± 2 min post-exercise sauna bathing (101–108 °C, 5–10%RH) 3 ± 1 times per week (SAUNA; n = 12). Changes from Pre to 3-Weeks were compared between-groups using an analysis of co-variance. Six SAUNA participants continued the intervention for 7 weeks, completing an additional HTT (7-Weeks; data compared using a one-way repeated-measures analysis of variance). Results During the HTT, SAUNA reduced peak rectal temperature ( T rec ; − 0.2 °C), skin temperature (− 0.8 °C), and heart rate (− 11 beats min −1 ) more than CON at 3-Weeks compared to Pre (all p < 0.05). SAUNA also improved $$V$$ V O 2max (+ 0.27 L −1 min −1 ; p = 0.02) and speed at 4 mmol L −1 [La − ] (+ 0.6 km h −1 ; p = 0.01) more than CON at 3-Weeks compared to Pre. Only peak T rec (− 0.1 °C; p = 0.03 decreased further from 3-Weeks to 7-Weeks in SAUNA (other physiological variables p > 0.05). Conclusions Three-weeks post-exercise sauna bathing is an effective and pragmatic method of heat acclimation, and an effective ergogenic aid. Extending the intervention to seven weeks only marginally improved T rec .

Immobilization of laccases and applications for the detection and remediation of pollutants: a review - Saptashwa Datta; R. Veena; Melvin S. Samuel; Ethiraj Selvarajan (Environmental Chemistry Letters, 2021)

Sensor Anchoring Improves the Correlation Between Intramuscular Pressure and Muscle Tension in a Rabbit Model - Shawn M. O’Connor; Kenton R. Kaufman; Samuel R. Ward; Richard L. Lieber (Annals of Biomedical Engineering, 2021)

Frenemy at the gate: Invasion by Pheidole megacephala facilitates a competitively subordinate plant ant in Kenya - Todd M. Palmer; Corinna Riginos; Patrick D. Milligan; Brandon R. Hays; Alejandro G. Pietrek; Nelly J. Maiyo; Samuel Mutisya; Benard Gituku; Simon Musila; Scott Carpenter; Jacob R. Goheen (Ecology, 2021)
Biological invasions can lead to the reassembly of communities and understanding and predicting the impacts of exotic species on community structure and functioning are a key challenge in ecology. We investigated the impact of a predatory species of invasive ant, Pheidole megacephala , on the structure and function of a foundational mutualism between Acacia drepanolobium and its associated acacia‐ant community in an East African savanna. Invasion by P. megacephala was associated with the extirpation of three extrafloral nectar‐dependent Crematogaster acacia ant species and strong increases in the abundance of a competitively subordinate and locally rare acacia ant species, Tetraponera penzigi , which does not depend on host plant nectar. Using a combination of long‐term monitoring of invasion dynamics, observations and experiments, we demonstrate that P. megacephala directly and indirectly facilitates T. penzigi by reducing the abundance of T. penzigi ’s competitors ( Crematogaster spp.), imposing recruitment limitation on these competitors, and generating a landscape of low‐reward host plants that favor colonization and establishment by the strongly dispersing T. penzigi . Seasonal variation in use of host plants by P. megacephala may further increase the persistence of T. penzigi colonies in invaded habitat. The persistence of the T. penzigi–A. drepanolobium symbiosis in invaded areas afforded host plants some protection against herbivory by elephants ( Loxodonta africana ), a key browser that reduces tree cover. However, elephant damage on T. penzigi ‐occupied trees was higher in invaded than in uninvaded areas, likely owing to reduced T. penzigi colony size in invaded habitats. Our results reveal the mechanisms underlying the disruption of this mutualism and suggest that P. megacephala invasion may drive long‐term declines in tree cover, despite the partial persistence of the ant–acacia symbiosis in invaded areas.

Improving Performance Criteria in the Water Resource Systems Based on Fuzzy Approach - Mohammad H. Golmohammadi; Hamid R. Safavi; Samuel Sandoval-Solis; Mahmood Fooladi (Water Resources Management, 2021)

Correction to: Widespread army ant aversion among East African jumping spiders (Salticidae) - Ximena J. Nelson; Samuel Aguilar-Arguello; Robert R. Jackson (Journal of Ethology, 2021)
The article Widespread army ant aversion among East African jumping spiders (Salticidae)

Assessment of Spatial and Temporal Soil Water Storage Using a Distributed Hydrological Model - Nayara P. V. Andrade; Marcelo R. Viola; Samuel Beskow; Tamara L. Caldeira; Li Guo; Carlos R. Mello (Water Resources Management, 2020)

Investigation of anomalous propagation conditions in Central and West African stations using high-resolution GPS radiosonde observations - Samuel Kaissassou; A Lenouo; R S Tanessong; Kamsu Tamo; A Vondou; W Pokam; J Kanko (Journal of Earth System Science, 2020)

Integrated metabolomics reveals altered lipid metabolism in adipose tissue in a model of extreme longevity - Justin Darcy; Yimin Fang; Samuel McFadden; Matthew D. Lynes; Luiz O. Leiria; Jonathan M. Dreyfuss; Valerie Bussburg; Vladimir Tolstikov; Bennett Greenwood; Niven R. Narain; Michael A. Kiebish; Andrzej Bartke; et al. (GeroScience, 2020)

Canine papillomavirus type 16 associated to squamous cell carcinoma in a dog: virological and pathological findings - Christian D. B. T. Alves; Matheus N. Weber; Lorena L. B. Guimarães; Samuel P. Cibulski; Flávio R. C. da Silva; Cíntia Daudt; Renata F. Budaszewski; Mariana S. Silva; Fabiana Q. Mayer; Ronaldo M. Bianchi; Claiton Ismael Schwertz; Carine R. Stefanello; et al. (Brazilian Journal of Microbiology, 2020)

Impact of Hot Water and Alkaline Pre-treatments in Cellulosic Ethanol Production from Banana Pseudostem - Isadora Ferreira da Silva; Luciana Reis Fontinelle Souto; Samuel R. A. Collins; Adam Elliston; José Humberto de Queiroz; Keith W. Waldron (BioEnergy Research, 2020)

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

Haplotype of RNASE 3 polymorphisms is associated with severe malaria in an Indian population - Benudhar Mukhi; Himanshu Gupta; Samuel C. Wassmer; Anupkumar R. Anvikar; Susanta Kumar Ghosh (Molecular Biology Reports, 2020)

dietr: an R package for calculating fractional trophic levels from quantitative and qualitative diet data - Samuel R. Borstein (Hydrobiologia, 2020)

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The effects of acute serotonin challenge on executive planning in patients with obsessive–compulsive disorder (OCD), their first-degree relatives, and healthy controls - Christine Lochner; Samuel R. Chamberlain; Martin Kidd; Lian Taljaard; Naomi A. Fineberg; Trevor W. Robbins; Dan J. Stein (Psychopharmacology, 2020)

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Caveolin-1 regulates medium spiny neuron structural and functional plasticity - Katherine R. Tonn Eisinger; Andrew D. Chapp; Samuel P. Swanson; Daniel Tam; Natalie M. Lopresti; Erin B. Larson; Mark J. Thomas; Lorene M. Lanier; Paul G. Mermelstein (Psychopharmacology, 2020)

Detection of rubber tree orchards infested by Meloidogyne exigua using vegetation indexes obtained from satellite images - Ernane M. Lemes; Túlio V. Machado; Luciana N. Gontijo; Samuel L. de Andrade; José L. R. Torres; Maria A. Santos; Lísias Coelho (New Forests, 2020)

Macrophage-Derived Extracellular Vesicles as Drug Delivery Systems for Triple Negative Breast Cancer (TNBC) Therapy - Matthew J. Haney; Yuling Zhao; Yeon S. Jin; Samuel M. Li; Juli R. Bago; Natalia L. Klyachko; Alexander V. Kabanov; Elena V. Batrakova (Journal of Neuroimmune Pharmacology, 2020)

Muscle pain induced by hypertonic saline in the knee extensors decreases single-limb isometric time to task failure - Samuel A. Smith; Dominic Micklewright; Samantha L. Winter; Alexis R. Mauger (European Journal of Applied Physiology, 2020)
Purpose Increased nociceptive activity and the experience of exercise-induced pain (EIP) may contribute to fatigue during endurance exercise. To investigate this, a pain model that produces pain similar to EIP and decouples its relationship to exercise intensity is required. This study (1) compared the quality of pain caused by a hypertonic saline injection into the vastus lateralis in resting and exercise conditions, and (2) investigated whether this pain contributes to changes in time to task failure. Methods On separate days, 18 participants completed a time to task failure at 20% maximal voluntary torque (MVT), a resting hypertonic saline intramuscular injection, and in a further three visits a time to task failure at 10% MVT following injection of isotonic saline, hypertonic saline or a control (no injection). Results In a subset of eligible participants ( n = 12), the hypertonic saline combined with 10% MVT produced a qualitative experience of pain (assessed by the McGill Pain Questionnaire) that felt similar to EIP. 10% MVT with hypertonic saline significantly elevated pain intensity in the first 20% of the time to task failure and caused a significantly ( P < 0.05) shorter time to task failure (448 ± 240 s) compared with the isotonic saline (605 ± 285 s) and control (514 ± 197 s) conditions. Conclusion These findings demonstrate that hypertonic saline increases the intensity of pain during exercise, which results in a faster occurrence of exercise-induced fatigue. These results provide important evidence supporting pain as a limiting factor in endurance performance.

Flavonoids against the Warburg phenotype—concepts of predictive, preventive and personalised medicine to cut the Gordian knot of cancer cell metabolism - Marek Samec; Alena Liskova; Lenka Koklesova; Samson Mathews Samuel; Kevin Zhai; Constanze Buhrmann; Elizabeth Varghese; Mariam Abotaleb; Tawar Qaradakhi; Anthony Zulli; Martin Kello; Jan Mojzis; et al. (EPMA Journal, 2020)
The Warburg effect is characterised by increased glucose uptake and lactate secretion in cancer cells resulting from metabolic transformation in tumour tissue. The corresponding molecular pathways switch from oxidative phosphorylation to aerobic glycolysis, due to changes in glucose degradation mechanisms known as the ‘Warburg reprogramming’ of cancer cells. Key glycolytic enzymes, glucose transporters and transcription factors involved in the Warburg transformation are frequently dysregulated during carcinogenesis considered as promising diagnostic and prognostic markers as well as treatment targets. Flavonoids are molecules with pleiotropic activities. The metabolism-regulating anticancer effects of flavonoids are broadly demonstrated in preclinical studies. Flavonoids modulate key pathways involved in the Warburg phenotype including but not limited to PKM2, HK2, GLUT1 and HIF-1. The corresponding molecular mechanisms and clinical relevance of ‘anti-Warburg’ effects of flavonoids are discussed in this review article. The most prominent examples are provided for the potential application of targeted ‘anti-Warburg’ measures in cancer management. Individualised profiling and patient stratification are presented as powerful tools for implementing targeted ‘anti-Warburg’ measures in the context of predictive, preventive and personalised medicine.

Phylogenomic analyses reveal a Palaeozoic radiation and support a freshwater origin for clitellate annelids - Christer Erséus; Bronwyn W. Williams; Kevin M. Horn; Kenneth M. Halanych; Scott R. Santos; Samuel W. James; Michel Creuzé des Châtelliers; Frank E. Anderson (Zoologica Scripta, 2020)
Clitellata is a major clade of Annelida comprising nearly all freshwater and terrestrial annelids as well as several marine species. We investigated clitellate phylogenetic relationships using transcriptomes sampled from 74 taxa (64 clitellates and 10 polychaetes), including multiple representatives of nearly all major clitellate higher taxa (Branchiobdellida, Capilloventridae, Crassiclitellata, Enchytraeidae, Haplotaxidae, Hirudinida, Lumbriculida, Moniligastridae, Naididae, Parvidrilidae, Phreodrilidae, Propappidae and Randiellidae). We used a number of filtered data matrices and phylogenetic analyses to examine the effects of data partitioning, missing data and compositional and branch‐length heterogeneity and used the resulting phylogenies for divergence time estimation and ancestral habitat reconstructions. All analyses and filtering methods produced a consistent, strongly supported topology in which (a) Enchytraeidae, Hirudinida, Hirudinea (here, Branchiobdellida plus Hirudinida), Lumbriculida, Lumbriculata (Lumbriculida plus Hirudinea), Phreodrilidae and Naididae are monophyletic, (b) a Parvidrilidae + Randiellidae clade is sister to the rest of Clitellata, (c) Phreodrilidae is sister to Naididae, (d) Haplotaxidae is non‐monophyletic, with some haplotaxids grouping with Crassiclitellata + Moniligastridae, (e) the Phreodrilidae + Naididae clade is sister to all other clitellates except Parvidrilidae + Randiellidae and Capilloventridae, and (f) Lumbriculata is sister to the Crassiclitellata + Moniligastridae + Haplotaxidae (in part) clade. Ancestral habitat reconstructions and divergence time analysis suggested that the most recent common ancestor of Clitellata lived in freshwater during the Devonian (419–359 million years ago) and that all major extant clitellate lineages arose over the next ~150 million years, with multiple lineages subsequently returning to marine habitats or invading land. This study provides a phylogenetic framework for further investigation of the geological, environmental and biotic forces and genomic changes that may have impacted clitellate evolution and enabled several major habitat transitions within this group.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Phylogeography of feral Monteiro pig in the Brazilian Pantanal Ecosystem - Elizabete C. Silva; Concepta McManus; Ubiratan Piovezan; Danielle A. Faria; Carla A. Souza; Alexandre R. Caetano; Samuel R. Paiva (Genetica, 2020)

A novel swine sex-linked marker and its application across different mammalian species - C. G. Lucas; A. M. Spate; M. S. Samuel; L. D. Spate; W. C. Warren; R. S. Prather; K. D. Wells (Transgenic Research, 2020)

Ichthyoplankton distribution and feeding habits of fish larvae at the inshore zone of northern Patagonia, Chile - Ainhoa Bernal; Leonardo R. Castro; Samuel Soto; Luis A. Cubillos (Marine Biodiversity, 2020)

Differential regulation of TREM2 and CSF1R in CNS macrophages in an SIV/macaque model of HIV CNS disease - Audrey C. Knight; Samuel A. Brill; Clarisse V. Solis; Morgan R. Richardson; Megan E. McCarron; Suzanne E. Queen; Charles C. Bailey; Joseph L. Mankowski (Journal of NeuroVirology, 2020)

Ischemic Neuroprotectant PKCε Restores Mitochondrial Glutamate Oxaloacetate Transaminase in the Neuronal NADH Shuttle after Ischemic Injury - Jing Xu; Nathalie Khoury; Charles W. Jackson; Iris Escobar; Samuel D. Stegelmann; Kunjan R. Dave; Miguel A. Perez-Pinzon (Translational Stroke Research, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Examining the roles of working memory and visual attention in multiple object tracking expertise - David J. Harris; Mark R. Wilson; Emily M. Crowe; Samuel J. Vine (Cognitive Processing, 2020)
When tracking multiple moving targets among visually similar distractors, human observers are capable of distributing attention over several spatial locations. It is unclear, however, whether capacity limitations or perceptual–cognitive abilities are responsible for the development of expertise in multiple object tracking. Across two experiments, we examined the role of working memory and visual attention in tracking expertise. In Experiment 1, individuals who regularly engaged in object tracking sports (soccer and rugby) displayed improved tracking performance, relative to non-tracking sports (swimming, rowing, running) ( p = 0.02, η p 2 = 0.163), but no differences in gaze strategy ( ps > 0.31). In Experiment 2, participants trained on an adaptive object tracking task showed improved tracking performance ( p = 0.005, d = 0.817), but no changes in gaze strategy ( ps > 0.07). They did, however, show significant improvement in a working memory transfer task ( p < 0.001, d = 0.970). These findings indicate that the development of tracking expertise is more closely linked to processing capacity limits than perceptual–cognitive strategies.

Widespread army ant aversion among East African jumping spiders (Salticidae) - Ximena J. Nelson; Samuel Aguilar-Arguello; Robert R. Jackson (Journal of Ethology, 2020)
Jumping spiders (Salticidae) typically prey on a variety of arthropods of similar size to themselves, but rarely on ants. Using 28 salticid species from East Africa, we first investigated vision-based aversion to ants by recording latency to enter a transparent sealed chamber flanked by chambers containing living army ants ( Dorylus sp.) or tsetse flies ( Glossina pallidipes ) of comparable size. For all species, entry latency was significantly longer when the stimuli were ants. In another experiment, we used dead ants and tsetse flies mounted in a life-like posture as stimuli; except for Goleba puella , a species with unusual retinal ultrastructure, we again found significantly longer entry latency when the stimuli were ants. Our findings imply that these salticids express an aversion specifically to ants even when restricted to using vision alone and, except for G. puella , even when relying on solely the static appearance of the insects. Having used salticids from laboratory cultures with no prior experience with ants, our findings are consistent with vision-based aversion to army ants being innate.

General DNA Methylation Patterns and Environmentally-Induced Differential Methylation in the Eastern Oyster (Crassostrea virginica) - Yaamini R. Venkataraman; Alan M. Downey-Wall; Justin Ries; Isaac Westfield; Samuel J. White; Steven B. Roberts; Kathleen E. Lotterhos (Frontiers in Marine Science, 2020)

The physiology of rapid ecological specialization: A look at the Midas cichlids - Michelle R. Gaither; Samuel Greaves; Pavithiran Amirthalingam (Molecular Ecology, 2020)
Understanding the process of speciation is a primary goal of evolutionary biology, yet the question of whether speciation can reach completion in the presence of gene flow remains controversial. For more than 50 years, the cichlids of Africa, and more recently those in South and Central America, have served as model systems for the study of speciation in nature. Cichlids are distinguished by their enormous species richness, their diversity of behavioural and trophic adaptations, and their rapid rate of divergence. In both Africa and South and Central America, the repeated interaction of geology, new founder events and adaptive evolution has created a series of natural experiments with speciation occurring both within and between waterbodies of differing ages. In the “From the Cover” paper in this issue of the Journal of Molecular Ecology , Raffini, Schneider, Franchini, Kautt and Meyer move beyond the question of which mechanisms drive speciation, and instead show that divergent morphologies and physiologies translate into adaptive traits. They investigate differences in physiology and gene expression profiles in a benthic/limnetic species pair of Midas cichlidsin a 24,000‐year‐old Nicaraguan crater lake. While recently diverged, these two species demonstrate significant ecological, but limited genetic differentiation. The authors find that the distinct morphotypes translate into relevant differences in swimming performance and metabolic rates that correspond to differential gene expression profiles. Hence, the authors take an integrative approach examining the impacts of morphological differences on performance and niche partitioning: an approach that can advance our understanding of the drivers of morphological and physiological divergence during speciation.

Populations of Populus angustifolia have evolved distinct metabolic profiles that influence their surrounding soil - Liam O. Mueller; Samuel R. Borstein; Eric D. Tague; Stephen P. Dearth; Hector F. Castro; Shawn R. Campagna; Joseph K. Bailey; Jennifer A. Schweitzer (Plant and Soil, 2020)

Effect of Additives to Improve Calcium-Based Sorbents in Semi-Dry Flue Gas Desulphurization - Ítalo W. L. França; Samuel J. M. Cartaxo; Moises Bastos-Neto; Luciana R. B. Gonçalves; Fabiano A. N. Fernandes (Emission Control Science and Technology, 2020)

Using aerial surveys and citizen science to create species distribution models for an imperiled grouse - Ashley M. Tanner; Evan P. Tanner; Monica Papeş; Samuel D. Fuhlendorf; R. Dwayne Elmore; Craig A. Davis (Biodiversity and Conservation, 2020)

Classical conditioning of antidepressant placebo effects in mice - Samuel R. Krimmel; Panos Zanos; Polymnia Georgiou; Luana Colloca; Todd D. Gould (Psychopharmacology, 2020)

Fire, rodent herbivory, and plant competition: implications for invasion and altered fire regimes in the Mojave Desert - Tara B. B. Bishop; Richard A. Gill; Brock R. McMillan; Samuel B. St. Clair (Oecologia, 2020)

Platelet Dynamics and Hemodynamics of Cerebral Aneurysms Treated with Flow-Diverting Stents - Laurel M. M. Marsh; Michael C. Barbour; Venkat Keshav Chivukula; Fanette Chassagne; Cory M. Kelly; Samuel H. Levy; Louis J. Kim; Michael R. Levitt; Alberto Aliseda (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Informing CITES Parties: Strengthening science‐based decision‐making when listing marine species - Kim Friedman; Matias Braccini; Matthew Bjerregaard‐Walsh; Ramón Bonfil; Corey J. A. Bradshaw; Stephen Brouwer; Ian Campbell; Rui Coelho; Enric Cortés; Wetjens Dimmlich; Michael G. Frisk; Irene Kingma; et al. (Fish and Fisheries, 2020)
International trade in vulnerable marine species is regulated once they are listed in CITES Appendices (the Convention on International Trade in Endangered Species of Wild Fauna and Flora). Parties to the Convention submit proposal(s) 150 days prior to the CITES Conference for voting on the inclusion of new species in Appendices I and II, making a case for why CITES listing criteria are met in each case. Before the vote, Parties receive advice from (a) the Food and Agriculture Organization of the United Nations, (b) the International Union for Conservation of Nature—TRAFFIC and (c) the CITES Secretariat, among others. This paper offers an expert review of listing processes, which are the subject of much debate in fishery and environment‐protection communities, looking at two specific cases: silky shark ( Carcharhinus falciformis, Carcharhinidae) and bigeye thresher shark ( Alopias superciliosus, Alopiidae). The reviewers determine that the evidence made available to voting Parties is substantial, but suffers from non‐standard presentation across assessments. The best available data are not always presented or described transparently in relation to CITES criteria. An extension of the assessment period, as well as the opportunity to refute evidence, has been suggested as ways to support more informed and effective decision‐making by CITES Parties, whose composition of delegations varies greatly in their experience of marine species management and trade. Experts welcomed a greater coherence of advice between fishery and non‐fishery sources in the long term, and proposed a range of suggested improvements for the delivery of information and advice to CITES Parties.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

Environmental friendly synthesis of zinc oxide nanoparticles and estimation of its larvicidal activity against Aedes aegypti - S. M. Roopan; R. S. Mathew; S. S. Mahesh; D. Titus; K. Aggarwal; N. Bhatia; K. I. Damodharan; K. Elumalai; J. J. Samuel (International Journal of Environmental Science and Technology, 2019)

Artificial seed aging reveals the invisible fraction: Implications for evolution experiments using the resurrection approach - Steven J. Franks; Michael R. Sekor; Samuel Davey; Arthur E. Weis (Evolutionary Ecology, 2019)

Respiratory and non-respiratory symptoms associated with pesticide management practices among farmers in Ghana’s most important vegetable hub - Reginald Quansah; John R. Bend; Frederick Ato Armah; Felix Bonney; Joshua Aseidu; David Oscar Yawson; Michael Osei Adu; Isaac Luginaah; David Kofi Essumang; Abukari Abdul-Rahaman; Samuel Cobbina; Samuel Iddi; et al. (Environmental Monitoring and Assessment, 2019)

Practical actions for applied systematic conservation planning - Emily A. Botts; Genevieve Pence; Stephen Holness; Kerry Sink; Andrew Skowno; Amanda Driver; Linda R. Harris; Philip Desmet; Boyd Escott; Mervyn Lötter; Jeanne Nel; Tammy Smith; et al. (Conservation Biology, 2019)
Systematic conservation planning is intended to inform spatially explicit decision making. Doing so requires that it be integrated into complex regulatory and governance processes, and there are limited instances where this has been achieved effectively. South Africa is a global leader in the application of conservation plans, the outputs of which are widely used for spatial planning and decision making in many spheres of government. We aimed to determine how conservation planning in the country progressed from theory to implementation, and to identify practical actions that enabled this transition, by assessing temporal trends in the characteristics of conservation plans (1990–2017, n = 94). Since 2010 conservation planning has entered an operational period characterized by government leadership of plans, administrative rather than ecological planning domains, decreasing size of planning units, increasing emphasis on end‐user products, and scheduled revision of plans. Key actions that enabled this progression include transitioning leadership of plans from scientists to practitioners, building capacity within implementing agencies, creating opportunities to integrate plans in legislative processes, establishing a strong community of practice, adopting implementation‐focused methods, and balancing standardization with innovation. Learning from this model will allow other countries, particularly those with a similar megadiverse, developing context, to operationalize conservation planning into spatial planning and decision making.

Virtually the same? How impaired sensory information in virtual reality may disrupt vision for action - David J. Harris; Gavin Buckingham; Mark R. Wilson; Samuel J. Vine (Experimental Brain Research, 2019)

The time-course of thermoregulatory responses during treadmill running is associated with running duration-dependent hypothalamic neuronal activation in rats - Paulo M. A. Lima; Helton O. Campos; Daniela R. C. Fóscolo; Raphael E. Szawka; Samuel P. Wanner; Cândido C. Coimbra (Brain Structure and Function, 2019)

Origin and age of The Hillocks and implications for post‐glacial landscape development in the upper Lake Wakatipu catchment, New Zealand - Samuel T. McColl; Simon J. Cook; Timothy Stahl; Timothy R. H. Davies (Journal of Quaternary Science, 2019)
Ambiguous landscape histories can arise from equivocal or incomplete geomorphological, sedimentological or geochronological evidence. In this study, we apply quantitative analyses to robustly assess the origin and age of a field of rounded mounds, known as ‘The Hillocks’. Using clast analysis, the sediment is shown to be consistent with a landslide origin but inconsistent with other glacial sediments in the region. Cosmogenic 10 Be exposure age dating suggests The Hillocks formed ~8 ka. Ground‐penetrating radar reveals that the deposit rests upon deltaic foreset beds; combined with topographical data, we calculate a deposit volume of ~15–27 M m 3 , consistent with the estimated volume of the proposed source area. Overall, our data support a rock avalanche origin, indicating that by 8 ka the valley was ice‐free at The Hillocks’ location, and the level of Lake Wakatipu was lower than 340 m asl by this time. The Dart River delta shoreline was situated somewhere between The Hillocks and the present day shoreline at that time, and has prograded at a maximum average rate of 1 m a −1 since ~8 ka. These findings are significant given the lack of landforms by which to constrain glacial or post‐glacial landscape histories in this region of New Zealand. Copyright © 2019 John Wiley & Sons, Ltd.

Ecological memory of daily carbon exchange across the globe and its importance in drylands - Yao Liu; Christopher R. Schwalm; Kimberly E. Samuels‐Crow; Kiona Ogle (Ecology Letters, 2019)
How do antecedent (past) conditions influence land‐carbon dynamics after those conditions no longer persist? In particular, quantifying such memory effects associated with the influence of past environmental (exogenous) and biological (endogenous) conditions is crucial for understanding and predicting the carbon cycle. Here we show, using data from 42 eddy covariance sites across six major biomes, that ecological memory—decomposed into environmental and biological memory components—of daily net carbon exchange (NEE) is critical for understanding the land‐carbon metabolism, especially in drylands for which memory explains ~ 32% of the variation in NEE. The strong environmental memory in drylands was primarily driven by short‐ and long‐term moisture status. Moreover, the strength of environmental memory scales with increasing water stress. This universal scaling relationship, emerging within and among major biomes, suggests a potential adaptive response to water limitation. Our findings underscore the necessity of considering ecological memory in experiments, observations and modelling.

Consumption of Atlantic Salmon Smolt by Striped Bass: A Review of the Predator-Prey Encounter Literature and Implications for the Design of Effective Sampling Strategies - Samuel Andrews; Sarah Hirtle; Tommi Linnansaari; R. Curry (Fishes, 2019)
The native striped bass (Morone saxatilis) population of the Miramichi River, New Brunswick is undergoing an unprecedented recovery while Atlantic salmon (Salmo salar) numbers within that system continue to decline. Atlantic salmon smolt depart from the Miramichi system during the striped bass spawning period and it is hypothesized that elevated striped bass abundances will increase encounter rates and predation on smolts. We summarize all available striped bass diet studies occurring within the native range of Atlantic salmon and present a review of the feeding behavior and diet preferences of striped bass before, during, and after their spawning period. The key studies vary in methodologies and interpretability. We present a standardized approach for assessing striped bass predation threats and smolt vulnerability and thus an improved understanding of the species interactions to guide future management in the Miramichi River.

Physiological host range of Trissolcus japonicus in relation to Halyomorpha halys and other pentatomids from California - Jesús R. Lara; Charles H. Pickett; Matthew T. Kamiyama; Samuel Figueroa; Mariana Romo; Christopher Cabanas; Vanessa Bazurto; Vincent Strode; Kristen Briseno; Mike Lewis; Joshua Oliva; Gabriel Hernandez; et al. (BioControl, 2019)

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

The effects of mitragynine and morphine on schedule-controlled responding and antinociception in rats - Takato Hiranita; Francisco Leon; Jasmine S. Felix; Luis F. Restrepo; Morgan E. Reeves; Anna E. Pennington; Samuel Obeng; Bonnie A. Avery; Christopher R. McCurdy; Lance R. McMahon; Jenny L. Wilkerson (Psychopharmacology, 2019)

Impacts of Air-Fuel Stratification in ACI Combustion on Particulate Matter and Gaseous Emissions - Melanie Moses-DeBusk; Scott J. Curran; Samuel A. Lewis; R. Maggie Connatser; John M. E. Storey (Emission Control Science and Technology, 2019)

It’s about time: A synthesis of changing phenology in the Gulf of Maine ecosystem - Michelle D. Staudinger; Katherine E. Mills; Karen Stamieszkin; Nicholas R. Record; Christine A. Hudak; Andrew Allyn; Antony Diamond; Kevin D. Friedland; Walt Golet; Meghan Elisabeth Henderson; Christina M. Hernandez; Thomas G. Huntington; et al. (Fisheries Oceanography, 2019)
The timing of recurring biological and seasonal environmental events is changing on a global scale relative to temperature and other climate drivers. This study considers the Gulf of Maine ecosystem, a region of high social and ecological importance in the Northwest Atlantic Ocean and synthesizes current knowledge of (a) key seasonal processes, patterns, and events; (b) direct evidence for shifts in timing; (c) implications of phenological responses for linked ecological‐human systems; and (d) potential phenology‐focused adaptation strategies and actions. Twenty studies demonstrated shifts in timing of regional marine organisms and seasonal environmental events. The most common response was earlier timing, observed in spring onset, spring and winter hydrology, zooplankton abundance, occurrence of several larval fishes, and diadromous fish migrations. Later timing was documented for fall onset, reproduction and fledging in Atlantic puffins, spring and fall phytoplankton blooms, and occurrence of additional larval fishes. Changes in event duration generally increased and were detected in zooplankton peak abundance, early life history periods of macro‐invertebrates, and lobster fishery landings. Reduced duration was observed in winter–spring ice‐affected stream flows. Two studies projected phenological changes, both finding diapause duration would decrease in zooplankton under future climate scenarios. Phenological responses were species‐specific and varied depending on the environmental driver, spatial, and temporal scales evaluated. Overall, a wide range of baseline phenology and relevant modeling studies exist, yet surprisingly few document long‐term shifts. Results reveal a need for increased emphasis on phenological shifts in the Gulf of Maine and identify opportunities for future research and consideration of phenological changes in adaptation efforts.

Establishing operant conflict tests for the translational study of anxiety in mice - Sara Oberrauch; Hannes Sigrist; Eva Sautter; Samuel Gerster; Dominik R. Bach; Christopher R. Pryce (Psychopharmacology, 2019)

Isotope fractionation during root water uptake by Acacia caven is enhanced by arbuscular mycorrhizas - María Poca; Olivia Coomans; Carlos Urcelay; Sebastián R. Zeballos; Samuel Bodé; Pascal Boeckx (Plant and Soil, 2019)

After Childhood Cancer: a Qualitative Study of Family Physician, Parent/Guardian, and Survivor Information Needs and Perspectives on Long-Term Follow-up and Survivorship Care Plans - Melanie R. Keats; Kelsey Shea; Louise Parker; Samuel A. Stewart; Annette Flanders; Mark Bernstein (Journal of Cancer Education, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Resveratrol Preconditioning Induces Genomic and Metabolic Adaptations within the Long-Term Window of Cerebral Ischemic Tolerance Leading to Bioenergetic Efficiency - Nathalie Khoury; Jing Xu; Samuel D. Stegelmann; Charles W. Jackson; Kevin B. Koronowski; Kunjan R. Dave; Juan I. Young; Miguel A. Perez-Pinzon (Molecular Neurobiology, 2019)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Iron Deficiency Reduces Synapse Formation in the Drosophila Clock Circuit - Samuel S. Rudisill; Bradley R. Martin; Kevin M. Mankowski; Charles R. Tessier (Biological Trace Element Research, 2019)

Impact of long-term seaweed farming on water quality: a case study from Palk Bay, India - K. R. Abhilash; R. Sankar; R. Purvaja; Samuel V. Deepak; C. R. Sreeraj; P. Krishnan; V. Sekar; Amit K. Biswas; G. Kumarapandiyan; R. Ramesh (Journal of Coastal Conservation, 2019)

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Introduction to the Special Issue on the Utility of Transdiagnostic Approaches for Developing Novel Interventions for Substance and Behavioural Addictions - Murat Yücel; Leonardo F. Fontenelle; Samuel R. Chamberlain (Neuropsychology Review, 2019)

Efficacy of Pharmacological Interventions in Targeting Decision-Making Impairments across Substance and Behavioral Addictions - Samuel R. Chamberlain; Jon E. Grant (Neuropsychology Review, 2019)

Feedbacks Between Nutrient Enrichment and Geomorphology Alter Bottom-Up Control on Food Webs - James A. Nelson; David Samuel Johnson; Linda A. Deegan; Amanda C. Spivak; Nathalie R. Sommer (Ecosystems, 2019)

Phylogeography and post‐glacial dynamics in the clonal‐sexual orchid Cypripedium calceolus L. - Roberta Gargiulo; Samuel Pironon; Ekaterina Zheleznaya; Michele D. Sanchez; Zoltan R. Balázs; Dorina Podar; Timothy Wilkinson; Anne Jäkäläniemi; Tiiu Kull; Henry Väre; Michael F. Fay (Journal of Biogeography, 2019)
Aim We investigated the phylogeographical history of a clonal‐sexual orchid, to test the hypothesis that current patterns of genetic diversity and differentiation retain the traces of climatic fluctuations and of the species reproductive system. Location Europe, Siberia and Russian Far East. Taxon Cypripedium calceolus L. (Orchidaceae). Methods Samples (>900, from 56 locations) were genotyped at 11 nuclear microsatellite loci and plastid sequences were obtained for a subset of them. Analysis of genetic structure and approximate Bayesian computations were performed. Species distribution modelling was used to explore the effects of past climatic fluctuations on the species range. Results Analysis of genetic diversity reveals high heterozygosity and allele diversity, with no geographical trend. Three genetic clusters are identified with extant gene pools derived from ancestral demes in glacial refugia. Siberian populations exhibit different plastid haplotypes, supporting an early divergence for the Asian gene pool. Demographic results based on genetic data are compatible with an admixture event explaining differentiation in Estonia and Romania and they are consistent with past climatic dynamics inferred through species distribution modelling. Current population differentiation does not follow isolation by distance model and is compatible with a model of isolation by colonization. Main conclusions The genetic differentiation observed today in C. calceolus preserves the signature of climatic fluctuations in the historical distribution range of the species. Our findings support the central role of clonal reproduction in the reducing loss of diversity through genetic drift. The dynamics of the clonal‐sexual reproduction are responsible for the persistence of ancestral variation and stability during glacial periods and post‐glacial expansion.

Occurrence of aflatoxins in rice and in cassava (Manihot esculenta) products (meal, bread) produced in Guyana - Donna M. Morrison; David R. Ledoux; Lambert F. B. Chester; Coretta A. N. Samuels (Mycotoxin Research, 2019)

Resistance to coronavirus infection in amino peptidase N-deficient pigs - Kristin M. Whitworth; Raymond R. R. Rowland; Vlad Petrovan; Maureen Sheahan; Ada G. Cino-Ozuna; Ying Fang; Richard Hesse; Alan Mileham; Melissa S. Samuel; Kevin D. Wells; Randall S. Prather (Transgenic Research, 2019)

Bovine papillomavirus 24: a novel member of the genus Xipapillomavirus detected in the Amazon region - Cíntia Daudt; Flavio R. C. da Silva; Samuel P. Cibulski; André F. Streck; Rebecca E. Laurie; John S. Munday; Cláudio W. Canal (Archives of Virology, 2019)

A Rapidly Expanding Macroalga Acts as a Foundational Species Providing Trophic Support and Habitat in the South Pacific - Sarah Joy Bittick; Rachel J. Clausing; Caitlin R. Fong; Samuel R. Scoma; Peggy Fong (Ecosystems, 2019)

Coupled long‐term limnological data and sedimentary records reveal new control on water quality in a eutrophic lake - Jake R. Walsh; Jessica R. Corman; Samuel E. Munoz (Limnology and Oceanography, 2019)
Human impacts on freshwater ecosystems are pervasive, but the short and discontinuous nature of most datasets limits our ability to understand the controls on water quality and effectively manage freshwater resources. We examine change in Lake Mendota (Madison, Wisconsin) over the last two centuries by pairing analyses of a sedimentary archive with the site's > 100 yr limnological record. We show that eutrophication of the lake, evident as an abrupt shift in sediment composition, began in the late 19 th century following the intensification of urban and agricultural land use in the watershed. Efforts to address deterioration of lake water quality, including the removal of point‐source pollutants and biomanipulation, have had a measurable influence on sediment composition and water clarity. Since the early 1980s, quasi‐seasonal cycles of phytoplankton blooms have induced calcite precipitation, leaving distinct laminations in the sedimentary record. These “whiting events” evidently did not accumulate in lake sediments until the late 20 th century, indicating that efforts to remediate water quality have shifted the lake to a new ecosystem state. Calcite whitings can improve water quality in eutrophic lakes by coprecipitation with phosphate, increasing phosphorus (P) burial in lake sediments. Using long‐term limnological records, we report negative correlations between calcite saturation indices and P in lake surface waters and show that calcite whitings could partially explain recent P decline in Lake Mendota surface waters. Our study reveals a previously uncharacterized potential control on water quality in this eutrophic lake and demonstrates the benefit of coupling long‐term limnological data with sedimentary records.

No apparent negative tagging effects after 13 years at liberty for lemon shark, Negaprion brevirostris implanted with acoustic transmitter - Matthew J. Smukall; Steven T. Kessel; Bryan R. Franks; Kevin A. Feldheim; Tristan L. Guttridge; Samuel H. Gruber (Journal of Fish Biology, 2019)
An intact and uncompromised internal acoustic transmitter was non‐lethally recovered from a lemon shark Negaprion brevirostris , after 13 years at liberty. The shark, first tagged at an estimated age of 2 years old near South Bimini, Bahamas in 2004, was recaptured in 2017 with a total length of 264 cm. The tagged shark displayed typical growth rate, pregnancy, natal homing and pupping behaviour of other individuals in this population. This observation provides important evidence regarding the effects from long‐term retention of implanted acoustic transmitters in a carcharhinid shark.

Impact of Future Climate Change on Water Temperature and Thermal Habitat for Keystone Fishes in the Lower Saint John River, Canada - Stephen J. Dugdale; R. Allen Curry; André St-Hilaire; Samuel N. Andrews (Water Resources Management, 2018)

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)

Num1 versus NuMA: insights from two functionally homologous proteins - Samuel R. Greenberg; Weimin Tan; Wei-Lih Lee (Biophysical Reviews, 2018)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

Demographic inference in barn swallows using whole‐genome data shows signal for bottleneck and subspecies differentiation during the Holocene - Chris C. R. Smith; Samuel M. Flaxman; Elizabeth S. C. Scordato; Nolan C. Kane; Amanda K. Hund; Basma M. Sheta; Rebecca J. Safran (Molecular Ecology, 2018)
Accounting for historical demographic features is vital for many types of evolutionary inferences, including the estimation of divergence times between closely related populations. In barn swallow, Hirundo rustica , inferring historical population sizes and subspecies divergence times can shed light on the recent co‐evolution of this species with humans. Pairwise sequentially Markovian coalescent uncovered population growth beginning on the order of one million years ago—which may reflect the radiation of the broader Hirundo genus—and a more recent population decline. Additionally, we used approximate Bayesian computation to evaluate hypotheses about recent timescale barn swallow demography, including population growth due to human commensalism, and a potential founder event associated with the onset of nesting on human structures. We found signal for a bottleneck event approximately 7,700 years ago, near the time that humans began building substantial structures, although there was considerable uncertainty associated with this estimate. Subspecies differentiation and subsequent growth occurred after the bottleneck in the best‐supported model, an order of magnitude more recently than previous estimates in this system. We also compared results obtained from whole‐genome sequencing versus reduced representation sequencing, finding many similar results despite substantial allelic dropout in the reduced representation data, which may have affected estimates of some parameters. This study presents the first genetic evidence of a potential barn swallow founder effect and subspecies divergence coinciding with the Holocene, which is an important step in analysing the biogeographical history of a well‐known human commensal species.

Dichomitus squalens partially tailors its molecular responses to the composition of solid wood - Paul Daly; Sara Casado López; Mao Peng; Christopher S. Lancefield; Samuel O. Purvine; Young‐Mo Kim; Erika M. Zink; Alice Dohnalkova; Vasanth R. Singan; Anna Lipzen; David Dilworth; Mei Wang; et al. (Environmental Microbiology, 2018)
Summary White‐rot fungi, such as Dichomitus squalens , degrade all wood components and inhabit mixed‐wood forests containing both soft‐ and hardwood species. In this study, we evaluated how D. squalens responded to the compositional differences in softwood [guaiacyl (G) lignin and higher mannan content] and hardwood [syringyl/guaiacyl (S/G) lignin and higher xylan content] using semi‐natural solid cultures. Spruce (softwood) and birch (hardwood) sticks were degraded by D. squalens as measured by oxidation of the lignins using 2D‐NMR. The fungal response as measured by transcriptomics, proteomics and enzyme activities showed a partial tailoring to wood composition. Mannanolytic transcripts and proteins were more abundant in spruce cultures, while a proportionally higher xylanolytic activity was detected in birch cultures. Both wood types induced manganese peroxidases to a much higher level than laccases, but higher transcript and protein levels of the manganese peroxidases were observed on the G‐lignin rich spruce. Overall, the molecular responses demonstrated a stronger adaptation to the spruce rather than birch composition, possibly because D. squalens is mainly found degrading softwoods in nature, which supports the ability of the solid wood cultures to reflect the natural environment.

Nitrogen Limitation of the Summer Phytoplankton and Heterotrophic Prokaryote Communities in the Chukchi Sea - Matthew M. Mills; Zachary W. Brown; Samuel R. Laney; Eva Ortega-Retuerta; Kate E. Lowry; Gert L. van Dijken; Kevin R. Arrigo (Frontiers in Marine Science, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Stable isotope ecology of black rhinos (Diceros bicornis) in Kenya - Thure E. Cerling; Samuel A. Andanje; Francis Gakuya; John M. Kariuki; Linus Kariuki; Jackson W. Kingoo; Cedric Khayale; Isaac Lekolool; Anthony N. Macharia; Christopher R. Anderson; Diego P. Fernandez; Lihai Hu; et al. (Oecologia, 2018)

Misidentification of istiophorid billfishes by fisheries observers raises uncertainty over stock status - Samuel M. Williams; Julian G. Pepperell; Michael Bennett; Jennifer R. Ovenden (Journal of Fish Biology, 2018)
We investigated whether commercially landed black marlin Istiompax indica were being misidentified by fisheries observers operating throughout the Pacific Ocean. Of 83 samples reported by observers as I. indica , 77% were genetically identified to be blue marlin Makaira nigricans and 2% to be striped marlin Kajikia audax . The high rate of misidentification by observers places considerable uncertainty over historic catch ratios of Indo‐Pacific marlin and stock assessments relying on the validity of these data.

Transgenic up-regulation of Claudin-6 decreases fine diesel particulate matter (DPM)-induced pulmonary inflammation - Joshua B. Lewis; Jared S. Bodine; Jason R. Gassman; Samuel Arce Muñoz; Dallin C. Milner; Todd M. Dunaway; Kaleb M. Egbert; Troy D. Monson; Dallin S. Broberg; Juan A. Arroyo; Paul R. Reynolds (Environmental Science and Pollution Research, 2018)

Cortical thickness abnormalities in trichotillomania: international multi-site analysis - Samuel R. Chamberlain; Michael Harries; Sarah A. Redden; Nancy J. Keuthen; Dan J. Stein; Christine Lochner; Jon E. Grant (Brain Imaging and Behavior, 2018)

Ice algal communities in the Chukchi and Beaufort Seas in spring and early summer: Composition, distribution, and coupling with phytoplankton assemblages - Virginia Selz; Samuel Laney; Alexandra E. Arnsten; Kate M. Lewis; Kate E. Lowry; Hannah L. Joy‐Warren; Matthew M. Mills; Gert L. van Dijken; Kevin R. Arrigo (Limnology and Oceanography, 2018)
To understand the controls on distributions of ice algal communities in spring and the role of ice algae in under‐ice bloom development through possible seeding, we sampled the ice and water column in the Chukchi and Beaufort Seas over spring and summer. Field observations showed that high springtime concentrations of bottom ice algal communities were released from the ice into the water column by summer. Furthermore, during our spring sampling, bottom ice algal concentrations were highly variable. Declines in spring ice algal biomass and physiological state were correlated with ice melt, rather than light or nutrient availability. Nonparametric multivariate data analysis of the seasonal succession of phytoplankton and ice algal community composition illustrated that the loss of algae from the sea ice temporarily elevated water column chlorophyll a (Chl a ) levels, as ice‐derived taxa dominated the phytoplankton biomass. Model simulations, constrained by field observations from this study, further suggested that seeding by ice algae was brief and alone could not account for the phytoplankton biomass concentrations exceeding 2 mg Chl a m −3 observed in our study. Ice algal sloughing from the sea ice to the water column contributes biomass to the phytoplankton community. However, this signal of ice‐derived taxa is brief and non‐ice derived taxa dominate phytoplankton blooms later in the spring and summer.

Temporal heterogeneity increases with spatial heterogeneity in ecological communities - Scott L. Collins; Meghan L. Avolio; Corinna Gries; Lauren M. Hallett; Sally E. Koerner; Kimberly J. La Pierre; Andrew L. Rypel; Eric R. Sokol; Samuel B. Fey; Dan F. B. Flynn; Sydney K. Jones; Laura M. Ladwig; et al. (Ecology, 2018)
Heterogeneity is increasingly recognized as a foundational characteristic of ecological systems. Under global change, understanding temporal community heterogeneity is necessary for predicting the stability of ecosystem functions and services. Indeed, spatial heterogeneity is commonly used in alternative stable state theory as a predictor of temporal heterogeneity and therefore an early indicator of regime shifts. To evaluate whether spatial heterogeneity in species composition is predictive of temporal heterogeneity in ecological communities, we analyzed 68 community data sets spanning freshwater and terrestrial systems where measures of species abundance were replicated over space and time. Of the 68 data sets, 55 (81%) had a weak to strongly positive relationship between spatial and temporal heterogeneity, while in the remaining communities the relationship was weak to strongly negative (19%). Based on a mixed model analysis, we found a significant but weak overall positive relationship between spatial and temporal heterogeneity across all data sets combined, and within aquatic and terrestrial data sets separately. In addition, lifespan and successional stage were negatively and positively related to temporal heterogeneity, respectively. We conclude that spatial heterogeneity may be a predictor of temporal heterogeneity in ecological communities, and that this relationship may be a general property of many terrestrial and aquatic communities.

Cortical Bilateral Adaptations in Rats Submitted to Focal Cerebral Ischemia: Emphasis on Glial Metabolism - Yasmine Nonose; Pedro E. Gewehr; Roberto F. Almeida; Jussemara S. da Silva; Bruna Bellaver; Leo A. M. Martins; Eduardo R. Zimmer; Samuel Greggio; Gianina T. Venturin; Jaderson C. Da Costa; André Quincozes-Santos; Luc Pellerin; et al. (Molecular Neurobiology, 2018)

Circulating extracellular vesicles in the aging process: impact of aerobic exercise - Karine Bertoldi; Laura Reck Cechinel; Bruna Schallenberger; Giana Blume Corssac; Samuel Davies; Irene Clemes Külkamp Guerreiro; Adriane Belló-Klein; Alex Sander R. Araujo; Ionara Rodrigues Siqueira (Molecular and Cellular Biochemistry, 2018)

Integrative taxonomy of the neotropical genus Omalonyx (Elasmognatha: Succineidae) - Teofânia H. D. A. Vidigal; Daniel Coscarelli; Hugo Paixão; Samuel Bernardes; Lângia C. Montresor; Almir R. Pepato (Zoologica Scripta, 2018)
The genus Omalonyx d'Orbigny, 1837, includes neotropical semi‐aquatic succineid slugs and comprises six recognized species to date. Field surveys across continental South America recovered five of the six recognized species. According to the morphological characters traditionally included in Omalonyx descriptions, the specimens were tentatively identified as O. matheroni , O. pattersonae , O. convexus , O. geayi and O. unguis . Employing sequences of mitochondrial cytochrome oxidase I (COI) alone or combined with the nuclear second internal transcribed spacer (ITS2) in discovery methods of species delimitation (GMYC and STACEY) led to species delimitation hypotheses that, except for unambiguously supporting O. convexus , have no correspondence to morphologically based assignments. To choose the delimitation model that best fit our data, the hypotheses recovered by GMYC, STACEY and morphology and created by merging species recovered by those methods had their marginal likelihood estimated and compared using the Bayes factors. The best‐supported hypothesis distinguished two species besides O. convexus: one widespread over most of South America and the other restricted to Rio de Janeiro State, Brazil. Furthermore, the pattern of genetic structuring supports pathways connecting the Amazonian and Atlantic forests. This pattern is similar to that observed in terrestrial taxa (e.g., forest‐dwelling small mammals) and is different from the pattern for fully aquatic taxa.

Making ecological models adequate - Wayne M. Getz; Charles R. Marshall; Colin J. Carlson; Luca Giuggioli; Sadie J. Ryan; Stephanie S. Romañach; Carl Boettiger; Samuel D. Chamberlain; Laurel Larsen; Paolo D’Odorico; David O’Sullivan (Ecology Letters, 2018)
Critical evaluation of the adequacy of ecological models is urgently needed to enhance their utility in developing theory and enabling environmental managers and policymakers to make informed decisions. Poorly supported management can have detrimental, costly or irreversible impacts on the environment and society. Here, we examine common issues in ecological modelling and suggest criteria for improving modelling frameworks. An appropriate level of process description is crucial to constructing the best possible model, given the available data and understanding of ecological structures. Model details unsupported by data typically lead to over parameterisation and poor model performance. Conversely, a lack of mechanistic details may limit a model's ability to predict ecological systems’ responses to management. Ecological studies that employ models should follow a set of model adequacy assessment protocols that include: asking a series of critical questions regarding state and control variable selection, the determinacy of data, and the sensitivity and validity of analyses. We also need to improve model elaboration, refinement and coarse graining procedures to better understand the relevancy and adequacy of our models and the role they play in advancing theory, improving hind and forecasting, and enabling problem solving and management.

Variation and drivers of airflow patterns associated with olfactory concealment and habitat selection - Dillon T. Fogarty; R. Dwayne Elmore; Samuel D. Fuhlendorf; Scott R. Loss (Ecology, 2018)
Many terrestrial predators rely on olfaction to detect prey; therefore, prey should select habitat to reduce detectability of their odor cues. One way prey can potentially conceal their odor is by selecting locations with high turbulence and/or updrafts, conditions that disperse odor plumes and make odor sources difficult to locate. However, it is unclear how these conditions vary among vegetation cover types and which vegetative features drive them. We assessed variation and drivers of variables hypothesized to influence olfactory concealment (turbulence intensity and airflow slope) and experimentally evaluated whether these variables indeed influence predator detection of simulated prey. Specifically, we compared vegetation patch‐scale values of turbulence intensity and airflow slope among grassland, shrubland, and forest and assessed relationships among these airflow variables and local‐scale vegetative features within each vegetation type. Additionally, we experimentally investigated the importance of turbulence intensity, airflow slope, and visual concealment for predicting predator detection of scented quail eggs. In all vegetation types, we documented high variability in airflow conditions. At the patch scale, turbulence intensity was greater in shrubland and grassland than in forest, and updrafts were most common in shrubland whereas downdrafts were most common in grassland. Grassland was the only vegetation type with strong relationships among turbulence intensity and local vegetation features; both visual concealment and vegetation height were positively related to turbulence intensity. Additionally, persistence of scented quail eggs in grassland was best predicted by turbulence intensity; egg persistence increased with turbulence intensity. Our characterization of differences in olfactory variables among vegetation types provides an important step towards building a clearer understanding of olfactory landscapes. Further, our observation of both patch‐ and local‐scale variation in olfactory variables suggests that prey can potentially select for olfactory concealment at multiple scales. We hypothesize that olfactory concealment provided by high levels of turbulence intensity is an important component of cover in grassland, and that in grassland/shrubland landscapes, prey selection of shrubland patches reduces odor detectability. Our finding of a positive relationship between turbulence intensity and visual concealment also suggests that olfactory concealment may be a previously underappreciated confounding factor in studies of habitat selection.

δ18O and δ2H characteristics of rainwater, groundwater and springs in a mountainous region of Ghana: implication with respect to groundwater recharge and circulation - Abass Gibrilla; Dickson Adomako; Geophrey Anornu; Samuel Ganyaglo; Tibor Stigter; Joseph R. Fianko; ShivePrakash Rai; Andrews Ako Ako (Sustainable Water Resources Management, 2017)

A small proportion of community-associated methicillin-resistant Staphylococcus aureus bacteraemia, compared to healthcare-associated cases, in two South African provinces - O. Perovic; A. Singh-Moodley; N. P. Govender; R. Kularatne; A. Whitelaw; V. Chibabhai; P. Naicker; N. Mbelle; R. Lekalakala; V. Quan; C. Samuel; E. Van Schalkwyk (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Comparison of mixing layer heights determined using LiDAR, radiosonde, and numerical weather prediction model at a rural site in southern India - R. Vishnu; Y. Bhavani Kumar; P. R. Sinha; T. Narayana Rao; E. James Jebaseelan Samuel; P. Kumar (International Journal of Remote Sensing, 2017)

Mechanisms of action of plant growth promoting bacteria - Oluwaseyi Samuel Olanrewaju; Bernard R. Glick; Olubukola Oluranti Babalola (World Journal of Microbiology and Biotechnology, 2017)

Rodent herbivory differentially affects mortality rates of 14 native plant species with contrasting life history and growth form traits - Tiffanny R. Sharp Bowman; Brock R. McMillan; Samuel B. St. Clair (Oecologia, 2017)

Factors Affecting Public Preferences for Grassland Landscape Heterogeneity in the Great Plains - Omkar Joshi; Terrie A. Becerra; David M. Engle; Samuel D. Fuhlendorf; R. Dwayne Elmore (Environmental Management, 2017)

High-Resolution Habitat Suitability Models for the Conservation and Management of Vulnerable Marine Ecosystems on the Louisville Seamount Chain, South Pacific Ocean - Ashley A. Rowden; Owen F. Anderson; Samuel E. Georgian; David A. Bowden; Malcolm R. Clark; Arne Pallentin; Andrew Miller (Frontiers in Marine Science, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Genome‐scale data reveal that endemic Poecilia populations from small sulphidic springs display no evidence of inbreeding - Anthony P. Brown; Ryan Greenway; Samuel Morgan; Corey R. Quackenbush; Luca Giordani; Lenin Arias‐Rodriguez; Michael Tobler; Joanna L. Kelley (Molecular Ecology, 2017)
Populations with limited ranges can be highly vulnerable to changes in their environment and are, thus, of high conservation concern. Populations that experience human‐induced range reductions are often highly inbred and lack genetic diversity, but it is unknown whether this is also the case for populations with naturally small ranges. The fishes Poecilia sulphuraria (listed as critically endangered) and Poecilia thermalis , which are endemic to small hydrogen sulphide‐rich springs in southern Mexico, are examples of such populations with inherently small habitats. We used geometric morphometrics and population genetics to quantify phenotypic and genetic variation within and among two populations of P. sulphuraria and one population of P. thermalis . Principal component analyses revealed phenotypic and genetic differences among the populations. Evidence for inbreeding was low compared to populations that have undergone habitat reduction. The genetic data were also used to infer the demographic history of these populations to obtain estimates for effective population sizes and migration rates. Effective population sizes were large given the small habitats of these populations. Our results imply that these three endemic extremophile populations should each be considered separately for conservation purposes. Additionally, this study suggests that populations in naturally small habitats may have lower rates of inbreeding and higher genetic diversity than expected, and therefore may be better equipped to handle environmental perturbations than anticipated. We caution, however, that the inferred lack of inbreeding and the large effective population sizes could potentially be a result of colonization by genetically diverse ancestors.

Omics to Explore Amyotrophic Lateral Sclerosis Evolution: the Central Role of Arginine and Proline Metabolism - Franck Patin; Philippe Corcia; Patrick Vourc’h; Lydie Nadal-Desbarats; Thomas Baranek; Jean-François Goossens; Sylviane Marouillat; Anne-Frédérique Dessein; Amandine Descat; Blandine Madji Hounoum; Clément Bruno; Samuel Leman; et al. (Molecular Neurobiology, 2017)

Racial Disparities in Emotional Distress Among Cancer Survivors: Insights from the Health Information National Trends Survey (HINTS) - Bettye A. Apenteng; Andrew R. Hansen; Samuel T. Opoku; William A. Mase (Journal of Cancer Education, 2017)

The euphotic zone under Arctic Ocean sea ice: Vertical extents and seasonal trends - Samuel R. Laney; Richard A. Krishfield; John. M. Toole (Limnology and Oceanography, 2017)
Eight Ice‐Tethered Profilers were deployed in the Arctic Ocean between 2011 and 2013 to measure vertical distributions of photosynthetically active radiation (PAR) and other bio‐optical properties in ice‐covered water columns, multiple times a day over periods of up to a year. With the radiometers used on these profilers, PAR could be measured to depths of only ∼20–40 m in the central Arctic in late summer under sea ice ∼1 m thick. At lower latitudes in the Beaufort Gyre, late summer PAR was measurable under ice to depths exceeding 125 m. The maximum depths of measurable PAR followed seasonal trends in insolation, with isolumes shoaling in the fall as solar elevation decreased and deepening in spring and early summer after insolation resumed and sea ice diminished. PAR intensities were often anomalously low above 20 m, likely due to a shading effect associated with local horizontal heterogeneity in light transmittance by the overlying sea ice. A model was developed to parameterize these complex vertical PAR distributions to improve estimates of the water column diffuse attenuation coefficient and other related parameters. Such a model is necessary to separate the effect of surface ice heterogeneity on under‐ice PAR profiles from that of the water column itself, so that euphotic zone depth in ice‐covered water columns can be computed using canonical metrics such as the 1% light level. Water column diffuse attenuation coefficients derived from such autonomously‐collected PAR profile data, using this model, agreed favorably with values determined manually in complementary studies.

Genes essential for phototrophic growth by a purple alphaproteobacterium - Jianming Yang; Liang Yin; Faith H. Lessner; Ernesto S. Nakayasu; Samuel H. Payne; Kathryn R. Fixen; Larry Gallagher; Caroline S. Harwood (Environmental Microbiology, 2017)
Summary Tn‐seq was used to identify genes essential for phototrophic growth by the purple bacterium Rhodopseudomonas palustris . About 167 genes required for anaerobic growth on acetate in light were identified, 35 of which are annotated as photosynthesis genes. The essentiality of many of these genes by analysing the phenotypes of independently generated mutants that had altered pigmentation was verified. Three genes were identified, two possibly involved in biogenesis of the membrane‐bound photosynthetic apparatus and one for phosphatidylcholine biosynthesis, that were not known to be essential for phototrophic growth. Site‐directed mutagenesis was used to show that the NADH:quinone oxidoreductase complex I E was essential for phototrophic growth under strictly anaerobic conditions and appeared to play a role in reverse electron transport to generate NADH. A homologous NADH:quinone oxidoreductase complex I A likely operates in the opposite direction to oxidize NADH. The operation of the two enzymes in opposition would allow R. palustris to maintain redox balance. As a complement to the genetic data, proteomics experiments were carried out in which it was found that 408 proteins were present in significantly higher amounts in cells grown anaerobically in light compared with aerobically. Among these were proteins encoded by subset of the phototrophic growth‐essential genes.

Tsunami Detection by High Frequency Radar Beyond the Continental Shelf: II. Extension of Time Correlation Algorithm and Validation on Realistic Case Studies - Stéphan T. Grilli; Charles-Antoine Guérin; Michael Shelby; Annette R. Grilli; Patrick Moran; Samuel Grosdidier; Tania L. Insua (Pure and Applied Geophysics, 2017)

A globally deployable strategy for co-development of adaptation preferences to sea-level rise: the public participation case of Santos, Brazil - Jose A. Marengo; Luci H. Nunes; Celia R. G. Souza; Joseph Harari; Frank Muller-Karger; Roberto Greco; Eduardo K. Hosokawa; Ernesto K. Tabuchi; Samuel B. Merrill; Catherine J. Reynolds; Mark Pelling; Lincoln M. Alves; et al. (Natural Hazards, 2017)

Flow and quiet eye: the role of attentional control in flow experience - David J. Harris; Samuel J. Vine; Mark R. Wilson (Cognitive Processing, 2017)

Spatio-temporal dynamics of gross rainfall partitioning and nutrient fluxes in shaded-cocoa (Theobroma cocoa) systems in a tropical semi-deciduous forest - Evans K. Dawoe; Victor R. Barnes; Samuel K. Oppong (Agroforestry Systems, 2017)

A tale of three cuffs: the hemodynamics of blood flow restriction - J. Grant Mouser; Scott J. Dankel; Matthew B. Jessee; Kevin T. Mattocks; Samuel L. Buckner; Brittany R. Counts; Jeremy P. Loenneke (European Journal of Applied Physiology, 2017)

Associations of human skeletal muscle fiber type and insulin sensitivity, blood lipids, and vascular hemodynamics in a cohort of premenopausal women - Gordon Fisher; Samuel T. Windham; Perry Griffin; Jonathan L. Warren; Barbara A. Gower; Gary R. Hunter (European Journal of Applied Physiology, 2017)

Bradyrhizobium centrolobii and Bradyrhizobium macuxiense sp. nov. isolated from Centrolobium paraense grown in soil of Amazonia, Brazil - Daniele C. Michel; Samuel R. Passos; Jean L. Simões-Araujo; Alexandre C. Baraúna; Krisle da Silva; Marcia M. Parma; Itamar S. Melo; Sofie E. De Meyer; Graham O’Hara; Jerri E. Zilli (Archives of Microbiology, 2017)

Methodological perspectives on the application of compound-specific stable isotope fingerprinting for sediment source apportionment - Hari R. Upadhayay; Samuel Bodé; Marco Griepentrog; Dries Huygens; Roshan M. Bajracharya; William H. Blake; Gerd Dercon; Lionel Mabit; Max Gibbs; Brice X. Semmens; Brian C. Stock; Wim Cornelis; et al. (Journal of Soils and Sediments, 2017)

Applying the process of backward design in revising an environmental science program - Caralyn B. Zehnder; Kalina Manoylov; Christine Mutiti; Samuel Mutiti; Allison R. VandeVoort (Journal of Environmental Studies and Sciences, 2017)

Extreme climatic events constrain space use and survival of a ground‐nesting bird - Evan P. Tanner; R. Dwayne Elmore; Samuel D. Fuhlendorf; Craig. A. Davis; David K. Dahlgren; Jeremy P. Orange (Global Change Biology, 2017)
Two fundamental issues in ecology are understanding what influences the distribution and abundance of organisms through space and time. While it is well established that broad‐scale patterns of abiotic and biotic conditions affect organisms’ distributions and population fluctuations, discrete events may be important drivers of space use, survival, and persistence. These discrete extreme climatic events can constrain populations and space use at fine scales beyond that which is typically measured in ecological studies. Recently, a growing body of literature has identified thermal stress as a potential mechanism in determining space use and survival. We sought to determine how ambient temperature at fine temporal scales affected survival and space use for a ground‐nesting quail species ( Colinus virginianus ; northern bobwhite). We modeled space use across an ambient temperature gradient (ranging from −20 to 38 °C) through a maxent algorithm. We also used Andersen–Gill proportional hazard models to assess the influence of ambient temperature‐related variables on survival through time. Estimated available useable space ranged from 18.6% to 57.1% of the landscape depending on ambient temperature. The lowest and highest ambient temperature categories ( 35 °C, respectively) were associated with the least amount of estimated useable space (18.6% and 24.6%, respectively). Range overlap analysis indicated dissimilarity in areas where Colinus virginianus were restricted during times of thermal extremes (range overlap = 0.38). This suggests that habitat under a given condition is not necessarily a habitat under alternative conditions. Further, we found survival was most influenced by weekly minimum ambient temperatures. Our results demonstrate that ecological constraints can occur along a thermal gradient and that understanding the effects of these discrete events and how they change over time may be more important to conservation of organisms than are average and broad‐scale conditions as typically measured in ecological studies.

Neurons in the pontomedullary reticular formation receive converging inputs from the hindlimb and labyrinth - Derek M. Miller; William M. DeMayo; George H. Bourdages; Samuel R. Wittman; Bill J. Yates; Andrew A. McCall (Experimental Brain Research, 2017)

Herbicide application during pasture renewal initially increases root turnover and carbon input to soil in perennial ryegrass and white clover pasture - Samuel R. McNally; Daniel C. Laughlin; Susanna Rutledge; Mike B. Dodd; Johan Six; Louis A. Schipper (Plant and Soil, 2017)

Design Considerations of a Fiber Optic Pressure Sensor Protective Housing for Intramuscular Pressure Measurements - Shanette A. Go; Elisabeth R. Jensen; Shawn M. O’Connor; Loribeth Q. Evertz; Duane A. Morrow; Samuel R. Ward; Richard L. Lieber; Kenton R. Kaufman (Annals of Biomedical Engineering, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Genome characterization of a bovine papillomavirus type 5 from cattle in the Amazon region, Brazil - Flavio R. C. da Silva; Cíntia Daudt; Samuel P. Cibulski; Matheus N. Weber; Ana Paula M. Varela; Fabiana Q. Mayer; Paulo M. Roehe; Cláudio W. Canal (Virus Genes, 2017)

Philopatry and Regional Connectivity of the Great Hammerhead Shark, Sphyrna mokarran in the U.S. and Bahamas - Tristan L. Guttridge; Maurits P. M. Van Zinnicq Bergmann; Chris Bolte; Lucy A. Howey; Jean S. Finger; Steven T. Kessel; Jill L. Brooks; William Winram; Mark E. Bond; Lance K. B. Jordan; Rachael C. Cashman; Emily R. Tolentino; et al. (Frontiers in Marine Science, 2017)

Differentiating swelling and hypertrophy through indirect assessment of muscle damage in untrained men following repeated bouts of resistance exercise - Samuel L. Buckner; Scott J. Dankel; Kevin T. Mattocks; Matthew B. Jessee; J. Grant Mouser; Brittany R. Counts; Gilberto C. Laurentino; Jeremy P. Loenneke (European Journal of Applied Physiology, 2017)

Towards management of invasive ectomycorrhizal fungi - Ian A. Dickie; Martin A. Nuñez; Anne Pringle; Teresa Lebel; Samuel G. Tourtellot; Peter R. Johnston (Biological Invasions, 2016)

A new densovirus in cerebrospinal fluid from a case of anti-NMDA-receptor encephalitis - Tung Gia Phan; Kevin Messacar; Samuel R. Dominguez; Antonio Charlys da Costa; Xutao Deng; Eric Delwart (Archives of Virology, 2016)

Post-exercise blood flow restriction attenuates muscle hypertrophy - Scott J. Dankel; Samuel L. Buckner; Matthew B. Jessee; Kevin T. Mattocks; J. Grant Mouser; Brittany R. Counts; Gilberto C. Laurentino; Takashi Abe; Jeremy P. Loenneke (European Journal of Applied Physiology, 2016)

Pyomelanin‐producing Pseudomonas aeruginosa selected during chronic infections have a large chromosomal deletion which confers resistance to pyocins - Didier Hocquet; Marie Petitjean; Laurence Rohmer; Benoît Valot; Hemantha D. Kulasekara; Elodie Bedel; Xavier Bertrand; Patrick Plésiat; Thilo Köhler; Alix Pantel; Michael A. Jacobs; Lucas R. Hoffman; et al. (Environmental Microbiology, 2016)
Summary When bacterial lineages make the transition from free‐living to permanent association with hosts, they can undergo massive gene losses, for which the selective forces within host tissues are unknown. We identified here melanogenic clinical isolates of Pseudomonas aeruginosa with large chromosomal deletions (66 to 270 kbp) and characterized them to investigate how they were selected. When compared with their wild‐type parents, melanogenic mutants (i) exhibited a lower fitness in growth conditions found in human tissues, such as hyperosmolarity and presence of aminoglycoside antibiotics, (ii) narrowed their metabolic spectrum with a growth disadvantage with particular carbon sources, including aromatic amino acids and acyclic terpenes, suggesting a reduction of metabolic flexibility. Despite an impaired fitness in rich media, melanogenic mutants can inhibit their wild‐type parents and compete with them in coculture. Surprisingly, melanogenic mutants became highly resistant to two intraspecific toxins, the S‐pyocins AP41 and S1. Our results suggest that pyocins produced within a population of infecting P. aeruginosa may have selected for bacterial mutants that underwent massive gene losses and that were adapted to the life in diverse bacterial communities in the human host. Intraspecific interactions may therefore be an important factor driving the continuing evolution of pathogens during host infections.

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

Co-evolution of wetland landscapes, flooding, and human settlement in the Mississippi River Delta Plain - Robert R. Twilley; Samuel J. Bentley; Qin Chen; Douglas A. Edmonds; Scott C. Hagen; Nina S.-N. Lam; Clinton S. Willson; Kehui Xu; DeWitt Braud; R. Hampton Peele; Annabeth McCall (Sustainability Science, 2016)

An overview of ice storms and their impact in the United States - Samuel K. Degelia; Jordan I. Christian; Jeffrey B. Basara; Trevor J. Mitchell; Daniel F. Gardner; Sara E. Jackson; John C. Ragland; Hayden R. Mahan (International Journal of Climatology, 2016)
Ice storms, defined by the US National Weather Service as freezing rain accumulations over 0.635 cm (0.25 inch), are often costly and destructive. Formation processes include the classic ‘melting’ process and supercooled warm rain process. Freezing rain is most commonly found ahead of a warm front or occlusion, where warm air is lifted over a cold shallow layer near the surface. Other synoptic patterns conducive to freezing rain include arctic fronts, isentropic lift over an arctic air mass, and cold air damming. Causes of spatial and temporal variations in freezing rain include, but are not limited to, terrain and proximity to water. Areas with the most occurrences of freezing rain in the United States include the Pacific Northwest, Upper Midwest, and Northeast/Appalachian regions. Empirical forecasting methods and numerical weather prediction are currently used to predict freezing rain. Successful forecasting of ice storm events requires evaluation of the thermodynamic profile of the atmosphere. Local effects such as proximity to water and topography must be taken into account, and non‐linear processes such as latent heating and cooling must not be ignored. Ice accumulation can cause tree damage, which, in addition to breakage of electrical cables, can lead to power outages. Deposition of ice also impacts road, rail, and air travel, with associated economic costs due to lost hours as workers are unable to travel. Ice storms also provide a significant risk to human health and life, with falling debris and slippery surfaces being primary threats.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Impact of prenatal nicotine on the structure of midbrain dopamine regions in the rat - Natalia Omelchenko; Priya Roy; Judith Joyce Balcita-Pedicino; Samuel Poloyac; Susan R. Sesack (Brain Structure and Function, 2016)

Full-Length Recombinant Human Proteoglycan 4 Interacts with Hyaluronan to Provide Cartilage Boundary Lubrication - Saleem Abubacker; Samuel G. Dorosz; Dragana Ponjevic; Gregory D. Jay; John R. Matyas; Tannin A. Schmidt (Annals of Biomedical Engineering, 2016)

Altered cognitive response to serotonin challenge as a candidate endophenotype for obsessive-compulsive disorder - Christine Lochner; Samuel R. Chamberlain; Martin Kidd; Naomi A. Fineberg; Dan J. Stein (Psychopharmacology, 2016)

Spatial and temporal estimation of soil loss for the sustainable management of a wet semi-arid watershed cluster - R. Rejani; K. V. Rao; M. Osman; Ch. Srinivasa Rao; K. Sammi Reddy; G. R. Chary; Pushpanjali; Josily Samuel (Environmental Monitoring and Assessment, 2016)

Temporal variability in aboveground plant biomass decreases as spatial variability increases - Devan Allen McGranahan; Torre J. Hovick; R. Dwayne Elmore; David M. Engle; Samuel D. Fuhlendorf; Stephen L. Winter; James R. Miller; Diane M. Debinski (Ecology, 2016)
Ecological theory predicts that diversity decreases variability in ecosystem function. We predict that, at the landscape scale, spatial variability created by a mosaic of contrasting patches that differ in time since disturbance will decrease temporal variability in aboveground plant biomass. Using data from a multi‐year study of seven grazed tallgrass prairie landscapes, each experimentally managed for one to eight patches, we show that increased spatial variability driven by spatially patchy fire and herbivory reduces temporal variability in aboveground plant biomass. This pattern is associated with statistical evidence for the portfolio effect and a positive relationship between temporal variability and functional group synchrony as predicted by metacommunity variability theory. As disturbance from fire and grazing interact to create a shifting mosaic of spatially heterogeneous patches within a landscape, temporal variability in aboveground plant biomass can be dampened. These results suggest that spatially heterogeneous disturbance regimes contribute to a portfolio of ecosystem functions provided by biodiversity, including wildlife habitat, fuel, and forage. We discuss how spatial patterns of disturbance drive variability within and among patches.

Informing conservation by identifying range shift patterns across breeding habitats and migration strategies - Torre J. Hovick; Brady W. Allred; Devan A. McGranahan; Michael W. Palmer; R. Dwayne Elmore; Samuel D. Fuhlendorf (Biodiversity and Conservation, 2016)

Exposure to environmental chemicals and heavy metals, and risk of pancreatic cancer - Samuel O. Antwi; Elizabeth C. Eckert; Corinna V. Sabaque; Emma R. Leof; Kieran M. Hawthorne; William R. Bamlet; Kari G. Chaffee; Ann L. Oberg; Gloria M. Petersen (Cancer Causes & Control, 2015)

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

A novel sister clade to the enterobacteria microviruses (family M icroviridae ) identified in methane seep sediments - Samuel Joseph Bryson; Andrew R. Thurber; Adrienne M. S. Correa; Victoria J. Orphan; Rebecca Vega Thurber (Environmental Microbiology, 2015)
Summary Methane seep microbial communities perform a key ecosystem service by consuming the greenhouse gas methane prior to its release into the hydrosphere, minimizing the impact of marine methane sources on our climate. Although previous studies have examined the ecology and biochemistry of these communities, none has examined viral assemblages associated with these habitats. We employed virus particle purification, genome amplification, pyrosequencing and gene/genome reconstruction and annotation on two metagenomic libraries, one prepared for ssDNA and the other for all DNA , to identify the viral community in a methane seep. Similarity analysis of these libraries (raw and assembled) revealed a community dominated by phages, with a significant proportion of similarities to the M icroviridae family of ssDNA phages. We define these viruses as the E el R iver B asin M icroviridae ( ERBM ). Assembly and comparison of 21 ERBM closed circular genomes identified five as members of a novel sister clade to the M icrovirus genus of Enterobacteria phages. Comparisons among other metagenomes and these Microviridae major‐capsid sequences indicated that this clade of phages is currently unique to the E el R iver B asin sediments. Given this ERBM clade's relationship to the M icroviridae genus M icrovirus , we define this sister clade as the candidate genus P equeñovirus .

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

The Political Use of the Cancer Metaphor: Negative Consequences for the Public and the Cancer Community - Barry R. Meisenberg; Samuel W. Meisenberg (Journal of Cancer Education, 2015)

Moisture stable heteroleptic titanium (IV) complexes derived from 8-hydroxyquinoline: synthesis, antibacterial, and antifungal studies - Blassan Samuel; K. R. Ethiraj; Madhvesh Pathak (Medicinal Chemistry Research, 2015)

Caffeine impairs the acquisition and retention, but not the consolidation of Pavlovian conditioned freezing in mice - Sylvain Dubroqua; Samuel R. L. Low; Benjamin K. Yee; Philipp Singer (Psychopharmacology, 2015)

Development of a Cell Permeable Competitive Antagonist of RhoA and CRMP4 binding, TAT-C4RIP, to Promote Neurite Outgrowth - Mohammad R. Khazaei; Samuel Montcalm; Adriana Di Polo; Alyson E. Fournier; Yves Durocher; Stephan Ong Tone (Journal of Molecular Neuroscience, 2015)

The role of the integument with respect to different modes of locomotion in the Nematalycidae (Endeostigmata) - Samuel J. Bolton; Gary R. Bauchan; Ronald Ochoa; Christopher Pooley; Hans Klompen (Experimental and Applied Acarology, 2015)

Effect of tyrosine ingestion on cognitive and physical performance utilising an intermittent soccer performance test (iSPT) in a warm environment - Nicole A. Coull; Samuel L. Watkins; Jeffrey W. F. Aldous; Lee K. Warren; Bryna C. R. Chrismas; Benjamin Dascombe; Alexis R. Mauger; Grant Abt; Lee Taylor (European Journal of Applied Physiology, 2015)

Synthesis and characterization of TiO2 and TiO2/Ag for use in photodegradation of methylviologen, with kinetic study by laser flash photolysis - Dayana Doffinger Ramos; Paula C. S. Bezerra; Frank H. Quina; Renato F. Dantas; Gleison A. Casagrande; Silvio C. Oliveira; Márcio R. S. Oliveira; Lincoln C. S. Oliveira; Valdir S. Ferreira; Samuel L. Oliveira; Amilcar Machulek (Environmental Science and Pollution Research, 2015)

Development and characterization of 23 microsatellite loci for scaled quail (Callipepla squamata) - Jeremy P. Orange; Craig A. Davis; Ronald A. Van Den Bussche; Samuel D. Fuhlendorf; R. Dwayne Elmore; Eric T. Thacker; Megan E. Judkins (Conservation Genetics Resources, 2014)

An analysis of the sponge Acanthostrongylophora igens' microbiome yields an actinomycete that produces the natural product manzamine A - Amanda L. Waters; Olivier Peraud; Noer Kasanah; James W. Sims; Nuwan Kothalawala; Matthew A. Anderson; Samuel H. Abbas; Karumanchi V. Rao; Vijay R. Jupally; Michelle Kelly; Amala Dass; Russell T. Hill; et al. (Frontiers in Marine Science, 2014)

From Refining Sugar to Growing Tomatoes - Samuel W. Short; Nancy M.P. Bocken; Claire Y. Barlow; Marian R. Chertow (Journal of Industrial Ecology, 2014)
Summary This article seeks to advance the understanding of the relationship between industrial ecology (IE) and business model innovation for sustainability as a means and driver of new value creation and competitive advantage by expanding the understanding of industrial symbiosis (IS) and internal symbiosis. This is explored through the case study of British Sugar, which, at the time of writing, is the UK's largest sugar producer by market share. Over the past three decades, the company has systematically sought opportunities to turn waste streams and emissions from their core production processes into useful and positive inputs to new product lines. Their core business is still sugar, but the business model has evolved to offer a broad range of additional synergistic and profitable product lines, including animal feed, electricity, tomatoes, and bioethanol. The research explores the temporal dimension of dynamic business model innovation, framing it in the context of a continuous evolutionary process rather than a discrete design activity. The case will be of interest as an additional contribution to the growing literature on IS; in offering an approach for linking the themes of IE literature and sustainable business model innovation more concretely in research and practice; and, by presenting the case as an evolutionary innovation process, the article furthers the emerging literature on business model innovation for sustainability.

Male biased sex ratio of poached elephants is negatively related to poaching intensity over time - Samrat Mondol; Celia R. Mailand; Samuel K. Wasser (Conservation Genetics, 2014)

Impact of human immunodeficiency virus on neurocognition and risky behaviors in young adults - Laurie M. Baker; Robert H. Paul; Jodi M. Heaps; Elizabeth Westerhaus; Jee Yoon Chang; Samuel Williams; Matthew R. Brier; Katie Plax; Beau M. Ances (Journal of NeuroVirology, 2014)

Functional analysis reveals angiogenic potential of human mesenchymal stem cells from Wharton’s jelly in dermal regeneration - Sandra S. Edwards; Gabriela Zavala; Catalina P. Prieto; Matías Elliott; Samuel Martínez; Jose T. Egaña; María R. Bono; Verónica Palma (Angiogenesis, 2014)

High humidity partially rescues the Arabidopsis thaliana exo70A1 stigmatic defect for accepting compatible pollen - Darya Safavian; Muhammad Jamshed; Subramanian Sankaranarayanan; Emily Indriolo; Marcus A. Samuel; Daphne R. Goring (Plant Reproduction, 2014)

Stand composition, proximity to overstory trees and gradients of soil moisture influence patterns of subalpine fir seedling emergence and survival - Joshua R. Buck; Samuel B. St. Clair (Plant and Soil, 2014)

Towards a molecular basis of oligometastatic disease: potential role of micro-RNAs - Abhineet Uppal; Mark K. Ferguson; Mitchell C. Posner; Samuel Hellman; Nikolai N. Khodarev; Ralph R. Weichselbaum (Clinical & Experimental Metastasis, 2014)

Phylogenomics, molecular evolution, and estimated ages of lineages from the deep phylogeny of Poaceae - Samuel S. Jones; Sean V. Burke; Melvin R. Duvall (Plant Systematics and Evolution, 2014)

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Texas environmental flow standards and the hydrology-based environmental flow regime methodology - Daniel R. Opdyke; Edmund L. Oborny; Samuel K. Vaugh; Kevin B. Mayes (Hydrological Sciences Journal, 2014)

Reply to letter: Acetaminophen and sport performance: doping or what? - Alexis R. Mauger; Lee Taylor; Bryna C. R. Chrismas; Samuel L. Watkins; Josh Foster (European Journal of Applied Physiology, 2014)

Land cover changes and their biogeophysical effects on climate - Rezaul Mahmood; Roger A. Pielke; Kenneth G. Hubbard; Dev Niyogi; Paul A. Dirmeyer; Clive McAlpine; Andrew M. Carleton; Robert Hale; Samuel Gameda; Adriana Beltrán‐Przekurat; Bruce Baker; Richard McNider; et al. (International Journal of Climatology, 2014)
Land cover changes ( LCCs ) play an important role in the climate system. Research over recent decades highlights the impacts of these changes on atmospheric temperature, humidity, cloud cover, circulation, and precipitation. These impacts range from the local‐ and regional‐scale to sub‐continental and global‐scale. It has been found that the impacts of regional‐scale LCC in one area may also be manifested in other parts of the world as a climatic teleconnection. In light of these findings, this article provides an overview and synthesis of some of the most notable types of LCC and their impacts on climate. These LCC types include agriculture, deforestation and afforestation, desertification, and urbanization. In addition, this article provides a discussion on challenges to, and future research directions in, assessing the climatic impacts of LCC .

Landscape effects on gene flow for a climate‐sensitive montane species, the A merican pika - Jessica A. Castillo; Clinton W. Epps; Anne R. Davis; Samuel A. Cushman (Molecular Ecology, 2014)
Climate change is arguably the greatest challenge to conservation of our time. Most vulnerability assessments rely on past and current species distributions to predict future persistence but ignore species' abilities to disperse through landscapes, which may be particularly important in fragmented habitats and crucial for long‐term persistence in changing environments. Landscape genetic approaches explore the interactions between landscape features and gene flow and can clarify how organisms move among suitable habitats, but have suffered from methodological uncertainties. We used a landscape genetic approach to determine how landscape and climate‐related features influence gene flow for A merican pikas ( O chotona princeps ) in C rater Lake National Park. Pikas are heat intolerant and restricted to cool microclimates; thus, range contractions have been predicted as climate changes. We evaluated the correlation between landscape variables and genetic distance using partial Mantel tests in a causal modelling framework, and used spatially explicit simulations to evaluate methods of model optimization including a novel approach based on relative support and reciprocal causal modelling. We found that gene flow was primarily restricted by topographic relief, water and west‐facing aspects, suggesting that physical restrictions related to small body size and mode of locomotion, as well as exposure to relatively high temperatures, limit pika dispersal in this alpine habitat. Our model optimization successfully identified landscape features influencing resistance in the simulated data for this landscape, but underestimated the magnitude of resistance. This is the first landscape genetic study to address the fundamental question of what limits dispersal and gene flow in the A merican pika.

Assessment of extracellular dehydration using saliva osmolality - Brett R. Ely; Samuel N. Cheuvront; Robert W. Kenefick; Marissa G. Spitz; Kristen R. Heavens; Neil P. Walsh; Michael N. Sawka (European Journal of Applied Physiology, 2014)

The influence of acetaminophen on repeated sprint cycling performance - Josh Foster; Lee Taylor; Bryna C. R. Chrismas; Samuel L. Watkins; Alexis R. Mauger (European Journal of Applied Physiology, 2014)

MicroRNAs in islet immunobiology and transplantation - Antonello Pileggi; Dagmar Klein; Carmen Fotino; Valia Bravo-Egaña; Samuel Rosero; Marco Doni; Michele Podetta; Camillo Ricordi; R. Damaris Molano; Ricardo L. Pastori (Immunologic Research, 2013)

Fractionation of heavy metals and assessment of contamination of the sediments of Lake Titicaca - Luis Fernando Cáceres Choque; Oswaldo E. Ramos Ramos; Sulema N. Valdez Castro; Rigoberto R. Choque Aspiazu; Rocío G. Choque Mamani; Samuel G. Fernández Alcazar; Ondra Sracek; Prosun Bhattacharya (Environmental Monitoring and Assessment, 2013)

Organic Trace Mineral Levels in the First 96-H Post-Hatch Impact Growth Performance and Intestinal Gene Expression in Broiler Chicks - K. M. Brennan; R. S. Samuel; D. E. Graugnard; T. Ao; R. Xiao; A. H. Cantor; A. J. Pescatore (Biological Trace Element Research, 2013)

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Neoproterozoic ophiolitic peridotites along the Allaqi-Heiani suture, South Eastern Desert, Egypt - M. K. Azer; M. D. Samuel; K. A. Ali; H. A. Gahlan; R. J. Stern; M. Ren; H. E. Moussa (Mineralogy and Petrology, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Designing for Scale: Development of the ReMotion Knee for Global Emerging Markets - Samuel R. Hamner; Vinesh G. Narayan; Krista M. Donaldson (Annals of Biomedical Engineering, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Coincidence of biophoton emission by wheat seedlings during simultaneous, transcontinental germination tests - Cristiano M. Gallep; Thiago A. Moraes; Samuel R. dos Santos; Peter W. Barlow (Protoplasma, 2013)

Do we need a global fisheries management organization? - J. Samuel Barkin; Elizabeth R. DeSombre (Journal of Environmental Studies and Sciences, 2013)

Conservation implications of native and introduced ungulates in a changing climate - Brady W. Allred; Samuel D. Fuhlendorf; Torre J. Hovick; R. Dwayne Elmore; David M. Engle; Anthony Joern (Global Change Biology, 2013)
In many grasslands, grazing by large native or introduced ungulates drives ecosystem structure and function. The behavior of these animals is important as it directs the spatial effects of grazing. To the degree that temperature drives spatial components of foraging, understanding how changes in climate alter grazing behavior will provide guidance for the conservation of ecosystem goods and services. We determined the behavioral response of native bison ( Bison bison ) and introduced cattle ( Bos taurus ) to temperature in tallgrass prairie within the Great Plains, USA . We described the thermal environment by measuring operative temperature (the temperature perceived by animals) through space and time. Site selection preferences of ungulates were quantified using resource selection functions. Woody vegetation in tallgrass prairie provided a cooler thermal environment for large ungulates, decreasing operative temperature up to 16 °C in the heat of the summer. Cattle began to seek thermal refugia at lower air temperatures (24 °C) by selecting areas closer to woody vegetation and water sources. Bison, however, sought refugia within wooded areas at higher air temperatures (36 °C), which occurred much less frequently. Both species became more attracted to riparian areas as air temperature increased, with preferences increasing tenfold during the hottest periods. As predicted warming occurs across the Great Plains and other grasslands, grazing behavior and subsequent grazing effects will be altered. Riparian areas, particularly those with both water and woody vegetation, will receive greater utilization and selection by large ungulates. The use of native grazers for conservation or livestock production may mitigate negative effects caused by increased temperatures.

Hydrogeologic and topographic controls on evolution of karst features in Illinois’ sinkhole plain - Samuel V. Panno; Walton R. Kelly; Julie C. Angel; Donald E. Luman (Carbonates and Evaporites, 2013)

Dispersal and vicariance of H oplias malabaricus ( B loch, 1794) ( T eleostei, E rythrinidae) populations of the B razilian continental margin - Tiago L. Pereira; Udson Santos; Carlos E. Schaefer; Gisele O. Souza; Samuel R. Paiva; Luiz R. Malabarba; Eduardo E. Schmidt; Jorge A. Dergam (Journal of Biogeography, 2013)
Aim The aim of this study was to test the hypothesis that the Brazilian coastal populations of Hoplias malabaricus were subject to the same geomorphological and palaeohydrological factors that resulted in endemic fish regions, by characterizing the mitochondrial DNA , nuclear sequences and cytogenetic data of these populations. Location Seventeen coastal basins in north‐eastern, eastern and south‐eastern Brazil, plus the São Francisco Basin. Methods Forty‐two specimens were analysed. Mitochondrial ATP synthase 6 ( ATPase‐6 ) and nuclear recombination activating gene 2 ( RAG2 ) gene sequences were used for Bayesian inference and maximum parsimony analyses. Molecular models were selected using MrModeltest . Results Molecular analyses indicated four haplogroups (Northeastern, Eastern A, Eastern B and Southeastern) for ATPase‐6 and three clades for RAG2 . All topologies were congruent with Hoplias malabaricus diploid numbers, with most regions of proposed endemism and coastal geomorphological units. Main conclusions Deep genetic divergence between the Northeastern and the other haplogroups was interpreted as evidence of the vicariant effect of the Abrolhos Formation, which effectively isolates 2 n = 40 and 2 n = 42 coastal populations. To the south, the Cabo Frio Magmatic Lineament also isolates the Eastern and Southeastern 2 n = 42 populations. In the Northeastern haplogroup, stream piracy was probably involved in chronologically varied dispersal events between coastal and continental basins. All haplogroups also included haplotypes that dispersed in recent times. Results show an older vicariant pattern and recent dispersal events congruent with the occurrence of temporary connections along the coast caused by eustatic sea level variations and the occurrence of stream piracy involving either continental or coastal basins, and suggest these processes contributed to the current distribution patterns of Brazilian coastal freshwater fish.

Hypohydration and acute thermal stress affect mood state but not cognition or dynamic postural balance - Brett R. Ely; Kurt J. Sollanek; Samuel N. Cheuvront; Harris R. Lieberman; Robert W. Kenefick (European Journal of Applied Physiology, 2013)

Biological invasions in soil: DNA barcoding as a monitoring tool in a multiple taxa survey targeting European earthworms and springtails in North America - David Porco; Thibaud Decaëns; Louis Deharveng; Samuel W. James; Dariusz Skarżyński; Christer Erséus; Kevin R. Butt; Benoit Richard; Paul D. N. Hebert (Biological Invasions, 2013)

The trade of medicinal animals in Brazil: current status and perspectives - Felipe S. Ferreira; Hugo Fernandes-Ferreira; Nivaldo A. Léo Neto; Samuel V. Brito; Rômulo R. N. Alves (Biodiversity and Conservation, 2013)

Emiliania huxleyi specific growth rate dependence on temperature - Samuel R. Fielding (Limnology and Oceanography, 2013)
A revised estimate of the relationship between the maximum growth rate ( μ max , d −1 ) of Emiliania huxleyi and temperature ( T , °C) was made using quantile regression and literature data from culture experiments ( n = 1415). For modeling E. huxleyi bloom formation and coccolithophore functional group growth rate, this relationship is commonly assumed to follow an exponential relationship, as is the case for photosynthetic algal species in general. However, data specific to E. huxleyi show that this relationship is better described by a power function. Direct comparison with growth rate‐temperature relationships used to model E. huxleyi from the literature shows that they overestimate growth rate by up to 250% over a wide range of temperatures. It is recommended that the revised relationship of μ max = 0.1419 T 0.8151 be used in future models incorporating temperature‐dependent maximum growth rate estimates of E. huxleyi and of coccolithophores as a functional group.

Hydrological Prediction in a Tropical Watershed Dominated by Oxisols Using a Distributed Hydrological Model - Samuel Beskow; Lloyd D. Norton; Carlos R. Mello (Water Resources Management, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Prediction of monthly mean daily global solar radiation using Artificial Neural Network - V SIVAMADHAVI; R SAMUEL SELVARAJ (Journal of Earth System Science, 2012)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Hydration assessment using the cardiovascular response to standing - Samuel N. Cheuvront; Brett R. Ely; Robert W. Kenefick; Mark J. Buller; Nisha Charkoudian; Michael N. Sawka (European Journal of Applied Physiology, 2012)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Erratum to: Macronutrient (N, P, K) and Redoximorphic Metal (Fe, Mn) Allocation in Leersia oryzoides (Rice Cutgrass) Grown Under Different Flood Regimes - Samuel C. Pierce; Matt T. Moore; Dan Larsen; S. R. Pezeshki (Water, Air, & Soil Pollution, 2012)

Water Quality and Plankton in the United States Nearshore Waters of Lake Huron - Peder M. Yurista; John R. Kelly; Samuel E. Miller; Jon D. Van Alstine (Environmental Management, 2012)

Assessment of the aquatic biodiversity of a threatened coastal lagoon at Bimini, Bahamas - David E. Jennings; Joseph D. DiBattista; Kristine L. Stump; Nigel E. Hussey; Bryan R. Franks; R. Dean Grubbs; Samuel H. Gruber (Journal of Coastal Conservation, 2012)

Diatoms favor their younger daughters - Samuel R. Laney; Robert J. Olson; Heidi M. Sosik (Limnology and Oceanography, 2012)
We used a time‐lapse imaging approach to examine cell division in the marine centric diatom Ditylum brightwellii and observed that daughter cells who inherited their parents& hypothecal frustule half were more likely to divide before their sisters. This is consistent with observations in Escherichia coli of a bias between sister cells, where faster growth in one sister is thought to arise from its inheriting parental material with less oxidative damage. We also observed that hypothecal sisters in D. brightwellii were more likely to inherit a greater proportion of their parents& cellular material, similar to what has been seen in E. coli . We found a statistically significant correlation between the amount of parental material inherited by a hypothecal daughter and its relative division rate, indicating that this extra material inherited by the hypothecal daughter plays a role in its more rapid division. Furthermore, the intercept in this regression was greater than zero, indicating that other factors, such as differences in the quality of inherited material, also play a role. This similarity between two taxonomically distant microbes suggests that favoritism toward one daughter might occur broadly among unicellular organisms that reproduce asexually by binary fission. Such a bias in cell division might be advantageous, given model predictions that show that favoring one daughter at the expense of the other can result in higher population growth rates, increasing the chance that a cell&s genotype will survive compared to a model where the daughters divide at equal rates.

Bio-reduction of Cr(VI) by exopolysaccharides (EPS) from indigenous bacterial species of Sukinda chromite mine, India - R. Harish; Jastin Samuel; R. Mishra; N. Chandrasekaran; A. Mukherjee (Biodegradation, 2012)

Preformulation Study of NSC-726796 - Duoli Guo; James P. Cain; Sean O’Connell; Erin R. Gardner; Steven Pisle; William D. Figg; S. Esmail Tabibi; Samuel H. Yalkowsky (AAPS PharmSciTech, 2012)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Antagonism at NMDA receptors, but not β-adrenergic receptors, disrupts the reconsolidation of pavlovian conditioned approach and instrumental transfer for ethanol-associated conditioned stimuli - Amy L. Milton; Moritz J. W. Schramm; James R. Wawrzynski; Felicity Gore; Faye Oikonomou-Mpegeti; Nancy Q. Wang; Daniel Samuel; Daina Economidou; Barry J. Everitt (Psychopharmacology, 2012)

Dronabinol, a cannabinoid agonist, reduces hair pulling in trichotillomania: a pilot study - Jon E. Grant; Brian L. Odlaug; Samuel R. Chamberlain; Suck Won Kim (Psychopharmacology, 2011)

Fire tolerance of a resprouting Artemisia (Asteraceae) shrub - Stephen L. Winter; Samuel D. Fuhlendorf; Carla L. Goad; Craig A. Davis; Karen R. Hickman; David M. Leslie (Plant Ecology, 2011)

DEET insect repellent: effects on thermoregulatory sweating and physiological strain - Robert W. Kenefick; Samuel N. Cheuvront; Brett R. Ely; Laura J. Palombo; Michael N. Sawka (European Journal of Applied Physiology, 2011)

The twentieth century contiguous US temperature changes indicated by daily data and higher statistical moments - Samuel S. P. Shen; Ai B. Gurung; Hee-S. Oh; T. Shu; David R. Easterling (Climatic Change, 2011)

Molecular and pedigree analysis applied to conservation of animal genetic resources: the case of Brazilian Somali hair sheep - Samuel R. Paiva; Olivardo Facó; Danielle A. Faria; Thaísa Lacerda; Gabriel B. Barretto; Paulo L. S. Carneiro; Raimundo N. B. Lobo; Concepta McManus (Tropical Animal Health and Production, 2011)

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

Role of ethylene and jasmonic acid on rhizome induction and growth in rhubarb (Rheum rhabarbarum L.) - Usha P. Rayirath; Rajasekaran R. Lada; Claude D. Caldwell; Samuel K. Asiedu; Kevin J. Sibley (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Determination of the Biodiesel Content in Diesel/Biodiesel Blends: A Method Based on Fluorescence Spectroscopy - Marisa D. Scherer; Samuel L. Oliveira; Sandro M. Lima; Luis H. C. Andrade; Anderson R. L. Caires (Journal of Fluorescence, 2011)

Persistence of deposited metals in the lungs after stainless steel and mild steel welding fume inhalation in rats - James M. Antonini; Jenny R. Roberts; Samuel Stone; Bean T. Chen; Diane Schwegler-Berry; Rebecca Chapman; Patti C. Zeidler-Erdely; Ronnee N. Andrews; David G. Frazer (Archives of Toxicology, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

Application of the principal component analysis on geochemical data: a case study in the basement complex of Southern Ilesa area, Nigeria - Emmanuel A. Ariyibi; Samuel L. Folami; Bankole D. Ako; Taye R. Ajayi; Adebowale O. Adelusi (Arabian Journal of Geosciences, 2011)

Effectiveness of Scat‐Detection Dogs in Determining Species Presence in a Tropical Savanna Landscape - CARLY VYNNE; JOHN R. SKALSKI; RICARDO B. MACHADO; MARTHA J. GROOM; ANAH T. A. JÁCOMO; JADER MARINHO‐FILHO; MARIO B. RAMOS NETO; CRISTINA POMILLA; LEANDRO SILVEIRA; HEATH SMITH; SAMUEL K. WASSER (Conservation Biology, 2011)
Most protected areas are too small to sustain populations of wide‐ranging mammals; thus, identification and conservation of high‐quality habitat for those animals outside parks is often a high priority, particularly for regions where extensive land conversion is occurring. This is the case in the vicinity of Emas National Park, a small protected area in the Brazilian Cerrado. Over the last 40 years the native vegetation surrounding the park has been converted to agriculture, but the region still supports virtually all of the animals native to the area. We determined the effectiveness of scat‐detection dogs in detecting presence of five species of mammals threatened with extinction by habitat loss: maned wolf ( Chrysocyon brachyurus ), puma ( Puma concolor ), jaguar ( Panthera onca ), giant anteater ( Myrmecophaga tridactyla ), and giant armadillo ( Priodontes maximus ). The probability of scat detection varied among the five species and among survey quadrats of different size, but was consistent across team, season, and year. The probability of occurrence, determined from the presence of scat, in a randomly selected site within the study area ranged from 0.14 for jaguars, which occur primarily in the forested areas of the park, to 0.91 for maned wolves, the most widely distributed species in our study area. Most occurrences of giant armadillos in the park were in open grasslands, but in the agricultural matrix they tended to occur in riparian woodlands. At least one target species occurred in every survey quadrat, and giant armadillos, jaguars, and maned wolves were more likely to be present in quadrats located inside than outside the park. The effort required for detection of scats was highest for the two felids. We were able to detect the presence for each of five wide‐ranging species inside and outside the park and to assign occurrence probabilities to specific survey sites. Thus, scat dogs provide an effective survey tool for rare species even when accurate detection likelihoods are required. We believe the way we used scat‐detection dogs to determine the presence of species can be applied to the detection of other mammalian species in other ecosystems.

A double-resolution transient RCM climate change simulation experiment for near-coastal eastern zone of the Eastern Mediterranean region - S. O. Krichak; J. S. Breitgand; R. Samuels; P. Alpert (Theoretical and Applied Climatology, 2011)

Memantine shows promise in reducing gambling severity and cognitive inflexibility in pathological gambling: a pilot study - Jon E. Grant; Samuel R. Chamberlain; Brian L. Odlaug; Marc N. Potenza; Suck Won Kim (Psychopharmacology, 2010)

Effects of acute modafinil on cognition in trichotillomania - Samuel R. Chamberlain; Jon E. Grant; Anna Costa; Ulrich Müller; Barbara J. Sahakian (Psychopharmacology, 2010)

Are compound leaves an adaptation to seasonal drought or to rapid growth? Evidence from the Amazon rain forest - Ana C. M. Malhado; Robert J. Whittaker; Yadvinder Malhi; Richard J. Ladle; Hans ter Steege; Oliver Phillips; L. E. O. C. Aragão; Timothy R. Baker; Luzmilla Arroyo; Samuel Almeida; Niro Higuchi; Tim J. Killeen; et al. (Global Ecology and Biogeography, 2010)
Aim To assess the hypotheses that compound leaves of trees in the Amazon forest are an adaptation to drought and/or rapid growth. Location Amazon rain forest, South America. Methods Genera from 137 permanent forest plots spread across Amazonia were classified into those with compound leaves and those with simple leaves. Metrics of compound leaf prevalence were then calculated for each plot and regression models that accounted for spatial autocorrelation were used to identify associations between climate variables and compound leaf structure. We also tested for associations between compound leaf structure and a variety of ecological variables related to life history and growth strategies, including wood density, annual increase in diameter and maximum height. Results One plant family, Fabaceae, accounts for 53% of compound‐leaved individuals in the dataset, and has a geographical distribution strongly centred on north‐east Amazonia. On exclusion of Fabaceae from the analysis we found no significant support for the seasonal drought hypothesis. However, we found evidence supporting the rapid growth hypothesis, with possession of compound leaves being associated with faster diameter growth rates and lower wood densities. Main conclusion This study provides evidence that possession of compound leaves constitutes one of a suite of traits and life‐history strategies that promote rapid growth in rain forest trees. Our findings highlight the importance of carefully considering the geographical distribution of dominant taxa and spatial clustering of data points when inferring ecological causation from environment–trait associations.

Automated masking of cloud and cloud shadow for forest change analysis using Landsat images - Chengquan Huang; Nancy Thomas; Samuel N. Goward; Jeffrey G. Masek; Zhiliang Zhu; John R. G. Townshend; James E. Vogelmann (International Journal of Remote Sensing, 2010)

Clinical and neurocognitive changes with modafinil in obsessive–compulsive disorder: a case report - Winand H. Dittrich; Thomas Johansen; Ashwini K. Padhi; Ian E. Smith; Samuel R. Chamberlain; Naomi A. Fineberg (Psychopharmacology, 2010)

Utility of computer simulations in landscape genetics - BRYAN K. EPPERSON; BRAD H. MCRAE; KIM SCRIBNER; SAMUEL A. CUSHMAN; MICHAEL S. ROSENBERG; MARIE‐JOSÉE FORTIN; PATRICK M. A. JAMES; MELANIE MURPHY; STÉPHANIE MANEL; PIERRE LEGENDRE; MARK R. T. DALE (Molecular Ecology, 2010)
Population genetics theory is primarily based on mathematical models in which spatial complexity and temporal variability are largely ignored. In contrast, the field of landscape genetics expressly focuses on how population genetic processes are affected by complex spatial and temporal environmental heterogeneity. It is spatially explicit and relates patterns to processes by combining complex and realistic life histories, behaviours, landscape features and genetic data. Central to landscape genetics is the connection of spatial patterns of genetic variation to the usually highly stochastic space–time processes that create them over both historical and contemporary time periods. The field should benefit from a shift to computer simulation approaches, which enable incorporation of demographic and environmental stochasticity. A key role of simulations is to show how demographic processes such as dispersal or reproduction interact with landscape features to affect probability of site occupancy, population size, and gene flow, which in turn determine spatial genetic structure. Simulations could also be used to compare various statistical methods and determine which have correct type I error or the highest statistical power to correctly identify spatio‐temporal and environmental effects. Simulations may also help in evaluating how specific spatial metrics may be used to project future genetic trends. This article summarizes some of the fundamental aspects of spatial–temporal population genetic processes. It discusses the potential use of simulations to determine how various spatial metrics can be rigorously employed to identify features of interest, including contrasting locus‐specific spatial patterns due to micro‐scale environmental selection.

Hypohydration reduces vertical ground reaction impulse but not jump height - Samuel N. Cheuvront; Robert W. Kenefick; Brett R. Ely; Everett A. Harman; John W. Castellani; Peter N. Frykman; Bradley C. Nindl; Michael N. Sawka (European Journal of Applied Physiology, 2010)

Use of Abundance of One Species as a Surrogate for Abundance of Others - SAMUEL A. CUSHMAN; KEVIN S. McKELVEY; BARRY R. NOON; KEVIN McGARIGAL (Conservation Biology, 2010)
Indicator species concepts have a long history in conservation biology. Arguments in favor of these approaches generally stress expediency and assume efficacy. We tested the premise that the abundance patterns of one species can be used to infer those of other species. Our data consisted of 72,495 bird observations on 55 species across 1046 plots distributed across 30 sub basins. We analyzed abundance patterns at two spatial scales (plot and sub basin) and for empirical and a priori grouping. There were few significant indicator relationships at either scale or under either grouping rule, and those few we found did not explain a substantial portion of the abundance of other species. Coupled with the lack of proven efficacy for species surrogacy in the literature, our results indicate the utility of indicators and similar types of surrogate approaches must be demonstrated rather than assumed.

Improvements in a half degree atmosphere/land version of the CCSM - Peter R. Gent; Stephen G. Yeager; Richard B. Neale; Samuel Levis; David A. Bailey (Climate Dynamics, 2010)

Macronutrient (N, P, K) and Redoximorphic Metal (Fe, Mn) Allocation in Leersia oryzoides (Rice Cutgrass) Grown Under Different Flood Regimes - Samuel C. Pierce; Matt T. Moore; Dan Larsen; S. R. Pezeshki (Water, Air, & Soil Pollution, 2010)

Liposome Damage and Modeling of Fragments of Human Islet Amyloid Polypeptide (IAPP) Support a Two-Step Model of Membrane Destruction - Deborah L. Heyl; Joshua M. Osborne; Sarika Pamarthy; Shyamprasad Samisetti; Andrew W. Gray; Anitha Jayaprakash; Srikanth Konda; Dorothy J. Brown; Samuel R. Miller; Reza Eizadkhah; Maria C. Milletti (International Journal of Peptide Research and Therapeutics, 2010)

IL-33 synergizes with IgE-dependent and IgE-independent agents to promote mast cell and basophil activation - Matthew R. Silver; Alexander Margulis; Nancy Wood; Samuel J. Goldman; Marion Kasaian; Divya Chaudhary (Inflammation Research, 2010)

A Model of the Lower Limb for Analysis of Human Movement - Edith M. Arnold; Samuel R. Ward; Richard L. Lieber; Scott L. Delp (Annals of Biomedical Engineering, 2010)

Strengthening recruitment of exploited scallops Pecten maximus with ocean warming - Samuel Shephard; Bryce Beukers-Stewart; Jan G. Hiddink; Andrew R. Brand; Michel J. Kaiser (Marine Biology, 2010)

Oxidation promotes insertion of the CLIC1 chloride intracellular channel into the membrane - Sophia C. Goodchild; Michael W. Howell; Nicole M. Cordina; Dene R. Littler; Samuel N. Breit; Paul M. G. Curmi; Louise Jennifer Brown (European Biophysics Journal, 2009)

Special issue on evapotranspiration measurement and modeling - Samuel Ortega-Farias; S. Irmak; R. H. Cuenca (Irrigation Science, 2009)

Wolverine gene flow across a narrow climatic niche - Michael K. Schwartz; Jeffrey P. Copeland; Neil J. Anderson; John R. Squires; Robert M. Inman; Kevin S. McKelvey; Kristy L. Pilgrim; Lisette P. Waits; Samuel A. Cushman (Ecology, 2009)
Wolverines ( Gulo gulo ) are one of the rarest carnivores in the contiguous United States. Effective population sizes in Montana, Idaho, and Wyoming, where most of the wolverines in the contiguous United States exist, were calculated to be 35 (credible limits, 28–52) suggesting low abundance. Landscape features that influence wolverine population substructure and gene flow are largely unknown. Recent work has identified strong associations between areas with persistent spring snow and wolverine presence and range. We tested whether a dispersal model in which wolverines prefer to disperse through areas characterized by persistent spring snow cover produced least‐cost paths among all individuals that correlated with genetic distance among individuals. Models simulating large preferences for dispersing within areas characterized by persistent spring snow explained the data better than a model based on Euclidean distance. Partial Mantel tests separating Euclidean distance from spring snow‐cover‐based effects indicated that Euclidean distance was not significant in describing patterns of genetic distance. Because these models indicated that successful dispersal paths followed areas characterized by spring snow cover, we used these understandings to derive empirically based least‐cost corridor maps in the U.S. Rocky Mountains. These corridor maps largely explain previously published population subdivision patterns based on mitochondrial DNA and indicate that natural colonization of the southern Rocky Mountains by wolverines will be difficult but not impossible.

DNA damage- and stress-induced apoptosis occurs independently of PIDD - Ira R. Kim; Kiichi Murakami; Nien-Jung Chen; Samuel D. Saibil; Elzbieta Matysiak-Zablocki; Alisha R. Elford; Madeleine Bonnard; Samuel Benchimol; Andrea Jurisicova; Wen-Chen Yeh; Pamela S. Ohashi (Apoptosis, 2009)

Assessing the applicability of Emiliania huxleyi coccolith morphology as a sea‐surface salinity proxy - Samuel R. Fielding; Jens O. Herrle; Jórg Bollmann; Richard H. Worden; David J. S. Montagnesd (Limnology and Oceanography, 2009)
Culture experiments were used to assess the applicability of Emiliania huxleyi coccolith morphology as a palaeo‐sea‐surface salinity (SSS) proxy. Coccolith morphology was dependent on salinity over a range reflecting present day marine conditions; both coccolith size and the number of coccolith elements increased linearly with increasing salinity. Using regression analysis, the effect of salinity on coccolith morphology was compared to those previously observed in sediment core‐top and plankton data. No significant differences were found between the slopes of these data, suggesting that salinity is the primary control on E. huxleyi coccolith size and element number in the ocean. However, the intercepts of the culture data were significantly higher. A combination of experimental and literature analysis indicated that temperature and nutrients were unlikely to be the causes of this discrepancy. Literature analysis also highlighted that coccolith size data from marginal environments displayed different intercepts to those from the open‐ocean data. This suggests that discrete morphotypes exist in these marginal locations. We, therefore, recommend that the original E. huxleyi coccolith morphology palaeo‐SSS transfer function requires further evaluation before being routinely applied.

Atorvastatin Prevents Hippocampal Cell Death due to Quinolinic Acid-Induced Seizures in Mice by Increasing Akt Phosphorylation and Glutamate Uptake - Tetsadê C. B. Piermartiri; Samuel Vandresen-Filho; Bruno de Araújo Herculano; Wagner C. Martins; Denis Dal’Agnolo; Ellen Stroeh; Cristiane Lima Carqueja; Carina R. Boeck; Carla I. Tasca (Neurotoxicity Research, 2009)

Long‐term natal site‐fidelity by immature lemon sharks ( Negaprion brevirostris ) at a subtropical island - DEMIAN D. CHAPMAN; ELIZABETH A. BABCOCK; SAMUEL H. GRUBER; JOSEPH D. DIBATTISTA; BRYAN R. FRANKS; STEVEN A. KESSEL; TRISTAN GUTTRIDGE; ELLEN K. PIKITCH; KEVIN A. FELDHEIM (Molecular Ecology, 2009)
Although many sharks begin their life confined in nursery habitats, it is unknown how rapidly they disperse away from their natal area once they leave the nursery. We examine this issue in immature lemon sharks ( Negaprion brevirostris ) from the time they leave the nursery (∼ age 3) at a subtropical island (Bimini, Bahamas), through to the onset of sexual maturity (∼ age 12). From 1995 to 2007 we tagged and genotyped a large fraction of the nursery‐bound sharks at this location (0–3 years of age, N = 1776 individuals). From 2003 to 2007 we sampled immature sharks aged from 3 to 11 years ( N = 150) living around the island and used physical/genetic tag recaptures coupled with kinship analysis to determine whether or not each of these ‘large immature sharks’ was locally born. We show that many island‐born lemon sharks remain close to their natal area for long periods (years) after leaving the nursery; more than half of the sampled sharks up to 135 cm total length (∼6 years old) were locally born. The fraction of locally born sharks gradually declined with increasing shark size, indicating that dispersal is relatively slow and does not primarily occur after sharks reach a threshold size. Local conservation measures (e.g. localized fishery closures, marine protected areas) can therefore help protect island‐born lemon sharks even after they leave the nursery habitat.

Factor analysis for El Niño signals in sea surface temperature and precipitation - Christine K. Lee; Samuel S. P. Shen; Barbara Bailey; Gerald R. North (Theoretical and Applied Climatology, 2009)

CCC and Prohexadione-Ca Enhance Rhizome Growth and Lateral Bud Production in Rhubarb (Rheum rhabarbarum L.) - Usha P. Rayirath; Rajasekaran R. Lada; Claude D. Caldwell; Samuel K. Asiedu; Kevin J. Sibley; Azure D. Adams (Journal of Plant Growth Regulation, 2009)

What signs and symptoms would be expected after ingestion of this plant? - Samuel J. Stellpflug; Carson R. Harris (Journal of Medical Toxicology, 2009)

The effect of temperature on the coupling between phosphorus and growth in lacustrine bacterioplankton communities - Edward K. Hall; Andrew R. Dzialowski; Samuel M. Stoxen; James B. Cotner (Limnology and Oceanography, 2009)
Phosphorus (P) routinely limits microbial growth in freshwater ecosystems. The growth rate hypothesis (GRH) relates growth to biomass P content mechanistically through changes in ribosomal ribonucleic acid (rRNA). Although the GRH has been shown in cultured bacteria, less well understood is how GRH relationships are affected by interactions with environmental parameters such as temperature. To address this, we evaluated the relationship between bacterial biomass P, RNA: deoxyribonucleic acid (DNA) ratio, and growth rate in 47 northern temperate lakes. Although RNA:DNA ratio was positively correlated with bacterial biomass P : carbon (C), we found no correlation between growth rate and RNA:DNA or between growth rate and biomass P : C. There was, however, a significant effect of temperature on biomass P : C. We investigated the effect of temperature more directly using filter‐separated bacterial communities from two lakes during two seasons while experimentally manipulating temperature and resources. For the summer communities, bacterial production (BP) and biomass P were positively correlated, and the slope of that relationship increased with increasing temperature. In winter communities, BP and biomass P were again positively correlated; however, the slope of that relationship decreased with increasing temperature. The slope of the relationship between BP and biomass P is a metric of nutrient use efficiency and was strongly influenced by temperature. More importantly, bacterioplankton demonstrated seasonal acclimation or adaptation to in situ temperature, suggesting that studies evaluating multiple communities in time and space fail to find a clear relationship between temperature and bacterial metabolism because bacterial communities are locally adapted to in situ temperature.

Comprehensive assessment of carbon productivity, allocation and storage in three Amazonian forests - YADVINDER MALHI; LUIZ EDUARDO O. C. ARAGÃO; DANIEL B. METCALFE; ROMILDA PAIVA; CARLOS A. QUESADA; SAMUEL ALMEIDA; LIANA ANDERSON; PAULO BRANDO; JEFFREY Q. CHAMBERS; ANTONIO C. L. Da COSTA; LUCY R. HUTYRA; PAULO OLIVEIRA; et al. (Global Change Biology, 2009)
The allocation and cycling of carbon (C) within forests is an important component of the biospheric C cycle, but is particularly understudied within tropical forests. We synthesise reported and unpublished results from three lowland rainforest sites in Amazonia (in the regions of Manaus, Tapajós and Caxiuanã), all major sites of the Large‐Scale Biosphere–Atmosphere Programme (LBA). We attempt a comprehensive synthesis of the C stocks, nutrient status and, particularly, the allocation and internal C dynamics of all three sites. The calculated net primary productivities (NPP) are 10.1±1.4 Mg C ha −1 yr −1 (Manaus), 14.4±1.3 Mg C ha −1 yr −1 (Tapajós) and 10.0±1.2 Mg C ha −1 yr −1 (Caxiuanã). All errors bars report standard errors. Soil and leaf nutrient analyses indicate that Tapajós has significantly more plant‐available phosphorus and calcium. Autotrophic respiration at all three sites (14.9–21.4 Mg C ha yr −1 ) is more challenging to measure, with the largest component and greatest source of uncertainty being leaf dark respiration. Comparison of measured soil respiration with that predicted from C cycling measurements provides an independent constraint. It shows general good agreement at all three sites, with perhaps some evidence for measured soil respiration being less than expected. Twenty to thirty percent of fixed C is allocated belowground. Comparison of gross primary productivity (GPP), derived from ecosystem flux measurements with that derived from component studies (NPP plus autotrophic respiration) provides an additional crosscheck. The two approaches are in good agreement, giving increased confidence in both approaches to estimating GPP. The ecosystem carbon‐use efficiency (CUEs), the ratio of NPP to GPP, is similar at Manaus (0.34±0.10) and Caxiuanã (0.32±0.07), but may be higher at Tapajós (0.49±0.16), although the difference is not significant. Old growth or infertile tropical forests may have low CUE compared with recently disturbed and/or fertile forests.

Ground-Cover Measurements: Assessing Correlation Among Aerial and Ground-Based Methods - D. Terrance Booth; Samuel E. Cox; Tim Meikle; Hans R. Zuuring (Environmental Management, 2008)

Effects of large-scale anthropogenic development on juvenile lemon shark (Negaprion brevirostris) populations of Bimini, Bahamas - David E. Jennings; Samuel H. Gruber; Bryan R. Franks; Steven T. Kessel; Anne L. Robertson (Environmental Biology of Fishes, 2008)

Effects of sertoli cell-conditioned medium on ventral midbrain neural stem cells: A preliminary report - Rania Shamekh; Samuel Saporta; Don F. Cameron; Alison E. Willing; Cindy D. Sanberg; Karl Johe; P. R. Sanberg (Neurotoxicity Research, 2008)

Efficacy of body ventilation system for reducing strain in warm and hot climates - Troy D. Chinevere; Bruce S. Cadarette; Daniel A. Goodman; Brett R. Ely; Samuel N. Cheuvront; Michael N. Sawka (European Journal of Applied Physiology, 2008)

Inhibitory effects of short-term administration of dl-α-lipoic acid on oxidative vulnerability induced by Aβ amyloid fibrils (25–35) in mice - E. Philip Jesudason; J. Gunasingh Masilamoni; Ben S. Ashok; B’joe Baben; V. Arul; K. Samuel Jesudoss; W. Charles E. Jebaraj; S. Dhandayuthapani; S. Vignesh; R. Jayakumar (Molecular and Cellular Biochemistry, 2008)

Liver Ischemia and Ischemia–Reperfusion Induces and Trafficks the Multi-specific Metal Transporter Atp7b to Bile Duct Canaliculi: Possible Preferential Transport of Iron into Bile - John A. Goss; Neal R. Barshes; Saul J. Karpen; Feng-Qin Gao; Samuel Wyllie (Biological Trace Element Research, 2008)

Colonization history of the Swiss Rhine basin by the bullhead ( Cottus gobio ): inference under a Bayesian spatially explicit framework - SAMUEL NEUENSCHWANDER; CARLO R. LARGIADÈR; NICOLAS RAY; MATHIAS CURRAT; PASCAL VONLANTHEN; LAURENT EXCOFFIER (Molecular Ecology, 2008)
The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20 000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead ( Cottus gobio ), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molecular diversity of eight sampled populations is simulated and compared to observed data at six microsatellite loci under an approximate Bayesian computation framework to estimate the parameters of the colonization process. Our demographic estimates fit well with current knowledge about the biology of this species, but they suggest that the Swiss Rhine basin was colonized very recently, after the Younger Dryas some 6600 years ago. We discuss the implication of this result, as well as the strengths and limits of the spatially explicit approach coupled to the approximate Bayesian computation framework.

Variability of Electrode Positions Using Electrode Caps - Samuel R. Atcherson; Herbert Jay Gould; Monique A. Pousson; Tina M. Prout (Brain Topography, 2007)

Arousal and the pupil: why diazepam-induced sedation is not accompanied by miosis - R. H. Hou; E. R. Samuels; R. W. Langley; E. Szabadi; C. M. Bradshaw (Psychopharmacology, 2007)

A Resistant‐Kernel Model of Connectivity for Amphibians that Breed in Vernal Pools - BRADLEY W. COMPTON; KEVIN McGARIGAL; SAMUEL A. CUSHMAN; LLOYD R. GAMBLE (Conservation Biology, 2007)
Pool‐breeding amphibian populations operate at multiple scales, from the individual pool to surrounding upland habitat to clusters of pools. When metapopulation dynamics play a role in long‐term viability, conservation efforts limited to the protection of individual pools or even pools with associated upland habitat may be ineffective over the long term if connectivity among pools is not maintained. Connectivity becomes especially important and difficult to assess in regions where suburban sprawl is rapidly increasing land development, road density, and traffic rates. We developed a model of connectivity among vernal pools for the four ambystomatid salamanders that occur in Massachusetts and applied it to the nearly 30,000 potential ephemeral wetlands across the state. The model was based on a modification of the kernel estimator (a density estimator commonly used in home range studies) that takes landscape resistance into account. The model was parameterized with empirical migration distances for spotted salamanders ( Ambystoma maculatum ), dispersal distances for marbled salamanders ( A. opacum ), and expert‐derived estimates of landscape resistance. The model ranked vernal pools in Massachusetts by local, neighborhood, and regional connectivity and by an integrated measure of connectivity, both statewide and within ecoregions. The most functionally connected pool complexes occurred in southeastern and northeastern Massachusetts, areas with rapidly increasing suburban development. In a sensitivity analysis estimates of pool connectivity were relatively insensitive to uncertainty in parameter estimates, especially at the local and neighborhood scales. Our connectivity model could be used to prioritize conservation efforts for vernal‐pool amphibian populations at broader scales than traditional pool‐based approaches.

Headwater Riparian Microclimate Patterns under Alternative Forest Management Treatments - Jessica J. Rykken; Samuel S. Chan; Andrew R. Moldenke (Forest Science, 2007)
Management of headwater streams and their riparian zones has included the implementation of forested riparian buffers, which are intended to protect ecological processes (such as microclimate) and biota, but the appropriate widths for these buffers have been widely debated. We measured the magnitude and extent of microclimatic gradients associated with headwater streams in mature unmanaged forests, and determined whether these patterns were maintained in clearcut harvested units with and without a 30 m-wide riparian buffer on each side of the stream. We measured air temperature, soil temperature, and relative humidity between 1 and 70 m from the stream in five replicate blocks of three treatments each in western Oregon. Results indicated the strongest stream effect on air temperature and relative humidity to be within 10 m of the stream in all management treatments at 3:00 pm, and gradients were evident to 20 m in the forested treatment. The clearcut was significantly hotter (air and soil) and drier than either the riparian buffer or the forest treatments at 3:00 pm. The riparian buffer and forest had similar microclimates at all distances from the stream, suggesting that the 30-m buffer adequately protected the riparian microclimatic gradient. We hypothesize that the strong stream effect on microclimate in the riparian zone serves a critical role in mitigating the influence of microclimatic “edge effects” associated with the forest-clearcut edge. Biota dependent on cool, humid microclimates provided by riparian zones will benefit from the implementation of riparian buffers in harvest units.

Periphyton and Macroinvertebrate Assemblage Structure in Headwaters Bordered by Mature, Thinned, and Clearcut Douglas-Fir Stands - Robert J. Danehy; Samuel S. Chan; Gary T. Lester; Russell B. Langshaw; Ted R. Turner (Forest Science, 2007)
We examined the structure of periphyton and macroinvertebrate assemblages in 18 Oregon Coast Range perennial headwater streams bordered by mature (6), clearcut (5), and thinned (7) forest treatments. Summer base flow discharge ranged from 0.02 to1.98 l/s (mean − 0.5 l/s). Periphyton was almost entirely diatoms (72 species) and assemblage characteristics were most strongly influenced by substrate characteristics. Mature treatment sites had fewer species of diatoms and less biomass than other treatments. Diatom richness was highest at sites with higher unit area discharge. Diatom assemblages were dominated by a single species (Achnanthes lanceolata [Brébisson] Grunow), which composed more than 50% relative abundance of the assemblage at nine sites. Macroinvertebrate assemblages were rich, with 194 taxa collected across all sites and 42 taxa found at a single site. Macroinvertebrate assemblages differed across treatments with higher abundance, more Chironomidae taxa, and more biomass at the clearcut treatment sites. We observed no difference in functional feeding group percentage composition across treatments, with collector-gatherers and shredders composing at least 50% abundance at all treatments. We found little difference in either periphyton or macroinvertebrate assemblages between thinned and mature treatments.

Characterization of Aeromonas Virulence Using an Immunocompromised Mouse Model - Dennis J. Lye; Mark R. Rodgers; Gerard Stelma; Stephen J. Vesper; Samuel L. Hayes (Current Microbiology, 2007)

Characterization and in vitro Cytotoxicity Testing of Ethanolamine-derived Cadmium Chelating Agents - Mikhail Zhukalin; Megan K. Blanksma; T. Dimitri Silva; Samuel W. Suyehira; Wendy A. Harvey; Sara J. Heggland; Peter R. Craig (BioMetals, 2007)

Long-Term Stability of N1 Sources Using Low-Resolution Electromagnetic Tomography - Samuel R. Atcherson; Herbert Jay Gould; Monique A. Pousson; Tina M. Prout (Brain Topography, 2006)

Production of endothelial nitric oxide synthase (eNOS) over-expressing piglets - Y. H. Hao; H. Y. Yong; C. N. Murphy; D. Wax; M. Samuel; A. Rieke; L. Lai; Z. Liu; D. C. Durtschi; V. R. Welbern; E. M. Price; R. M. McAllister; et al. (Transgenic Research, 2006)

Tetracycline-inducible gene expression in mycobacteria within an animal host using modified Streptomyces tcp830 regulatory elements - S. Moises Hernandez-Abanto; Samuel C. Woolwine; Sanjay K. Jain; W. R. Bishai (Archives of Microbiology, 2006)

Noradrenergic modulation of working memory and emotional memory in humans - Samuel R. Chamberlain; Ulrich Müller; Andrew D. Blackwell; Trevor W. Robbins; Barbara J. Sahakian (Psychopharmacology, 2006)

Comparison of pramipexole and amisulpride on alertness, autonomic and endocrine functions in healthy volunteers - E. R. Samuels; R. H. Hou; R. W. Langley; E. Szabadi; C. M. Bradshaw (Psychopharmacology, 2006)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Oral trophallaxis in adult leaf-cutting ants Acromyrmex subterraneus subterraneus (Hymenoptera, Formicidae) - D. D. O. Moreira; M. Erthal; M. P. Carrera; C. P. Silva; R. I. Samuels (Insectes Sociaux, 2006)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Phylogenetics of Quiinaceae (Malpighiales): evidence from trnL-trnF sequence data and morphology - J. V. Schneider; U. Swenson; R. Samuel; T. Stuessy; G. Zizka (Plant Systematics and Evolution, 2006)

Ants can sort their brood without a gaseous template - Samuel R. Scholes; Ana B. Sendova-Franks; S. Tim Swift; Chris Melhuish (Behavioral Ecology and Sociobiology, 2006)

Why patients with Alzheimer’s disease may show increased sensitivity to tropicamide eye drops: role of locus coeruleus - R. H. Hou; E. R. Samuels; M. Raisi; R. W. Langley; E. Szabadi; C. M. Bradshaw (Psychopharmacology, 2006)

Formulation of an ocean model for global climate simulations - S. M. Griffies; A. Gnanadesikan; K. W. Dixon; J. P. Dunne; R. Gerdes; M. J. Harrison; A. Rosati; J. L. Russell; B. L. Samuels; M. J. Spelman; M. Winton; R. Zhang (Ocean Science, 2005)
This paper summarizes the formulation of the ocean component to the Geophysical Fluid Dynamics Laboratory's (GFDL) climate model used for the 4th IPCC Assessment (AR4) of global climate change. In particular, it reviews the numerical schemes and physical parameterizations that make up an ocean climate model and how these schemes are pieced together for use in a state-of-the-art climate model. Features of the model described here include the following: (1) tripolar grid to resolve the Arctic Ocean without polar filtering, (2) partial bottom step representation of topography to better represent topographically influenced advective and wave processes, (3) more accurate equation of state, (4) three-dimensional flux limited tracer advection to reduce overshoots and undershoots, (5) incorporation of regional climatological variability in shortwave penetration, (6) neutral physics parameterization for representation of the pathways of tracer transport, (7) staggered time stepping for tracer conservation and numerical efficiency, (8) anisotropic horizontal viscosities for representation of equatorial currents, (9) parameterization of exchange with marginal seas, (10) incorporation of a free surface that accomodates a dynamic ice model and wave propagation, (11) transport of water across the ocean free surface to eliminate unphysical ``virtual tracer flux" methods, (12) parameterization of tidal mixing on continental shelves. We also present preliminary analyses of two particularly important sensitivities isolated during the development process, namely the details of how parameterized subgridscale eddies transport momentum and tracers.

Sprout development and processing quality changes in potato tubers stored under ethylene: 1. Effects of ethylene concentration - Barbara J. Daniels-Lake; Robert K. Prange; Jerzy Nowak; Samuel K. Asiedu; John R. Walsh (American Journal of Potato Research, 2005)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

First steps in understanding the export of lipids to the plant cuticle - L Samuels; R Jetter; L Kunst (Plant Biosystems, 2005)

The protective role of DL-?-lipoic acid in the oxidative vulnerability triggered by A?-amyloid vaccination in mice - E. Philip Jesudason; J. Gunasingh Masilamoni; K. Samuel Jesudoss; R. Jayakumar (Molecular and Cellular Biochemistry, 2005)

Evaluation of Optically Acquired Zooplankton Size-Spectrum Data as a Potential Tool for Assessment of Condition in the Great Lakes - Peder Yurista; John R. Kelly; Samuel Miller (Environmental Management, 2005)

Nitrogen mineralization in a pecan (Carya illinoensis K. Koch)?cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P. K. R. Nair; Barry J. Brecke; Vimala D. Nair; Donald A. Graetz; Craig L. Ramsey (Biology and Fertility of Soils, 2005)

A Multiscale Landscape Approach to Predicting Bird and Moth Rarity Hotspots in a Threatened Pitch Pine–Scrub Oak Community - JOANNA GRAND; JOHN BUONACCORSI; SAMUEL A. CUSHMAN; CURTICE R. GRIFFIN; MAILE C. NEEL (Conservation Biology, 2004)
In the northeastern United States, pitch pine ( Pinus rigida Mill.)–scrub oak ( Quercus ilicifolia Wang.) communities are increasingly threatened by development and fire suppression, and prioritization of these habitats for conservation is of critical importance. As a basis for local conservation planning in a pitch pine–scrub oak community in southeastern Massachusetts, we developed logistic‐regression models based on multiscale landscape and patch variables to predict hotspots of rare and declining bird and moth species. We compared predicted moth distributions with observed species‐occurrence records to validate the models. We then quantified the amount of overlap between hotspots to assess the utility of rare birds and moths as indicator taxa. Species representation in hotspots and the current level of hotspot protection were also assessed. Predictive models included variables at all measured scales and resulted in average correct classification rates (optimal cut point) of 85.6% and 89.2% for bird and moth models, respectively. The majority of moth occurrence records were within 100 m of predicted habitat. Only 13% of all bird hotspots and 10% of all moth hotspots overlapped, and only a few small patches in and around Myles Standish State Forest were predicted to be hotspots for both taxa. There was no correlation between the bird and moth species‐richness maps across all levels of richness ( r =−0.03, p = 0.62). Species representation in hotspots was high, but most hotspots had limited or no protection. Given the lack of correspondence between bird and moth hotspots, our results suggest that use of species‐richness indicators for conservation planning may be ineffective at local scales. Based on these results, we suggest that local‐level conservation planning in pitch pine–scrub oak communities be based on multitaxa, multiscale approaches.

Variation in wood density determines spatial patterns inAmazonian forest biomass - Timothy R. Baker; Oliver L. Phillips; Yadvinder Malhi; Samuel Almeida; Luzmila Arroyo; Anthony Di Fiore; Terry Erwin; Timothy J. Killeen; Susan G. Laurance; William F. Laurance; Simon L. Lewis; Jon Lloyd; et al. (Global Change Biology, 2004)
Uncertainty in biomass estimates is one of the greatest limitations to models of carbon flux in tropical forests. Previous comparisons of field‐based estimates of the aboveground biomass (AGB) of trees greater than 10 cm diameter within Amazonia have been limited by the paucity of data for western Amazon forests, and the use of site‐specific methods to estimate biomass from inventory data. In addition, the role of regional variation in stand‐level wood specific gravity has not previously been considered. Using data from 56 mature forest plots across Amazonia, we consider the relative roles of species composition (wood specific gravity) and forest structure (basal area) in determining variation in AGB. Mean stand‐level wood specific gravity, on a per stem basis, is 15.8% higher in forests in central and eastern, compared with northwestern Amazonia. This pattern is due to the higher diversity and abundance of taxa with high specific gravity values in central and eastern Amazonia, and the greater diversity and abundance of taxa with low specific gravity values in western Amazonia. For two estimates of AGB derived using different allometric equations, basal area explains 51.7% and 63.4%, and stand‐level specific gravity 45.4% and 29.7%, of the total variation in AGB. The variation in specific gravity is important because it determines the regional scale, spatial pattern of AGB. When weighting by specific gravity is included, central and eastern Amazon forests have significantly higher AGB than stands in northwest or southwest Amazonia. The regional‐scale pattern of species composition therefore defines a broad gradient of AGB across Amazonia.

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Hypothesis: the act of taking a Papanicolaou smear reduces the prevalence of human papillomavirus infection: a potential impact on the risk of cervical cancer - Samuel Shapiro; Henri Carrara; Bruce R. Allan; Margaret Hoffman; Lynn Rosenberg; Judith P Kelly; Diane D Cooper; Anna-Lise Williamson (Cancer Causes & Control, 2003)

Genetics of colonization in Hypochaeris tenuifolia (Asteraceae, Lactuceae) on Volcán Lonquimay, Chile - K. Tremetsberger; T. F. Stuessy; R. M. Samuel; C. M. Baeza; M. F. Fay (Molecular Ecology, 2003)
Understanding the genetics of colonizing populations has been, and continues to remain, an important focus in evolutionary biology. Different theoretical models predict varying levels of genetic variation in colonizing populations depending upon strength of founder effect, gene flow and rate of population growth and immigration following colonization. We analyse overall genetic variation using amplified fragment length polymorphism markers in colonizing populations of Hypochaeris tenuifolia (Asteraceae) in the southern Andes. Volcán Lonquimay newly erupted on 25 December 1988, producing a side cone, La Navidad, and sent lava and ash into surrounding areas. Many domesticated animals (estimated at 10 000) and many natural plant populations were destroyed. Into this new open habitat have come immigrant populations of several angiosperm species, most conspicuously H. tenuifolia that forms leaf rosettes with flowering scapes to 15 cm and orange–yellow heads 1–2 cm in diameter. Genetic diversity in five founder populations in the eruption zone is compared with that from five nearby survivor populations, as well as with eight isolated northern and four southern populations from throughout the entire range of the species in Chile. Results from 477 individuals representing 447 different multilocus phenotypes, yielded 170 DNA fragments of which 144 (85%) were polymorphic. Genetic diversity within founder populations is neither lower than in survivor populations nor in isolated populations throughout the range of the species, but it is lower among founder populations than among other populations immediately and distantly outside the zone of disturbance. Closest genetic similarity occurs between founders and nearby survivor populations as well as those in adjacent southern regions.

Risk of invasive cancer of the cervix in relation to the use of injectable progestogen contraceptives and combined estrogen/progestogen oral contraceptives (South Africa) - Samuel Shapiro; Lynn Rosenberg; Margaret Hoffman; Judith P. Kelly; Diane D. Cooper; Henri Carrara; Lynnette E. Denny; George du Toit; Bruce R. Allan; Ilse A. Stander; Anna-Lise Williamson (Cancer Causes & Control, 2003)

Effects of Sertoli cell transplants in a 3-nitropropionic acid model of early Huntington's disease: a preliminary study - Alba I. Rodriguez; Alison E. Willing; Samuel Saporta; Don F. Cameron; Paul R. Sanberg (Neurotoxicity Research, 2003)

Ultrastructure of vascular cambial cell cytokinesis in pine seedlings preserved by cryofixation and substitution - K. H. Rensing; A. L. Samuels; R. A. Savidge (Protoplasma, 2002)

Analysis of Poly(D,L-Lactic-Co-Glycolic Acid) Nanosphere Uptake by Human Dendritic Cells and Macrophages In Vitro - M. E. Christine Lutsiak; Deborah R. Robinson; Conrad Coester; Glen S. Kwon; John Samuel (Pharmaceutical Research, 2002)

Multiple origins of Southern Hemisphere Anemone (Ranunculaceae) based on plastid and nuclear sequence data - E. Schuettpelz; S. B. Hoot; R. Samuel; F. Ehrendorfer (Plant Systematics and Evolution, 2002)

Neurobehavioral assessment of transplanted porcine Sertoli cells into the intact rat striatum - Alba I. Rodríguez; Alison E. Willing; Don F. Cameron; Samuel Saporta; Paul R. Sanberg (Neurotoxicity Research, 2002)

Preliminary study of the behavioral effects of LBS-neuron implantation on seizure susceptibility following middle cerebral artery occlusion in the rat - Alison E. Willing; Samuel Saporta; Jiang Lixian; Melissa Milliken; Steve Poulos; Scott S. Bowersox; Paul R. Sanberg (Neurotoxicity Research, 2002)

SPERM WHALE DIVES TRACKED BY RADIO TAG TELEMETRY - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Paul W. Howey; Romaine R. Maiefski (Marine Mammal Science, 2002)
A bstract Dives of a 12‐m sperm whale ( Physeter catodon Linnaeus, 1758) were tracked in the southeast Caribbean by long range, 30 MHz radio tag with dive‐profile telemetry over 4.6 d, 26 April‐1 May 1995. Over the 295‐km track, average speed was 0.7 m/sec (2.6 km/h). Of 158 dives (defined as submergences longer than 3 min), 65 were shallow (

Diagnosis of foot-and-mouth disease by RT-PCR: use of phylogenetic data to evaluate primers for the typing of viral RNA in clinical samples - S. M. Reid; N. P. Ferris; G. H. Hutchings; K. De Clercq; B. J. Newman; N. J. Knowles; A. R. Samuel (Archives of Virology, 2001)

The home stretch, a first analysis of the nearly completed genome of Rhodobacter sphaeroides 2.4.1 - Chris Mackenzie; Madhusudan Choudhary; Frank W. Larimer; Paul F. Predki; Stephanie Stilwagen; Judith P. Armitage; Robert D. Barber; Timothy J. Donohue; Jonathan P. Hosler; Jack E. Newman; James P. Shapleigh; R. Elizabeth Sockett; et al. (Photosynthesis Research, 2001)

Genotypic and Phenotypic Evidence of Different Drug-Resistance Mutation Patterns between B and Non-B Subtype Isolates of Human Immunodeficiency Virus Type 1 found in Brazilian Patients Failing HAART - Elena Caride; Kurt Hertogs; Brendan Larder; Pascale Dehertogh; Rodrigo Brindeiro; Elizabeth Machado; Carlos A.M. De Sá; Walter A. Eyer-Silva; Fernando Samuel Sion; Luiz F.C. Passioni; Jaqueline A. Menezes; Alexandre R. Calazans; et al. (Virus Genes, 2001)

Biogeochemical and physical factors influencing seawater ƒCO 2 and air‐sea CO 2 exchange on the Bermuda coral reef - Nicholas R. Bates; Leone Samuels; Liliane Merlivat (Limnology and Oceanography, 2001)
It is uncertain whether coral reef ecosystems are oceanic sources or sinks of carbon dioxide (CO 2 ). Understanding the complex interactions between biogeochemical and physical processes within reef ecosystems is important for determining the contribution of coral reefs to the global carbon cycle and the air‐sea flux of CO2 . The influence of biogeochemical and physical processes on CO 2 cycling was examined for 1 month at Hog Reef Flat, part of the rim reef of Bermuda. The fugacity of seawater CO 2 (CO 2 ) was measured hourly by use of a Carbon Interface Ocean Atmosphere buoy, providing the longest time series of seawater CO 2 data on a coral reef ecosystem. Seawater CO 2 ranged from ~340 to 470 µatm, with a diurnal variability ranging from ~20–60 µatm. Air‐sea CO 2 was directed from ocean to atmosphere with a mean flux of 3.3 ± 4.6 mmoles CO 2 m −2 d −1 . The reef data are compared with a seawater CO 2 time series collected at the U.S. Joint Global Ocean Flux Study Bermuda Atlantic Time‐series Study (BATS) site (31°50'N, 64°10'W) in the Sargasso Sea surrounding Bermuda. Sargasso Sea waters are the original source for Bermuda platform water, providing a context for understanding the biogeochemical modification of reef water at Hog Reef Flat. Seawater fCO 2 at Hog Reef Flat was elevated relative to the Sargasso Sea by ~0 to ~120 µatm, primarily as a result of calcium carbonate production. However, the ability of the reef to act either as a source or sink of CO 2 to/from the atmosphere largely depended on the air‐sea CO 2 disequilibrium of offshore Sargasso Sea waters impinging on the reef site. This study also revealed that an assessment of the fate of CO 2 on coral reefs is dependent on understanding the reef's physical regime and forcing. The dynamics of wind, tide, platform circulation, and fluxes of offshore or onshore waters are necessary context for all coral reef sites.

The 18 kDa Antigen of Theileria equi is a Specific but Less Abundant Protein Also Expressed by Parasites Cultured In Vitro - T. Samuel; R. Böse (Veterinary Research Communications, 2001)

Review of Elasmobranch Behavioral Studies Using Ultrasonic Telemetry with Special Reference to the Lemon Shark, Negaprion Brevirostris, Around Bimini Islands, Bahamas - L. Fredrik Sundström; Samuel H. Gruber; Susi M. Clermont; João P.S. Correia; Jean R.C. de Marignac; John F. Morrissey; Courtney R. Lowrance; Lori Thomassen; Miguel T. Oliveira (Environmental Biology of Fishes, 2001)

Risk of ovarian cancer according to use of antidepressants, phenothiazines, and benzodiazepines (United States) - Patricia F. Coogan; Lynn Rosenberg; Julie R. Palmer; Brian L. Strom; Paul D. Stolley; Ann G. Zauber; Samuel Shapiro (Cancer Causes & Control, 2000)

Molecular typing of Salmonella weltevreden and Salmonella chincol by pulsed-field gel electrophoresis (PFGE) and enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) - A.M. Sahilah; R. Son; G. Rusul; L. Samuel; Z. Hassan; K.Y. Lum; M.A. Ahmad (World Journal of Microbiology and Biotechnology, 2000)

Simulation Studies of Vestibular Macular Afferent-Discharge Patterns Using a New, Quasi-3-D Finite Volume Method - Muriel D. Ross; Samuel W. Linton; Bruce R. Parnas (Journal of Computational Neuroscience, 2000)

SPERM WHALE SURFACE ACTIVITY FROM TRACKING BY RADIO AND SATELLITE TAGS 1 - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Damon P. Gannon; Paul W. Howey; Romaine R. Maiefski; Trevor R. Spradlin (Marine Mammal Science, 1999)
A bstract Three 12‐m sperm whales ( Physeter catodon ) were tagged and tracked west of Dominica in the southeast Caribbean to follow the surfacing patterns and movements of these presumed subadult males. Whale N was tagged in April 1993 with a 30‐MHz radio tag and tracked for two days. Whale H was tagged in April 1995 with a 30‐MHz radio tag and tracked for 4.6 d. Whale A was tagged in April 1995 with a satellite‐monitored tag tracked by ARGOS for 21.5 d, the first four of which were concurrent with the tracking of Whale H, an associate. The tagged whales remained west of Dominica for at least 2, 5, and 13 d, respectively. Whales N and A then moved southward to waters off Martinique. There were no apparent effects on the whales by tagging or the presence of the tags. The whales averaged speeds of 2.6‐3.5 km/h. Surfacings, indicated by tag signals, were of two types: short surfacings apparently primarily for respiration, averaging 7‐10.5 min between repeated longer dives, occurring day and night; and extended surfacings seemingly for rest and social interactions with conspecifics, occurring mostly in daylight. Whales were near the surface for 20.4%–22.6% of the total time (26.6%–27.1% during the day and 14.9%–17.1% at night). Delayed blowing was observed as Whale N surfaced for 8.3 min between 47‐ and 45‐min dives but delayed the first of its 31 blows for 1.5 min after surfacing.

Impact of urban development on the chemical composition of ground water in a fen-wetland complex - Samuel V. Panno; Victoria A. Nuzzo; Keros Cartwright; Bruce R. Hensel; Ivan G. Krapac (Wetlands, 1999)

The diagnosis of renal cell cancer in relation to hypertension (United States) - Lynn Rosenberg; Wendy P. Stephenson; R. Sowmya Rao; Julie R. Palmer; Brian L. Strom; Samuel Shapiro (Cancer Causes & Control, 1998)

Abundance and properties of dissolved organic matter in pore waters of a freshwater wetland - Yu‐Ping Chin; Samuel J. Traina; Cathleen R. Swank; Debera Backhus (Limnology and Oceanography, 1998)
The abundances, molecular weights, molar absorptivities, and polydispersities of sediment pore water dissolved organic matter (DOM) and ferrous iron, Fe(II), were measured from three sites within a freshwater wetland (Old Woman Creek) adjacent to Lake Erie. DOM concentrations (expressed as organic carbon) increased with depth. Number‐average molecular weight, weight‐average molecular weight, and molar absorptivities (at 280 nm) also increased with depth up to 5 cm and remained relatively constant below this depth. These properties are indicative of the respective changes in the size of the DOM constituents and the number of aromatic moieties present. Moreover, a strong correlation was observed between Fe(II) and DOM, which suggests that both constituents coaccumulate in these pore fluids, It is hypothesized that reductionof iron oxides coated with organic matter releases both DOM and Fe(II). Increases in the molecular weights and molar absorptivities of the DOM constituents suggest that the “sorbed” component released by iron oxide dissolution is composed of larger and more aromatic molecules. The molecular‐weight data also suggest that much of the refractory organic carbon in the interstitial waters comprises smaller‐than‐expected polymeric molecules. Thus, the release of the sorbed organic materials during the reductive dissolution of the oxide phases in anoxic sediments coupled with the selective preservation of refractory organic components may play an important role in both the DOM‐mediated fate of pollutants and the cycling of carbon in wetlands.

Characterizing sequence variation in the VP1 capsid proteins of foot and mouth disease virus (serotype 0) with respect to virion structure - Daniel Haydon; Susan Lea; Liz Fry; Nick Knowles; Alan R. Samuel; David Stuart; Mark E. J. Woolhouse (Journal of Molecular Evolution, 1998)

Mechanism of Ca ++ Release from the Sarcoplasmic Reticulum: A Computer Model - Arkady Glukhovsky; Dan R. Adam; Giora Amitzur; Samuel Sideman (Annals of Biomedical Engineering, 1998)

Transitional cell cancer of the urinary tract and renal cell cancer in relation to acetaminophen use (United States) - Lynn Rosenberg; R. Sowmya Rao; Julie R. Palmer; Brian L. Strom; Ann Zauber; M. Ellen Warshauer; Paul D. Stolley; Samuel Shapiro (Cancer Causes & Control, 1998)

Induced and spontaneous abortion in relation to risk of breast cancer (United States) - Julie R. Palmer; Lynn Rosenberg; R. Sowmya Rao; Ann Zauber; Brian L. Strom; M. Ellen Warshauer; Paul D. Stolley; Samuel Shapiro (Cancer Causes & Control, 1997)

Antigenic analysis of type O foot-and-mouth disease virus in the persistently infected bovine - J. S. Salt; A. R. Samuel; R. P. Kitching (Archives of Virology, 1996)

The twisting of the heart during contraction - Hans R. Chaudhry; Rafael Beyar; Haim Azhari; Samuel Sideman (Annals of Biomedical Engineering, 1996)

Serial passage in tissue culture of mixed foot-and-mouth disease virus serotypes - E. L. Woodbury; A. R. Samuel; N. J. Knowles (Archives of Virology, 1995)

Specific cleavage of Sendai virus nucleocapsid protein subunits during virus storage - L. M. Popa; Rodica Repanovici; I. Samuel; R. Portocala (Archives of Virology, 1975)

Primate hemoglobins: Some sequences and some proposals concerning the character of evolution and mutation - Samuel H. Boyer; Emilio F. Crosby; Andrea N. Noyes; Gail F. Fuller; Sanford E. Leslie; Lois J. Donaldson; George R. Vrablik; Edward W. Schaefer; Theodore F. Thurmon (Biochemical Genetics, 1971)

Effect of lyophilization on picornaviruses - R. Portocala; I. Samuel; M. Popescu (Archives of Virology, 1969)